Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Subclinical infection with Anaplasma phagocytophilum and gastrointestinal nematodes results in reduced weight gain in grazing weaned lambs - Jade M. Duncan; Mara S. Rocchi; Alison Stephen; Adam D. Hayward; Madeleine Maley; Heather McDougall; Sharon Brown; Leigh Andrews; Gillian Mitchell; Fiona Kenyon (The Veterinary Journal, 2026)

Fuels reduction thinning positively influences native bees, but not blooming plants, in a mixed coniferous forest - Scott R. Mitchell; Sandra J. DeBano; Mary M. Rowland; Skyler Burrows (Forest Ecology and Management, 2026)

Correction to: Blooming Plant and Bee Communities in an Inland Pacific Northwestern Forest Vary by Forest Type, Season, and Environmental Factors - Scott R. Mitchell; Sandra J. DeBano; Mary M. Rowland; Skyler Burrows; Ryan Nielson (Journal of Forestry, 2026)

The microbial communities of a tomato crop grown in Veggie under different lighting regimes on the International Space Station - Cory J. Spern; Mary E. Hummerick; Christina LM Khodadad; Cristiana J. Morales; Anirudha R. Dixit; Lashelle E. Spencer; Cary A. Mitchell; Robert C. Morrow; Raymond M. Wheeler; Gioia D. Massa (Life Sciences in Space Research, 2026)

Application of the Total Nutrient Index as a Precision Nutrition Tool to Address Dietary Recommendations Across the Life Course - Alexandra E. Cowan-Pyle; Janet A. Tooze; Lindsay M. Reynolds; Jaime J. Gahche; Johanna T. Dwyer; Diane C. Mitchell; Raymond J. Carroll; Bani K. Mallick; Regan L. Bailey (Journal of the Academy of Nutrition and Dietetics, 2026)

103 Germinal vesicle to metaphase II: Transcriptomic dynamics of single-equine oocytes following holding and in vitro maturation - S.B. Cousseau; V. Medina; C.R. Neto; M.S. Lindley; S. Loux; M.C. Azevedo; D. Rosseti; M. Mitchell; C.R.F. Pinto (Journal of Equine Veterinary Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Grazing by wild and domestic ungulates reduces floral resources and native bee abundance in a multi-use landscape - Will Glenny; Sandra J. DeBano; Mary M. Rowland; Scott R. Mitchell; Skyler Burrows; Michael J. Wisdom; Joshua P. Averett; Bridgett Naylor (Biological Conservation, 2026)

Water quality and physical impact of bushfire on HDPE & PVC-M reticulation pipes - Vaughan Mitchell; Ellen M Moon; Wenyan Wu; Jinzhe Gong (Water Research, 2026)

Mechanical jamming in pseudotachylyte-hosted breccias - David P. Dobson; Charlotte L. Bays; Thomas M. Mitchell (Tectonophysics, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Constructed value of information with iterative scoring and parametric uncertainty to identify management‐relevant research priorities for a declining raptor species - Kristin P. Davis; Mitchell J. Eaton; Emily R. Bjerre; Hillary M. White; Clint W. Boal; Jennifer H. Herner‐Thogmartin; Orin J. Robinson; Abigail J. Lawson (Conservation Biology, 2026)
Constructed value of information (CVoI) is an expert elicitation decision‐analytic tool used to prioritize sources of uncertainty based on their potential to improve decision outcomes if resolved. Despite increased application of CVoI, the robustness of CVoI prioritization of sources of uncertainty relative to differences in expert elicitation and scoring methods has not been evaluated. We engaged a group of species experts in a decision‐analytic process to elicit uncertainties, framed as alternative hypotheses, about current population declines of the American kestrel ( Falco sparverius ) in the United States. Participants scored 13 hypotheses across 3 CVoI criteria, which are defined as constructed scales. Rather than experts selecting a single score per criterion, we used a likelihood point method to incorporate parametric uncertainty in the scoring process, in which experts were given 100 points to distribute across possible score categories within the criterion‐specific constructed scale. Experts provided scores over 2 scoring rounds, with an opportunity to review and discuss initial scores between rounds. We used a Shannon entropy calculation to quantify how evenly participants allotted their points. We used simulation to evaluate the robustness of our prioritization results relative to a scoring method in which participants selected a single score category for each criterion. Participants often spread their points across 2 adjacent scores, reflecting parametric uncertainty. For one third of the hypothesis‐scoring round combinations, the prioritization results differed in approximately 50% of simulations. The highest scoring hypotheses related to how the use of artificial versus natural nest cavities affects fecundity or survival, whether winter roosting sites are a limiting factor for population growth, and whether gamebird habitat management may benefit kestrel populations. Our CVoI prioritization framework can be used to develop collaborative research that is directly relevant to a management decision and is an advance in eliciting more representative expert beliefs.

Unintended consequences of estuarine management within the trajectory of recovery: examples from the Chesapeake Bay - Jessica S. Turner; Fei Da; Molly M. Mitchell (Frontiers in Marine Science, 2026)
Estuaries are vital ecosystems that support biodiversity, human populations, and economic activities such as fisheries, aquaculture, and tourism. Managing estuarine systems often involves interventions to regulate sediment and nutrient inputs with the goal of improving water quality, and subsequently the economic values of the estuary. However, these management strategies can produce unintended consequences. The Chesapeake Bay is an estuary recovering from eutrophication which provides clear case studies for these patterns. In the Chesapeake Bay, decreased sediment inputs, resulting from shoreline stabilization and watershed modifications, can impair marsh resilience to sea level rise and disrupt sediment-light-algal interactions affecting water clarity. Likewise, reductions in riverine nutrient inputs, while beneficial for mitigating eutrophication, may contribute to surface water acidification. These outcomes complicate assessments of restoration success. Throughout other estuaries’ recovery from historical nutrient and sediment pollution, similar patterns have been observed in several other estuarine systems worldwide. Effective long-term estuarine management requires integrating diverse monitoring approaches, adaptive decision-making, and ecosystem-based strategies to balance environmental and economic objectives. Understanding both the intended and unintended effects of management actions is crucial to ensuring sustainable outcomes along the non-linear path of recovery from eutrophication, including both nutrient and sediment pollution. Future efforts should prioritize holistic assessments, stakeholder involvement, and targeted modeling to guide effective estuarine conservation and restoration.

Unravelling the ketone story. Secondary vessel use at the Ness of Brodgar, Orkney, Scotland - Julia Becher; Alexandre Lucquin; Rowan McLaughlin; Martine Regert; Mark Edmonds; Jan Blatchford; Nick Card; Anne Mitchell; Helen M. Talbot; Roy Towers; Oliver E. Craig (Organic Geochemistry, 2026)

Cover crop treatments differentially impact soil nematode communities including pathogenic genera - Roy Neilson; Andrew Christie; Ewan Findlay; Susan M. Mitchell; Katharine Preedy; David Roberts; Victoria G. Buswell (European Journal of Agronomy, 2026)

Soil and genotype-driven resource allocation trade-offs shape root exudation across crop species - Henning Schwalm; Carmen Escudero-Martinez; Molly Brown; Lawrie Brown; David Roberts; Susan M. Mitchell; Ignacio Romero Lozano; Natacha Bodenhausen; Davide Bulgarelli; Kelly Houston; Timothy S. George; Eva Oburger (Plant and Soil, 2026)
Aims Root exudates play a central role in rhizosphere processes, many of which support plant growth. While increased exudation under abiotic stresses has been frequently linked to enhanced plant resilience, crop- and genotype- and soil-specific exudation patterns under non-stress conditions remain poorly understood. This study aimed to assess how soil type and genotype influence root exudation in major and emerging European crops and to explore how root morphology and plant growth are related to exudation. Methods Four genotypes each of barley ( Hordeum vulgare ), faba bean ( Vicia faba ), potato ( Solanum tuberosum ), and sweet potato ( Ipomoea batatas (L.) Lam.) were grown in three distinct European soils under non-stress conditions. Exudates were collected using a soil-hydroponic-hybrid approach and analysed for dissolved organic carbon and nitrogen, as well as total carbohydrates, amino acids, and phenolic compounds. Biomass and root morphology were assessed to examine correlations with exudation patterns. Results Results showed that soil type and genotype affected exudation patterns, but their influence varied by crop. Plant growth was negatively correlated with exudation rates across most crops, likely reflecting a trade-off in carbon and nitrogen allocation between biomass accumulation and rhizodeposition. Root morphological traits partly correlated with root exudation rates, but no universal relationships were detected across crops. Conclusion Our results provide novel insights into belowground resource partitioning and broaden the understanding of exudation patterns to previously underexplored crops, highlighting resource allocation trade-offs shaped by genotype and soil as important drivers of exudation dynamics.

Prospective categorisation of maternal care style in Thoroughbred broodmares - Alexandra L. Moss; Orlagh O’Reilly; Amy Rand; Amy R. Holtby; Siobhan Mullan; Katharyn Mitchell; Emmeline W. Hill; Michael Salter-Townshend; Lisa M. Katz (Applied Animal Behaviour Science, 2026)

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

Nonlinear Creep Model of Fractured Rock Considering Combined Effects of Initial Macro- and Mesoscopic Damage - Ben Liu; Tao Xu; Thomas M. Mitchell; Philip G. Meredith; Michael J. Heap; John Browning; Yongping Liu; Yanchao Xue (Rock Mechanics and Rock Engineering, 2026)

Why abundance alone cannot assess sustainability in long-finned pilot whales (Globicephala melas): population structure, genetic uncertainty, and management implications - Lavinia Mitchell; Nina M. Young (Frontiers in Marine Science, 2026)
Long-finned pilot whales ( Globicephala melas ) are widely distributed across the North Atlantic and are often assessed for management as a single, abundant population. However, the species exhibits strong social organisation, stable matrilineal structure, and reproduction that occurs within social units, characteristics that shape demographic connectivity. These features raise questions about whether abundance alone provides a sufficient basis for assessing the sustainability of recurrent removals from a socially structured marine mammal population. Recent genetic and ecological studies indicate broad-scale differentiation and suggest regional structuring within the North Atlantic, yet sampling remains uneven and datasets linked directly to harvested individuals are limited. Consequently, it is not currently possible to determine how removals in the Faroe Islands are distributed across potential demographically independent populations (DIPs), matrilines or family lineages. This Mini Review synthesises current evidence on population structure, identifies key uncertainties, and evaluates post-mortem genetic sampling as a practical approach to reducing uncertainty and improving sustainability assessments for North Atlantic long-finned pilot whales.

Drivers of fine-scale space use and grazing patterns of juvenile parrotfish on western Atlantic reefs - David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Manuel González-Rivero; Alastair R. Harborne (Coral Reefs, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Reconstructing human–animal interactions via multiproxy analysis of dog paleofeces from the medieval Central Balkans - Nemanja Marković; Freya Steinhagen; Elena Marinova; Samantha Brown; Susan M. Mentzer; Christopher E. Miller; Maria A. Spyrou; Víctor Roces; Ella Reiter; Dejan Bulić; Mirjana Roksandić; Piers D. Mitchell; et al. (Archaeological and Anthropological Sciences, 2026)

Warming influences nutrient removal in mesocosms across different substrates - Abagael N. Pruitt; Jennifer L. Tank; Caroline G. T. Anscombe; Mitchell J. Liddick; Elise D. Snyder; Emma M. Thrift‐Cahall; Erik M. Curtis; Anna E. S. Vincent (Limnology and Oceanography, 2026)
Climate change is increasing stream temperatures globally, likely impacting stream ecosystem processes. We conducted a stream warming experiment at the Notre Dame Experimental Mesocosm Facility using N = 24 recirculating mesocosms to examine the effect of warming on biofilm colonization of organic and inorganic substrata and rates of nutrient removal. We conducted an experiment with three temperature treatments (20°C, 23°C, and 26°C) in mesocosms containing either decomposing sugar maple ( Acer saccharum ) leaves or cobble substrate under shaded and unshaded conditions, respectively. We measured biofilm chlorophyll a (Chl a ) on cobble, community respiration on leaf disks, and removal of ammonium (NH 4 + ‐N) and soluble reactive phosphorus weekly for 21 d. Warming did not significantly alter Chl a or community respiration (generalized linear mixed model, p > 0.05). For nutrients, however, warming increased NH 4 + ‐N removal for both leaves and cobble. For cobble, NH 4 + ‐N removal was higher at 26°C (mean = 3.5 h −1 with a 75% credible interval of [3.1, 4.0]) compared to 20°C (2.3 h −1 [1.9, 2.7]; Bayesian regression model). For leaves, NH 4 + ‐N removal was also higher at 26°C (1.1 h −1 [1.0, 1.2]) compared to 20°C (0.5 h −1 [0.4, 0.6]). In contrast, warming only altered soluble reactive phosphorus removal for cobble; removal was higher at 26°C at 1.9 h −1 [1.7, 2.2] compared to 20°C (1.1 h −1 [0.8, 1.3]). Warming did not alter soluble reactive phosphorus removal for leaves. We show that warming‐induced changes in nutrient removal are mediated by substrate, and that NH 4 + ‐N removal may be more sensitive to elevated temperatures than soluble reactive phosphorus removal, with implications for altered nutrient cycling under a warmer future.

Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Space waste: An update of the anthropogenic matter injection into Earth’s atmosphere - Leonard Schulz; Karl-Heinz Glassmeier; Moritz Herberhold; Adam Mitchell; Daniel M. Murphy; John M.C. Plane; Ferdinand Plaschke (Advances in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Volatile organic compound analysis of Humboldt Penguin (Spheniscus humboldti) preen oil: a pilot study - Dante E. Rojas; Mitchell M. McCartney; Eva Borras; Michael O. Eze; Abigail Pietrow; Jennifer J. Valvo; Cristina E. Davis (Journal of Ornithology, 2026)

Ten years on: Are raw material criticality assessments making more sense? - Baptiste Andrieu; Benjamin Adams; Mehrnoosh Heydari; Philip Mitchell; Luke Cullen; Alexey Noskov; Julian M. Allwood; André Cabrera Serrenho; Jonathan Cullen (Resources, Conservation and Recycling, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

The genetic landscape of Pacific taro: diversity, population structure, and strategic germplasm management - Caroline M. Mitchell; Amit Sukal; Anastasija Podolyan; Sera Dau; Renuma Kumar; Semi Cakaunitavuki; Preeti Nand; Connor Watson; Logotonu M. Waqainabete; Gary J. Houliston (Genetic Resources and Crop Evolution, 2026)

SuperTIGER galactic cosmic-ray source abundances for the charge interval 16 ⩽ Z ⩽ 56 - N.E. Osborn; N.E. Walsh; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; et al. (Advances in Space Research, 2026)

SuperTIGER ultra-heavy galactic cosmic ray atmospheric corrections using Geant4 simulations - N.E. Osborn; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; T. Hams; et al. (Advances in Space Research, 2026)

The role of living shorelines as a resilience strategy for nutrient reduction in estuarine systems - Emma Dodsworth; Molly M. Mitchell; Bongkeun Song; Donna M. Bilkovic; Mark J. Brush (Frontiers in Marine Science, 2026)
Introduction Tidal salt marshes provide critical ecosystem services in estuaries including the removal, storage, and transformation of nutrients, improving water quality and aquatic habitat. As tidal marshes drown from sea level rise, this service is lost, impacting estuarine resilience and leading to degradation of water quality. Living shorelines are a strategy to protect shorelines, while restoring some capacity to improve water quality. Methods In this study, we examine the magnitude of different nutrient storage and removal pathways in living shorelines, which range from short-term storage of nutrients (weeks-months) to permanent removals. Results We found that all variables (plant and algal biomass, soil characteristics and sediment nutrient fluxes) varied significantly across sites emphasizing the variability in living shoreline functions. Plant biomass, benthic microalgae biomass, soil %C, soil %N, and denitrification (net N2 fluxes) were significantly different by season. Marsh age was only significantly correlated with phosphate fluxes from the sediment, so it was not an important driver of variability in function between living shorelines. Discussion Despite the spatial variability, we found that nutrient storage and removal pathways were generally similar to those in natural marshes, reinforcing the assumption that these systems are replacements for natural marshes and an important component of resilience efforts. However, we found the short-term storage of nitrogen and phosphorus through uptake by benthic microalgae and the permanent removal of nitrogen through denitrification (both higher in living shorelines) suggests that living shorelines could maintain or improve estuarine water quality, contributing to coastal resilience.

OnabotulinumtoxinA Alters Pro- and Anti-Inflammatory Dural Macrophage Response to CSD in Female Mice - Aaron J. Schain; Diego Delgado Fajardo; Andrew M. Strassman; Subhash Kulkarni; Ron S. Broide; Amy D. Brideau-Andersen; Aubrey Manack Adams; Mitchell F. Brin; Rami Burstein (Toxicon, 2026)

OnabotulinumtoxinA Inhibits Dysregulation of Descending Pain Modulation Following Mild Traumatic Brain Injury in Mice - Robson C. Lillo Vizin; Caroline M. Kopruszinski; Janice N. Oyarzo; David W. Dodick; Ron S. Broide; Amy D. Brideau-Andersen; Mitchell F. Brin; Trent Anderson; Edita Navratilova; Frank Porreca (Toxicon, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

How would Australian women and people with a cervix like to access self-collection for cervical screening? Screening preferences from a national survey - Claire Bavor; Chloe Jennett; Emily Phillips; Louise Mitchell; Tessa Saunders; Lisa Whop; Angela Kelly-Hanku; Deborah Bateson; Julia M. L. Brotherton; Megan A. Smith; Claire Nightingale (Cancer Causes & Control, 2026)
Purpose In Australia, cervical screening is usually offered face-to-face through primary care. As self-collection offers flexibility in how and where screening can be accessed, we assessed participant preferences for flexible screening models. Methods We recruited women and people with a cervix aged 24–74 years into a national survey (December 2023–April 2024) via a paid Meta campaign and community networks. Sociodemographic factors associated with a preference for appointment- or non-appointment-based models were assessed using logistic regression, stratified by age, < 50 and ≥ 50 years. Results Among 9,586 respondents, the median age was 41 years, 67.9% lived in a major city, 82.5% were born in Australia, and 62.6% screened regularly. Most (82.6%) viewed flexible options for accessing screening as very important/important. Respondents favored non-appointment-based compared to appointment-based models, with 53.5% of those < 50 ( n = 4,842) and 49.5% of those ≥ 50 ( n = 1,257) preferring to receive a swab in the mail when due. Non-appointment-based models were preferred by participants aged < 50 and ≥ 50 years who were never-screened (adjOR = 1.52, 95% CI = 1.18–1.96, p = 0.001; adjOR = 2.91, 95% CI = 1.67–5.09, p < 0.001), irregular screeners (adjOR = 1.58, 95% CI = 1.36–1.85, p < 0.001; adjOR = 1.52, 95% CI = 1.17–1.98, p = 0.002) and recently eligible for screening (adjOR = 1.64, 95% CI = 1.08–2.50, p = 0.02) compared to regular screeners. Convenience was the most common reason for participants’ preferred screening model (87.4% non-appointment-based; 55.1% appointment-based). Conclusion Flexibility in how cervical screening can be accessed appeals to many screen-eligible people. Further research trialing different models assessing screening uptake and clinical pathways to follow-up care is needed.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Legacy effects of cover crops on weed biomass and yield of the subsequent corn crop - Barbara Baraibar; Brosi A. Bradley; Mitchell C. Hunter; Charles M. White; Denise M. Finney; Jason P. Kaye; Megan E. Schipanski; David A. Mortensen (European Journal of Agronomy, 2026)

Depth affects the population dynamics on a soft coral-dominated reef on the Great White Wall, Fiji - Nile P. Stephenson; Katie M. Delahooke; Charlotte G. Kenchington; Jone Waitaiti; Alice A. Ball; Victor E. Bonito; Andrea Manica; Emily G. Mitchell (Coral Reefs, 2026)
Soft corals (order Alcyonacea) are an important component of tropical coral reefs, and often form locally abundance dense carpets. Some soft coral species are prone to bleaching and heat stress like scleractinian, reef-forming corals, but others appear resistant to bleaching stressors. Despite the importance of soft corals in tropical reefs, there is limited knowledge regarding their demographic ecology. Spatial point process analysis (SPPA) enables inference of ecological processes underlying spatial distributions of individuals in a community by investigating the fit of models of known processes to observed spatial patterns. SPPA can also quantify how these underlying ecological processes change with environmental gradients (such as depth). We used SPPA to investigate the population ecology on the Great White Wall (GWW), Fiji—a vertical reef dominated by Nephtheidae soft corals alongside other filter feeders and algae. We found that a combination of reproductive and habitat association processes best explained the spatial patterns on the GWW. We found that the best-fit underlying ecological processes changed with depth, and that Nephtheidae soft corals became more dominant on deeper parts of the wall, likely due to a combination of reproductive lability, fast growth rates, and increasing suitable habitat associated with filter-feeding. Even where the Nephtheidae were most dominant, other filter feeders were able to persist. This mixed community composition could be because the Nephtheidae feed in periods of high current, and temporal niche partitioning in feeding could be permitting biodiversity on the GWW, allowing for hydroids and sponges to coexist with the Nephtheidae.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Tidal marsh species mapping using commercial satellite imagery for enhanced coastal management in Chesapeake Bay - Megan M. Coffer; Rebecca Trinh; Molly Mitchell; Kory Angstadt; David Stanhope; Zhonghui Lv; Karinna Nunez; Nicole D. Bartlett; Daniel Wiltsie; Sully Sullivan; Blake A. Schaeffer (Remote Sensing Applications: Society and Environment, 2026)

Impact of physiological transitions during forward processing on Shiga-toxin producing Escherichia coli risks in lettuce - Joshua Ombaka Owade; Teresa M. Bergholz; Jade Mitchell (Food Microbiology, 2026)

Hippocampal Bioenergetics and Metabolic Profiling Identifies Fatty Acid Oxidation as a Potential Therapeutic Target in Traumatic Brain Injury - Di Zhou; Mengxuan Shi; Mitchell D. Kilgore; Yuwen Xiu; Yingjie Wang; Danni Wang; Thin Yadanar Sein; Charles Vidoudez; Amin Iskender; Gaby A. Moyano; Lauren M. Dumont; Yinghua Jiang; et al. (Molecular Neurobiology, 2026)
Traumatic brain injury (TBI) causes lasting neurological impairments, particularly learning and memory deficits associated with hippocampal damage. Emerging evidence suggests that hippocampal vulnerability may be linked to bioenergetic dysfunction, though its role remains poorly defined. A deeper understanding of post-TBI metabolic disturbances and their association with pathological outcomes could reveal novel therapeutic targets. In this study, we conducted functional bioenergetic assessments and multi-omics analyses on hippocampal slices using a mouse controlled cortical impact model of TBI. Seahorse analysis revealed a significant reduction in mitochondrial oxidative phosphorylation in dentate gyrus (DG) slices at day 1 (acute phase), which recovered by day 7 (subacute phase) post-TBI. Metabolomic profiling revealed acute impairments in purine nucleotide, glucose, amino acid, and fatty acid metabolism, most of which normalized by day 7. Isotope tracing indicated enhanced octanoate-derived fatty acid oxidation (FAO) in DG slices at day 7 post-TBI. Proteomics confirmed suppressed purine metabolism at day 1 across hippocampal subregions, while FAO remained preserved at day 1 and became significantly elevated by day 7, suggesting a compensatory metabolic adaptation. Administration of sodium octanoate, a medium-chain fatty acid, at 1 h post-TBI enhanced mitochondrial respiration at 24 h, reduced microglial counts at 48 h, and attenuated neurodegeneration by day 3. These findings identify FAO enhancement as a promising metabolic strategy to restore hippocampal bioenergetics and promote neuroprotection following TBI.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Blooming Plant and Bee Communities in an Inland Pacific Northwestern Forest Vary by Forest Type, Season, and Environmental Factors - Scott R. Mitchell; Sandra J. DeBano; Mary M. Rowland; Skyler Burrows; Ryan Nielson (Journal of Forestry, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Preserving tororaro’s legacy: conservation genetics of in-situ and ex-situ populations of Muehlenbeckia astonii (Polygonaceae) - Caroline M. Mitchell; Connor Watson; Peter B. Heenan (New Zealand Journal of Botany, 2025)

Detection of Cryptosporidium spp. and Giardia duodenalis DNA in wild deer in Scotland - Paul M. Bartley; Clare M. Hamilton; Jackie Thomson; Ross Bacchetti; Mairi C. Mitchell; Tom N. McNeilly; Renata Pimentel Bandeira de Melo; Adam D. Hayward; Frank Katzer; Beth Wells (Veterinary Parasitology, 2025)

Establishing baseline control water values for differential scanning calorimetry (DSC) in cryoprotectant exploration - P.U. Ashvin Iresh Fernando; Nick Mitchell; Olivier Montmayeur; Brianna M. Fernando; Matthew A. Fort; John G. Tsavalas; Emily Asenath-Smith (Cryobiology, 2025)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Full-length mRNA sequencing resolves novel variation in 5′ UTR length for genes expressed during human CD4 T-cell activation - Cassandra R. Woolley; Julia H. Chariker; Eric C. Rouchka; Easton E. Ford; Elizabeth Hudson; Kamille M. Rasche; Caleb S. Whitley; Zachary Vanwinkle; Carolyn R. Casella; Melissa L. Smith; Thomas C. Mitchell (Immunogenetics, 2025)

Integrative use of conventional and DNA metabarcoding methods reveals high diversity, prevalence and intensity of gastrointestinal parasites in pigs from Victoria, Australia - Ghazanfar Abbas; Yuet On Lee; Hannah Mitchell; Abdul Ghafar; Mark A. Stevenson; Charles G. Gauci; Leah G. Starick; Regina M. Fogarty; Bernie Gleeson; Dianne E. Phillips; Tao Wang; Robin B. Gasser; et al. (Research in Veterinary Science, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

Correction: One-step Immobilization of Human α-1-acid Glycoprotein on Magnetic Beads: A Rapid Method for Small Molecule hAGP Binding Study - Ting Wang; Hamid Samareh Afsari; Steven Anderlot; Aaron M. Teitelbaum; Mitchell E. Taub (The AAPS Journal, 2025)

A modified-live Mannheimia haemolytica expressing Mycoplasma bovis EFTu and Hsp70 induced systemic and mucosal antibody responses in American bison but failed to fully protect against Mycoplasma bovis challenge. - Bryan S. Kaplan; Rohana P. Dassanayake; Bradley O. Chriswell; William D. Boatwright; Steven C. Olsen; Mitchell V. Palmer; Paola M. Boggiatto; Carly R. Kanipe; Eduardo Casas; Robert E. Briggs; Fred M. Tatum (Veterinary Microbiology, 2025)

Bayesian latent class analyses show that serological testing outperforms conventional diagnostic methods for the detection of Ascaris in (individual) pigs - Ghazanfar Abbas; Hannah Mitchell; Mark Stevenson; Yuet On Lee; Abdul Ghafar; Charles Gauci; Hagan Brodziak; Leah G. Starick; Regina M. Fogarty; Bernie Gleeson; Dianne Phillips; Tao Wang; et al. (The Veterinary Journal, 2025)

Evaluating climatic and anthropogenic drivers of fire activity over four millennia at Eilandvlei, southern Cape coast, South Africa - Stella G. Mosher; Mitchell J. Power; Brian M. Chase; Lynne J. Quick; Torsten Haberzettl; Thomas Kasper; David R. Braun; J. Tyler Faith (Quaternary Science Reviews, 2025)

Trends in Fomepizole Use for Acetaminophen Poisoning in the United States; 2013–2024 - Mitchell D’Aloia; Dale Smith; Randy Boley; Emily Schamber; Dillon Thorpe; Trevonne M. Thompson; Neeraj Chhabra (Journal of Medical Toxicology, 2025)
Background Fomepizole has been suggested as adjunctive therapy for severe acetaminophen poisoning though clinical efficacy is unknown. We sought to determine trends in the use of fomepizole for acetaminophen poisoning. Methods This is a cross-sectional analysis of hospitalized patients with acetaminophen poisoning from January 2013 through December 2024, using Epic Cosmos, a research database of 298 million patients nationally. We identified encounters involving acetaminophen poisoning by International Classification of Diseases, version 10 (ICD-10-CM) code. Data extracted included administration of N-acetylcysteine (NAC) and fomepizole, demographic data, and outcomes of death and liver transplantation. Data were analyzed using descriptive statistics to identify trends and multivariable logistic regression to determine associations with death. Results There were 114,111 hospital encounters involving acetaminophen poisoning with 64,957 (56.92%) receiving NAC, and 1,552 (1.36%) receiving fomepizole. In 2013, 0.44% of NAC-treated acetaminophen poisoning cases also received fomepizole. This rose to 6.27% in 2024. From 2013 to 2019, the proportion of NAC-treated acetaminophen cases receiving fomepizole was stable, but from 2019 to 2024, there was a 1029.64% increase in fomepizole use. Regression modeling indicated increased odds for death (OR = 5.88, aOR = 5.32 [95% CI: 4.52, 6.27]) among those who received fomepizole in addition to NAC, indicating increased fomepizole use in patients with severe toxicity. Conclusion Fomepizole use in acetaminophen poisoning has risen dramatically since 2019, particularly among patients at highest risk for death and liver transplantation. It is of critical importance to determine the efficacy of fomepizole for acetaminophen poisoning.

Geographic, Taxonomic and Metric Gaps in Biodiversity Research Limit Evidence‐Based Conservation in Agricultural Landscapes: An Umbrella Review - Jonathan Bonfanti; Joseph Langridge; A. Avadí; N. Casajus; A. Chaudhary; G. Damour; N. Estrada‐Carmona; S. K. Jones; D. Makowski; M. Mitchell; R. Seppelt; Damien Beillouin (Ecology Letters, 2025)
Agriculture is fundamentally dependent on biodiversity, yet unsustainable management practices increasingly threaten various organisms and ecosystem services. Confronting the global crisis of biodiversity loss requires a thorough understanding of the gaps, clusters and biases in existing knowledge across various management practices, spatial scales, and taxonomic groups. We undertook a comprehensive literature review, synthesising secondary data from 200 meta‐analyses on agricultural management impacts on biodiversity in croplands. Our systematic map covers 1885 comparisons (mean effect sizes), from over 9000 primary studies. In the latter, seven high‐income countries prevail (notably the USA, China and Brazil), with particular focus on fertiliser use, phytosanitary interventions and crop diversification. This emphasis on individual practices overshadows research at the farm and landscape levels. In secondary evidence, arthropods and microorganisms are most frequently studied, while annelids, vertebrates and plants are less represented. Evidence predominantly stems from averaged abundance data, revealing substantial gaps in studies on functional and phylogenetic diversity. Our findings highlight the need to analyse combinations of multiple practices to accurately reflect real‐world farming contexts, and covering a wider range of taxa, biodiversity metrics and spatial levels, to enable evidence‐based conservation strategies in agriculture. Given the uneven evidence on agricultural impacts, caution is required when applying meta‐analytical findings to public policies and global assessments.

One-step Immobilization of Human α-1-acid Glycoprotein on Magnetic Beads: A Rapid Method for Small Molecule hAGP Binding Study - Ting Wang; Hamid Samareh Afsari; Steven Anderlot; Aaron M. Teitelbaum; Mitchell E. Taub (The AAPS Journal, 2025)

P12-35 From neat compounds to complex mixtures: Microphysiological systems for cardiotoxicity safety testing of botanical extracts - M. Gossmann; A. Monteiro da Rocha; S. Zhao; J. Krzykwa; C. Mitchell; J. Wu; P. Linder (Toxicology Letters, 2025)

S03-04 Induction of genomic damage by natural plant constituents: development of genotoxicity testing strategies - H. Stopper; S. Pfuhler; S. Smith-Roe; J.T. MacGregor; N. Mei; C.A. Mitchell; M. Embry; J. van Benthem; E. Zeiger; K.L. Witt (Toxicology Letters, 2025)

Novel primers for the detection and differentiation of S. zooepidemicus and S. equi by PCR - Tanya Mikaiel; Andrew Waller; Alastair Foote; Jacqueline M Cardwell; Judy Mitchell; Simon L. Priestnall (Research in Veterinary Science, 2025)

GMFOLD: Subgraph matching for high-throughput DNA-aptamer secondary structure classification and machine learning interpretability - Paolo Climaco; Noelle M. Mitchell; Matthew J. Tyler; Kyungae Yang; Anne M. Andrews; Andrea L. Bertozzi (Mathematical Biosciences, 2025)

Impacts of orthophosphate addition on chloramine decay and biofilm development in a model drinking water distribution system - Mahmoud H. Badawy; Mitchell G. Cooke; Kimia Aghasadeghi; Sigrid Peldszus; Robin M. Slawson; Peter M. Huck (Water Research, 2025)

A coral microatoll record of sea-level rise, interseismic deformation, and El Niño in La Union, Philippines since 1906 CE - Gina M. Sarkawi; Aron J. Meltzner; Dongju Peng; Joanne T.Y. Lim; Xinnan Li; Rohan Gautam; Anandh Gopal; Andrew Mitchell; Loraine Faye Sarmiento; Jennifer Weil-Accardo; Kathrine V. Maxwell; Junki Komori; et al. (Marine Geology, 2025)

A time-dependent microplane model for deformation and fracturing of brittle rock - Yang Yuan; Tao Xu; Philip G. Meredith; Thomas M. Mitchell; Michael J. Heap; Zhen Heng (Computers and Geotechnics, 2025)

An Evaluation of the Usage of Internet Resources by Patients with Lung Cancer - Sandy Lum-Wang; Paris-Ann Ingledew; Hannah Carolan; Emma M. Dunne; Elisa Chan; Ying Wang; Mitchell Liu; Brandon S. Chai (Journal of Cancer Education, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Priming the decomposition of cover crop residues in no-till organic cropping systems - Delaney A. Sondag; Amélie C.M. Gaudin; Jeffery P. Mitchell; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2025)

From whole bodies to single cells: A guide to transcriptomic approaches for ecology and evolutionary biology - Katja M. Hoedjes; Sonja Grath; Nico Posnien; Michael G. Ritchie; Christian Schlötterer; Jessica K. Abbott; Isabel Almudi; Marta Coronado‐Zamora; Esra Durmaz Mitchell; Thomas Flatt; Claudia Fricke; Amanda Glaser‐Schmitt; et al. (Molecular Ecology, 2025)
RNA sequencing (RNAseq) methodology has experienced a burst of technological developments in the last decade, which has opened up opportunities for studying the mechanisms of adaptation to environmental factors at both the organismal and cellular level. Selecting the most suitable experimental approach for specific research questions and model systems can, however, be a challenge and researchers in ecology and evolution are commonly faced with the choice of whether to study gene expression variation in whole bodies, specific tissues, and/or single cells. A wide range of sometimes polarised opinions exists over which approach is best. Here, we highlight the advantages and disadvantages of each of these approaches to provide a guide to help researchers make informed decisions and maximise the power of their study. Using illustrative examples of various ecological and evolutionary research questions, we guide the readers through the different RNAseq approaches and help them identify the most suitable design for their own projects.

Coexistence, Extinction and Survival—The Evolutionary History of Bison Species in Western Eurasia - Bastien Llamas; Ayla L. van Loenen; Kieren J. Mitchell; Emilia Hofman‐Kamińska; Hervé Bocherens; Holly Heiniger; Martina Pacher; Daniel Makowiecki; Giedrė Piličiauskienė; Dorothée G. Drucker; David Brown; Zoe A. Thomas; et al. (Global Change Biology, 2025)
European bison ( Bison bonasus ) are one of the few European megafaunal species to survive the Late Pleistocene mass megafaunal extinction. Current conservation management efforts have proceeded in the absence of information about their evolutionary history, which has been obscured by recent severe population bottlenecks. We characterized mitochondrial genomes from 135 ancient bison samples spanning > 50,000 years (> 50 ka) across the Eurasian continent and detected three distinct phylogenetic groups: two distinct clades of European bison and the extinct steppe bison ( Bison priscus ). The geographical distributions and dietary/ecological signatures of the three groups overlapped during the Late Pleistocene climate cycles and tracked environmental changes including vegetation cover and human impacts. The abundance of European bison specimens responded negatively to the extent of forest cover, including Holocene cycles of abrupt atmospheric‐ocean circulation changes originating in the North Atlantic. European bison remain preferentially adapted to an open environment, but with today's anthropogenic landscapes, are now largely restricted to forest habitats with negative implications under scenarios of future environmental change.

Spontaneous social media: An exploratory study of young adults’ BeReal uses and gratifications - J. Mitchell Vaterlaus; Sophia M. Chow (The Social Science Journal, 2025)

Early Childhood Nutrition-Related Policy, System, and Environmental-Focused Evaluation: A Qualitative Study Exploring Knowledge, Barriers, and Opportunities - Elder Garcia Varela; Alaina M. Mitchell; Isabella Bolivar; Megan A. McVay; Karla P. Shelnutt; David Miller; Amy R. Mobley (Journal of Nutrition Education and Behavior, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Fluid pressure fluctuations and the seismic signature of a fault-controlled fluid migration pulse - Ashley Stanton-Yonge; Almudena Sánchez De La Muela; Rebecca K. Pearce; James O.S. Hammond; Thomas M. Mitchell; Stephen P. Hicks; W. Ashley Griffith; Max Moorkamp; Philip G. Meredith; José Cembrano (Earth and Planetary Science Letters, 2025)

The effect of recent concussion history on dynamic visual acuity and balance control in varsity athletes - Katelyn M. Mitchell; Kristine N. Dalton; Michael E. Cinelli (Experimental Brain Research, 2025)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Pressure management strategies for large-scale aquifer recharge: Mitigating the potential for injection-induced earthquakes - Ethan W. Conley; Cameron R. Chambers; John B. Ogunleye; Lars W. Koehn; Dan Holloway; Jamie Heisig-Mitchell; Martin Chapman; Mahesh Parija; Ryan M. Pollyea (Journal of Hydrology, 2025)

Climate and Emissions Benefits of Renewable Diesel: In-Use Testing of a Tier 2 Commercial Harbor Craft - Julia A. Billington; Bo Yang; Wayne Sobieralski; Christian Fehrenbacher; Gavin M. Hoch; Andrew L. Damiano; Razieh Nadafianshahamabadi; Alexander R. Mitchell; David C. Quiros (Emission Control Science and Technology, 2025)

Mapping illegal trade routes of live cheetahs from the Horn of Africa to the Arabian Peninsula - Paul H. Evangelista; Nicholas E. Young; Darin K. Schulte; Patricia D. Tricorache; Matthew W. Luizza; Sarah M. Durant; Kelly W. Jones; Nicholas Mitchell; Tomas Maule; Abdullahi H. Ali; Redae T. Tesfai; Peder S. Engelstad (Conservation Biology, 2025)
Less than 7000 cheetahs ( Acinonyx jubatus ) persist in Africa. Although human–wildlife conflict, habitat degradation, and loss of prey are major threats to cheetah populations, illegal trade in live cubs for pets may have the most significant impact on populations in the Horn of Africa. We developed a novel, stepwise decision support tool to predict probable trafficking routes by leveraging the power of distinct modeling approaches. First, we created a cheetah habitat suitability index (HSI) to determine where source cheetah populations may occur. We then created a trafficking network model linking known and predicted cheetah populations with documented destinations in the Arabian Peninsula. A significant area in Eastern Ethiopia and Northern Somalia was estimated to harbor undocumented cheetahs. When these predicted populations were used as a supply source, the trafficking network model showed multiple routes passing through Somaliland and across the Gulf of Aden to Yemen, supporting the notion that undocumented cheetahs may be supplying pet market demands. Though we demonstrate how our decision support tool can inform law enforcement, conservation strategies, and community engagement, we caution that our results are not fully validated due to limited accessibility, alternative trafficking routes, and the cryptic nature of illegal wildlife trade.

Interplay between quantitative trait loci for stem strength and agronomic traits in a wheat doubled-haploid population - J. Allan Feurtado; Letitia M. Da Ros; Shola H. Kareem; Breenah Mulligan; Daiqing Huang; Lanette Ehman; Parul Jain; Leah K. Flatman; Hanna Hovland; Jeff Hovland; Brett Beckie; Richard D. Cuthbert; et al. (Field Crops Research, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Process intensification in hydrothermal liquefaction of biomass: A review - Shahin Mazhkoo; Salman Soltanian; Habeeb O. Odebiyi; Omid Norouzi; Mitchell Ubene; Aneela Hayder; Omid Pourali; Rafael M. Santos; Robert C. Brown; Animesh Dutta (Journal of Environmental Chemical Engineering, 2025)

Historical increases in plant density increased vegetative maize biomass while breeding increased reproductive biomass and allocation to ear over stem - Ezequiel Saenz; Alejo Ruiz; Cintia Sciarresi; Kyle King; Mitchell Baum; Antonella Ferela; Gerasimos J.N. Danalatos; Brenda Gambin; George Kalogeropoulos; August Thies; Raziel A. Ordóñez; Slobodan Trifunovic; et al. (Field Crops Research, 2025)

Uranium removal from environmental water and nuclear waste: Nanomaterial solutions and their environmental sustainability - Ahmed S. Helal; Miryana Hémadi; John S. Lomas; Souad Ammar; Ali Abdelhafiz; Said M. El-Sheikh; Sheta M. Sheta; Mitchell Galanek; Mohamed H. Hassan; Jeng-Kuei Chang; Ju Li (Chemical Engineering Journal, 2025)

Inference from eDNA-based field distributions vs laboratory analysis of isolated strains: physiological performance of non-marine Antarctic biota - Phil M. Novis; Adrian Monks; John E. Hunt; Byron Adams; Manpreet K. Dhami; Ji Hee Kim; Caroline Mitchell; Fraser Morgan; Ian Hawes; Jackie Aislabie; Paul Broady (Polar Biology, 2025)
Environmental DNA (eDNA) is frequently used to infer distributions of microorganisms in Antarctica. Their distributions relative to environmental variables are, in turn, sometimes used to infer their physiological range (and a relationship between the two is generally assumed for conservation purposes). We sought to determine whether ecological inferences based on distributions accurately reflect tolerances of the organisms concerned, using 249 legacy non-marine samples from a latitudinal gradient between 72 and 86°S, Antarctica. A cyanobacterium, a heterotrophic bacterium, two eukaryotic algae, two fungi, and a moss were isolated into culture, and their field distributions inferred using eDNA analysis of the samples above. Tolerances of each organism with respect to environmental predictors were then inferred from the eDNA distribution and metadata using Generalised Additive Models. We then measured growth of the cultured isolates in response to a set of these predictors. Laboratory responses were then compared to inferences from the eDNA/metadata. Predictions from eDNA/metadata agreed with the results of physiological laboratory experiments for strains that were detected at high taxonomic resolution in the field samples. However, errors were never completely eliminated, and direct contradictions occurred when strains were represented at lower taxonomic resolution in the field data. We found that accurate ecological inference from eDNA studies would be best achieved via maximising both taxonomic resolution (through marker choice/read length) and ecological signal (through careful sampling design and rigorous metadata collection).

Narrow Margins: Aerobic Performance and Temperature Tolerance of Coral Reef Fishes Facing Extreme Thermal Variability - Grace O. Vaughan; Daniel M. Ripley; Matthew D. Mitchell; Dain McParland; Jacob L. Johansen; Holly A. Shiels; John A. Burt (Global Change Biology, 2025)
Climate change is driving rising average sea temperatures and the intensification of thermal variability. Tropical coral reef fishes have evolved under thermally stable conditions to function optimally within a narrow temperature range, with many currently living close to their upper thermal limits. However, recent work has demonstrated that some species possess additional capacity, such as reductions in basal metabolic rates (i.e., ‘plastic floors’), to compensate for the acute effects of thermal challenges when assessed over multigenerational timeframes. In this study, we use the ‘plastic floors and concrete ceilings’ hypothesis to generate and then test predictions regarding the thermal physiology of reef fishes in the world's hottest and most thermally variable coral reef ecosystem (southern Arabian/Persian Gulf). By comparing three species of reef fishes ( Scolopsis ghanam , Ecsenius pulcher and Cheilodipterus novemstriatus ) from the southern Arabian/Persian Gulf, with an annual temperature range of 18.0°C–36.5°C, to conspecifics from nearby but more thermally benign (~21.0°C–32.0°C) reefs in the Gulf of Oman, we find enhanced upper thermal limits and a broadening of the temperature performance curves for aerobic scope in the Arabian/Persian Gulf, but no evidence for changes in basal metabolic rates (‘plastic floors’). Despite these conserved increases in temperature tolerance, the summer thermal safety margins of Arabian/Persian Gulf fishes were 1.47°C lower than those of conspecifics from the Gulf of Oman, demonstrating that while the temperature tolerance of tropical coral reef fishes is somewhat plastic over multigenerational timeframes, its rate of change is likely insufficient to keep pace with the rising average temperatures and growing thermal variability expected under climate change.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The genetic structure of the ash obligate moth prays fraxinella suggests that it is not affected by current habitat fragmentation - Fiona A. Plenderleith; Lesley T. Lancaster; Jenni A. Stockan; Justin M. J. Travis; Ruth J. Mitchell (Journal of Insect Conservation, 2025)
Tree diseases may cause the extirpation or functional extinction of a common tree species on large spatial scales. For example, ash dieback ( Hymenoscyphus fraxineus ) is expected to cause widespread loss of European ash ( Fraxinus excelsior ). This type of widespread loss of a tree species may have consequences for the ability of some insects to move between woodlands, particularly obligate species (species reliant on one tree species for food). Our aim was to use ddRAD-seq genetic data to determine the population structure of Prays fraxinella (ash bud moth), an ash-obligate micro-moth, and to assess its ability to maintain connectivity across fragmented patches of native broadleaf woodlands. We found no evidence of genetic structuring at local (up to 44 km) spatial scales, and no evidence of inbreeding. At regional scales (up to 426 km), we found evidence of mixed ancestry and long-distance dispersal. Our research highlights that given its ability to maintain gene flow in areas where woodlands have historically been very fragmented, P. fraxinella may continue to maintain connectivity under moderate future tree losses under ongoing ash dieback outbreaks. Implications for insect conservation: Our research highlights the potential indirect impacts of ash-dieback through losses in connectivity. This approach should be extended to other ash-obligate species, under various levels of existing fragmentation, to inform conservation strategies more fully for managing ash dieback.

Distinct Longitudinal Changes in EEG Measures Reflecting Functional Network Disruption in ALS Cognitive Phenotypes - Marjorie Metzger; Stefan Dukic; Roisin McMackin; Eileen Giglia; Matthew Mitchell; Saroj Bista; Emmet Costello; Colm Peelo; Yasmine Tadjine; Vladyslav Sirenko; Lara McManus; Teresa Buxo; et al. (Brain Topography, 2025)
Amyotrophic lateral sclerosis (ALS) is characterised primarily by motor system degeneration, with clinical evidence of cognitive and behavioural change in up to 50% of cases. We have shown previously that resting-state EEG captures dysfunction in motor and cognitive networks in ALS. However, the longitudinal development of these dysfunctional patterns, especially in networks linked with cognitive-behavioural functions, remains unclear. Longitudinal studies on non-motor changes in ALS are essential to further develop our understanding of disease progression, improve care and enhance the evaluation of new treatments. To address this gap, we examined 124 ALS individuals with 128-channel resting-state EEG recordings, categorised by cognitive impairment (ALSci, n = 25), behavioural impairment (ALSbi, n = 58), or non-impaired (ALSncbi, n = 53), with 12 participants meeting the criteria for both ALSci and ALSbi. Using linear mixed-effects models, we characterised the general and phenotype-specific longitudinal changes in brain network, and their association with cognitive performance, behaviour changes, fine motor symptoms, and survival. Our findings revealed a significant decline in $$\:θ\:$$ -band spectral power over time in the temporal region along with increased $$\:{γ\:}_{l}$$ -band power in the fronto-temporal region in the ALS group. ALSncbi participants showed widespread β-band synchrony decrease, while ALSci participants exhibited increased co-modulation correlated with verbal fluency decline. Longitudinal network-level changes were specific of ALS subgroups and correlated with motor, cognitive, and behavioural decline, as well as with survival. Spectral EEG measures can longitudinally track abnormal network patterns, serving as a candidate stratification tool for clinical trials and personalised treatments in ALS.

DNA metabarcoding of stomach contents shows predation impacts of black rats on island birds after a resource pulse are driven by numerical not functional response - Joanna K. Carpenter; Alexander J. F. Verry; Kieren J. Mitchell; Katherine Trought; Adrian Monks; John Innes; James Griffiths; Max Harvey; Janet M. Wilmshurst (Biological Invasions, 2025)
Generalist predator populations often surge during resource pulses but decline sharply afterwards and shift to alternative prey sources, which experience elevated predation rates. Understanding these numerical and functional responses of predators to resource pulses is especially important for effectively managing island ecosystems, where invasive mammals are generalist predators and vulnerable indigenous birds are alternative prey. We used DNA metabarcoding of stomach contents to test whether the proportion of black rats ( Rattus rattus ) consuming birds changed during and after a mast seeding year in a New Zealand beech forest. Contrary to prevailing assumptions that black rats in forests consume birds only occasionally and increase their consumption of birds once a resource pulse finishes, we found that the overall proportion of rats consuming birds was surprisingly high (19.4%), and that the proportion of rats consuming birds did not change significantly across the three years of a beech mast cycle. We detected 15 unique bird taxa in the rat stomachs and 40 unique plant taxa. The frequency of beech consumption declined across the three years, as predicted. We conclude that (1) forest birds are a common part of rat diet rather than an occasional opportunistic prey item, and (2) the impact of black rats on indigenous birds following seed pulses is predominantly driven by the numerical response (increased numbers of rats present) rather than a functional (prey switching) response. Conservation interventions that seek to maximally and consistently suppress rats are therefore likely to have the best outcomes for birds.

Using Community Composition and Successional Theory to Guide Site‐Specific Coral Reef Management - Orion S. McCarthy; Emily L. A. Kelly; Anela K. Akiona; Samantha M. Clements; Tatiana Martinez; Nicole E. Pedersen; Cole Peralto; Sarah L. Romero; Mitchell H. Smelser; Kristy Wong Stone; Russell T. Sparks; Jennifer E. Smith (Global Change Biology, 2025)
High spatial or temporal variability in community composition makes it challenging for natural resource managers to predict ecosystem trajectories at scales relevant to management. This is commonly the case in nearshore marine environments, where the frequency and intensity of disturbance events vary at the sub‐kilometer to meter scale, creating a patchwork of successional stages within a single ecosystem. The successional stage of a community impacts its stability, recovery potential, and trajectory over time in predictable ways. Here we demonstrate the value of successional theory for interpreting fine‐scale community heterogeneity using Hawaiian coral reefs as a case study. We tracked benthic community dynamics on 36 forereefs over a 6‐year period (2017–2023) that captures impacts from high surf events, a marine heatwave, and unprecedented shifts in human behavior due to the COVID‐19 pandemic. We document high spatial variation in benthic community composition that was only partially explained by island and environmental regime. Through hierarchical clustering, we identify three distinct community types that appear to represent different successional stages of reef development. Reefs belonging to the same community type exhibited similar rates of change in coral cover and structural complexity over time, more so than reefs located on the same island. Importantly, communities that were indicative of early succession (low coral cover reefs dominated by stress‐tolerant corals) were most likely to experience an increase in coral cover over time, while later‐stage successional communities were more likely to experience coral decline. Our findings highlight the influence of life history and successional stage on community trajectories. Accounting for these factors, not simply overall coral cover, is essential for designing effective management interventions. Site‐specific management that accounts for a community's unique composition and history of disturbance is needed to effectively conserve these important ecosystems.

Parasitoid avoidance of intraguild predation drives enemy complementarity in a multi‐trophic ecological network - Andrew B. Hennessy; Riley M. Anderson; Nora Mitchell; Kailen A. Mooney; Michael S. Singer (Ecology, 2025)
How consumer diversity determines consumption efficiency is a central issue in ecology. In the context of predation and biological control, this relationship concerns predator diversity and predation efficiency. Reduced predation efficiency can result from different predator taxa eating each other in addition to their common prey (interference due to intraguild predation). By contrast, multiple predator taxa with overlapping but complementary feeding niches can generate increased predation efficiency on their common prey (enemy complementarity). When viewed strictly from an ecological perspective, intraguild predation and enemy complementarity are opposing forces. However, from an evolutionary ecology perspective, predators facing strong intraguild predation may evolve traits that reduce their predation risk, possibly leading to niche complementarity between enemies; thus, selection from intraguild predation may lead to enemy complementarity rather than opposing it. As specialized predators that live in or on their hosts, parasitoids are subjected to intraguild predation from generalist predators that consume the parasitoids' hosts. The degree to which parasitoid–predator interactions are ruled by interference versus enemy complementarity has been debated. Here, we address this issue with field experiments in a forest community consisting of multiple species of trees, herbivorous caterpillars, parasitoids, ants, and birds. Our experiments and analyses found no interference effects, but revealed clear evidence for complementarity between parasitoids and birds (not ants). Parasitism rates by hymenopterans and dipterans were negatively associated with bird predation risk, and the variation in the strength of this negative association suggests that this enemy complementarity was due to parasitoid avoidance of intraguild predation. We further argue that avoidance of intraguild predation by parasitoids and other arthropod predators may explain enigmatic patterns in vertebrate–arthropod–plant food webs in a variety of terrestrial ecosystems.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Chemical succession of naphthenic acid fraction compounds in reclamation landscape mesocosms established on centrifuged and co-mixed fluid fine tailings from the Athabasca oil sands - Mitchell E. Alberts; Ian J. Vander Meulen; Dani Degenhardt; Kerry M. Peru; Dena W. McMartin; John V. Headley (Science of The Total Environment, 2024)

Aquatic hazard and risk posed by four pesticides detected in waterways discharging to the Great Barrier Reef, Australia: Part 2. Hazard and risk assessment - Hannah C. Mitchell; Michael St.J. Warne; Reinier M. Mann; Catherine A. Neelamraju; Ryan D.R. Turner (Science of The Total Environment, 2024)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Applying acoustic telemetry, vessel tracking and fisher knowledge to investigate and manage fisher-shark conflict at Lord Howe Island, Australia - Jonathan D. Mitchell; Victoria Camilieri-Asch; Sallyann Gudge; Fabrice R. A. Jaine; Victor M. Peddemors; Tim J. Langlois (Marine Biology, 2024)
Fisher-shark conflict is occurring at Lord Howe Island, Australia due to high levels of Galapagos shark ( Carcharhinus galapagensis ) depredation (where sharks consume hooked fish) and bycatch. Depredation causes costly loss of target catch and fishing gear and increased mortality of target species, and sharks can be injured or killed when bycaught. This study applied acoustic telemetry and vessel tracking from 2018 to 2021 to identify; (1) how the movements of 30 tagged sharks and activity of six fishing vessels overlapped, and (2) where key ‘hotspots’ of overlap occurred. Fisher surveys were also conducted to collect information about mitigating shark interactions. Residency index analysis indicated that three sharks tagged at a fish waste dumping site had markedly higher residency. Core home ranges of sharks overlapped with higher fishing activity at four ‘hotspots’. Statistical modelling indicated positive linear effects of fishing activity and bathymetric complexity on shark detections and tagged sharks were present for 13% of the total time that vessels were fishing close to acoustic receivers. Spatio-temporal overlaps between shark movements and fishing activity could potentially have occurred because sharks learned to associate fishing vessels with food (i.e. hooked fish) and because fishers and sharks utilise highly productive shelf edge areas, however more research is needed to investigate these relationships. Fishers reported that rotating fishing areas and reducing time at each location, fishing deeper than 100 m, and using electric reels and lures instead of bait, reduced bycatch and depredation. The integrated approach used here identified practical methods for reducing fisher-shark conflict, improving socio-economic outcomes for fishers and conservation prospects for this unique shark population.

Dynamics of peripheral T cell exhaustion and monocyte subpopulations in neurocognitive impairment and brain atrophy in chronic HIV infection - Brooks I. Mitchell; Isabelle E. Yazel Eiser; Kalpana J. Kallianpur; Louie Mar Gangcuangco; Dominic C. Chow; Lishomwa C. Ndhlovu; Robert Paul; Cecilia M. Shikuma (Journal of NeuroVirology, 2024)
Background HIV-associated neurocognitive disorders (HAND) is hypothesized to be a result of myeloid cell-induced neuro-inflammation in the central nervous system that may be initiated in the periphery, but the contribution of peripheral T cells in HAND pathogenesis remains poorly understood. Methods We assessed markers of T cell activation (HLA-DR + CD38+), immunosenescence (CD57 + CD28-), and immune-exhaustion (TIM-3, PD-1 and TIGIT) as well as monocyte subsets (classical, intermediate, and non-classical) by flow cytometry in peripheral blood derived from individuals with HIV on long-term stable anti-retroviral therapy (ART). Additionally, normalized neuropsychological (NP) composite test z-scores were obtained and regional brain volumes were assessed by magnetic resonance imaging (MRI). Relationships between proportions of immune phenotypes (of T-cells and monocytes), NP z-scores, and brain volumes were analyzed using Pearson correlations and multiple linear regression models. Results Of N = 51 participants, 84.3% were male, 86.3% had undetectable HIV RNA < 50 copies/ml, median age was 52 [47, 57] years and median CD4 T cell count was 479 [376, 717] cells/uL. Higher CD4 T cells expressing PD-1 + and/or TIM-3 + were associated with lower executive function and working memory and higher CD8 T cells expressing PD-1 + and/or TIM-3 + were associated with reduced brain volumes in multiple regions (putamen, nucleus accumbens, cerebellar cortex, and subcortical gray matter). Furthermore, higher single or dual frequencies of PD-1 + and TIM-3 + expressing CD4 and CD8 T-cells correlated with higher CD16 + monocyte numbers. Conclusions This study reinforces evidence that T cells, particularly those with immune exhaustion phenotypes, are associated with neurocognitive impairment and brain atrophy in people living with HIV on ART. Relationships revealed between T-cell immune exhaustion and inflammatory in CD16 + monocytes uncover interrelated cellular processes likely involved in the immunopathogenesis of HAND.

Inferences based on diatom compositions improve estimates of nutrient concentrations in streams - Lester L. Yuan; Richard M. Mitchell; Erik M. Pilgrim; Nathan J. Smucker (Science of The Total Environment, 2024)

Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Robert H. Heflich; Michelle E. Bishop; Roberta A. Mittelstaedt; Jian Yan; Sharon K. Guerrero; Audrey M. Sims; Kamela Mitchell; Nyosha Moore; Xilin Li; Nan Mei; Rosalie K. Elespuru; Sruthi T. King; et al. (Regulatory Toxicology and Pharmacology, 2024)

The Calorimetric Electron Telescope (CALET) on the International Space Station: Results from the first eight years on orbit - Y. Akaike; O. Adriani; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Direct measurements of cosmic – Ray iron and nickel with CALET on the International Space Station - O. Adriani; Y. Akaike; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Ecotoxicity threshold values for 4-hydroxychlorothalonil, carbendazim, dimethoate and methoxyfenozide in fresh and marine waters: Part 1. Derivation of threshold values - Hannah C. Mitchell; Michael St.J. Warne; Reinier M. Mann; Olivia C. King; Ryan D.R. Turner (Science of The Total Environment, 2024)

Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

The 2019 pumice raft forming eruption of Volcano-F (Volcano 0403–091) and implications for hazards posed by submerged calderas - Isobel A. Yeo; Iona M. McIntosh; Scott E. Bryan; Kenichiro Tani; Matthew Dunbabin; Katherine J. Dobson; Samuel J. Mitchell; Patrick C. Collins; Michael A. Clare; Henrietta Cathey; Isikeli Duwai; Philipp A. Brandl; et al. (Journal of Volcanology and Geothermal Research, 2024)

Fracture growth and damage zone evolution in fault-vein systems determined through scaling relations in alteration halo-bearing hydrothermal veins - Karin Hofer-Apostolidis; José Cembrano; John Browning; Pamela Pérez-Flores; Thomas M. Mitchell; Philip G. Meredith; Flavia Rojas; Tao Xu (Journal of Structural Geology, 2024)

Generation of the First Transgenic Line of the Iconic Coral Reef Fish Amphiprion ocellaris - Gabriel J. Graham; Emma M. Ibanez; Laurie J. Mitchell; Karen E. Weis; Lori T. Raetzman; Fabio Cortesi; Justin S. Rhodes (Marine Biotechnology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Genomic identification of Oryctes rhinoceros nudivirus isolates, a biocontrol agent for coconut rhinoceros beetle - Ela Hiszczynska-Sawicka; Mitchell K. Weston; Aurelie Laugraud; Charles A. Hefer; Jeanne M. E. Jacobs; Sean D. G. Marshall (Archives of Microbiology, 2024)
The coconut rhinoceros beetle ( Oryctes rhinoceros , CRB) is a serious pest of coconut and oil palms. It is native to South and Southeast Asia and was inadvertently introduced to Samoa in 1909. It has invaded many other Pacific countries throughout the last century. Oryctes rhinoceros nudivirus (OrNV), a natural pathogen of CRB in its native range, was successfully introduced as a classical biocontrol agent and has effectively suppressed invasive CRB populations for decades. However, resurgence of CRB has been recorded, with new invasions detected in several Pacific Island Countries and Territories. Additionally, new populations of CRB are emerging in some invaded areas that have a degree of resistance to the virus isolates commonly released for CRB biocontrol. Here, we designed a fast and reliable tool for distinguishing between different OrNV isolates that can help with the selection process to identify effective isolates for management of new CRB invasions. A comparison of 13 gene/gene region sequences within the OrNV genome of 16 OrNV isolates from native and invaded ranges allowed us to identify unique Single Nucleotide Polymorphisms (SNPs). With these SNPs, we developed an assay using multiplex PCR-amplicon-based nanopore sequencing to distinguish between OrNV isolates. We found that as few as four gene fragments were sufficient to identify 15 out of 20 OrNV isolates. This method can be used as a tool to monitor the establishment and distribution of OrNV isolates selected for release as biocontrol agents in CRB-infected areas.

Ecosourcing for resilience in a changing environment - Peter B. Heenan; William G. Lee; Matt S. McGlone; James K. McCarthy; Caroline M. Mitchell; Matthew J. Larcombe; Gary J. Houliston (New Zealand Journal of Botany, 2024)

Not feeling the heat? Effects of dietary protein on satiation and satiety in mice are not due to its impact on body temperature - Jazmin Osorio M; Sharon E. Mitchell; Catherine Hambly; David B. Allison; John R. Speakman (Appetite, 2024)

Life history and early ontogeny determine vertical swimming behaviors in the larvae of Caribbean corals - Benjamin D. Limer; Olivia Payne; Aran Brancato; Molly Mitchell; Caitlyn Abu-Kubie; Joana Figueiredo; Daniel M. Holstein (Journal of Experimental Marine Biology and Ecology, 2024)

Large structural estuaries: Their global distribution and morphology - Mitchell P. Baum; David M. Kennedy; Sarah L. McSweeney (Geomorphology, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

Development and characterisation of a novel complex triple cell culture model of the human alveolar epithelial barrier - Sarah M. Mitchell; Kirsty Meldrum; Joshua W. P. Bateman; Teresa D. Tetley; Shareen H. Doak; Martin J. D. Clift (In vitro models, 2024)
Owing to increased pressure from ethical groups and the public to avoid unnecessary animal testing, the need for new, responsive and biologically relevant in vitro models has surged. Models of the human alveolar epithelium are of particular interest since thorough investigations into air pollution and the effects of inhaled nanoparticles and e-cigarettes are needed. The lung is a crucial organ of interest due to potential exposures to endogenous material during occupational and ambient settings. Here, an in vitro model of the alveolar barrier has been created in preparation for use in the quasi-air liquid interface (qALI) and (aerosol) air–liquid interface (ALI) exposures. The model consists of an alveolar type 1-like cell line (TT1), an alveolar type 2-like cell line (NCI-H441) and a model of (alveolar) macrophages (dTHP-1). The model formulates a complex, multi-cellular system, cultured at the air–liquid interface, that mimics the apical layer of the alveolar epithelial region in the human lung. Characterisation data has shown that both TT1 and NCI-H441 epithelial cells are able to be cultured together in addition to dTHP-1 cells through imaging (morphology), pro-inflammatory response and viability measurements. This dataset also demonstrates evidence of a reasonable barrier created by the cell culture in comparison to negative controls. Furthermore, it shows that while maintaining a low baseline of (pro)-inflammatory mediator expression during normal conditions, the model is highly responsive to inflammatory stimuli. This model is proposed to be suitable for use in toxicology testing of inhaled exogenous agents.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Using DNA metabarcoding to characterize national scale diatom-environment relationships and to develop indicators in streams and rivers of the United States - Nathan J. Smucker; Erik M. Pilgrim; Christopher T. Nietch; Leslie Gains-Germain; Charlie Carpenter; John A. Darling; Lester L. Yuan; Richard M. Mitchell; Amina I. Pollard (Science of The Total Environment, 2024)

Contrasting hydrocarbon reservoirs in the North China Craton in relation to inhomogeneous craton destruction - Caineng Zou; Yong Li; Xiao-Fang He; M. Santosh; Kun Yu; Ross N. Mitchell (Earth-Science Reviews, 2024)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Perceptions of Telehealth-Based Cancer Support Groups at a Rural Community Oncology Program - Bree E. Holtz; Katharine M. Mitchell; Deborah Strand; Kelly Hirko (Journal of Cancer Education, 2024)

Changes in soil N2O emissions and nitrogen use efficiency following long-term soil carbon storage: Evidence from a mesocosm experiment - Lindsey A. Kelley; Zhenglin Zhang; Santiago Tamagno; Mark E. Lundy; Jeffrey P. Mitchell; Amélie C.M. Gaudin; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Network analyses on photographic surveys reveal that invertebrate predators do not structure epibenthos in the deep (~2000m) rocky Powell Basin, Weddell Sea, Antarctica - Tasnuva Ming Khan; Huw J. Griffiths; Rowan J. Whittle; Nile P. Stephenson; Katie M. Delahooke; Autun Purser; Andrea Manica; Emily G. Mitchell (Frontiers in Marine Science, 2024)
Predator-prey interactions in marine ecosystems control population sizes, maintain species richness, and provide intermediate disturbance. Such ecosystem structuring interactions may be rare in Antarctic epibenthic communities, which are unique among marine ecosystems worldwide for their dominance of soft bodied fauna (sponges, soft and hard corals, and echinoderms) and a simultaneous paucity of shell crushing predators (sharks, rays and durophagous decapods). In the shallow benthos, instead of durophagy, important Antarctic predators such as starfish, pycnogonids (sea spiders), nemertean worms, and nudibranchs employ grazing, scavenging, or sucking strategies. Far less is known about deep sea (>1000 m) Antarctic benthic communities due to the challenging nature of polar data collection, so that photographic surveys provide one of the only means of making in situ observations of these deep sea communities. We used seabed photographs of the deep (~2000m) slope of the Powell Basin, northwest Weddell Sea, taken by the Ocean Floor Observation and Bathymetry System on board the RV Polarstern (PS118, April 2019) to investigate the epibenthic community composition, and Bayesian Network Inference (BNI) to determine the ecological network, namely the ecological associations, including potential invertebrate predator-prey relationships between taxa. Photographs show that the rocky substrates of the basin slope support between 10-22 morphotaxa per photo, and highly abundant communities (density between 106 to 553 individuals/m 2 ). BNI results reveal a network of associations between the sessile and mobile suspension and filter feeding organisms and their physical environment. However, associations between invertebrate predators like starfish, and other organisms, were not detected in the network. This lack of inclusion within the network suggests that, despite the presence of these normally important mobile predators, invertebrate predator-prey interactions on the rocky Powell Basin slope do not have the same ecosystem-regulating impact that they do on shallow Antarctic epibenthic communities.

Biological lags and market dynamics in vertically coordinated food supply chains: HPAI impacts on U.S. egg prices - James L. Mitchell; Jada M. Thompson; Trey Malone (Food Policy, 2024)

Water mass influence on spatial and seasonal distributions of diatoms, dinoflagellates and coccolithophores in the western Barents Sea - Qingshan Luan; Elaine Mitchell; Sian F. Henley; Andrew C. M. Orkney; Heather A. Bouman; Judith S. Braun; Alex J. Poulton; Keith Davidson (Polar Biology, 2024)
Arctic phytoplankton are highly sensitive to seawater physical and chemical conditions, especially in the context of rapid climate change and sea ice loss. We studied the spatial and seasonal distributions of diatoms, dinoflagellates and coccolithophores, and clarified their associations with light, temperature and nutrients in the western Barents Sea in late summer 2017, and winter, spring and early summer 2018. Diatoms, composed mainly of Chaetoceros , Fragilariopsis and Thalassiosira , bloomed in spring at the southern border of the marginal ice zone with mean abundance of 1.1 × 10 6 cells L −1 and biomass of 119.5 µg C L −1 , and were observed to follow the retreat of sea ice in the Arctic water to the north at the shelf break near Nansen Basin, contributing to the progression of the summer situation. Dinoflagellates flourished in surface waters south of Svalbard in summer, with maxima of 2.2 × 10 5 cells L −1 and 78.2 µg C L −1 . High abundances and calcite mass of coccolithophores were detected in the southern Barents Sea and southwest of Svalbard in summer, with maxima of 3.3 × 10 5 cells L −1 and 4.7 µg C L −1 . Two distinct phytoplankton assemblages, closely linked with Atlantic water and Arctic water, were geographically separated by the Polar Front in two summers, with a percent similarity below 11.9%, suggesting great influence of the two water masses on large-scale distributions of phytoplankton. Redundancy analysis revealed that temperature was one of the most important factors in shaping the seasonal distributions of diatoms, while irradiance showed positive correlation with dominant dinoflagellates of each season. From the perspectives of phytoplankton composition and carbon biomass, our findings highlight the governing effect of physical seawater conditions on driving seasonal patterns of phytoplankton biogeography, as well as the pivotal role of nutrients in supporting the phytoplankton growing seasons in the western Barents Sea.

Cover crop cultivars and species differ in root traits potentially impacting their selection for ecosystem services - Kong M. Wong; Marcus Griffiths; Amelia Moran; Andrea Johnston; Alexander E. Liu; Mitchell A. Sellers; Christopher N. Topp (Plant and Soil, 2024)
Background and aims Cover crops have the potential to aid in adapting agricultural systems to climate change impacts through their ecosystem services, such as preventing soil erosion, remediating soil structure, and storing carbon belowground. Though roots are integral to these processes, there is a lack of cover crop root trait data. This study aims to characterize rooting behavior of several commercially available cover crops and assess how differences in root system architecture potentially impact their selection for ecosystem services. Methods Twenty-two cover crop cultivars across the grass, legume, and brassica families were grown in O’Fallon, Missouri, USA. Canopy cover was monitored throughout the growing season. Shoot and root biomass samples were collected and analyzed. Results Cereal rye and winter triticale were the most winter hardy cultivars and provided the highest percent canopy cover. Cereal rye and winter triticale also generated the highest amount of shoot and root biomass among treatments but diverged in their root system architectures. Winter triticale forms coarser roots and exhibited deeper rooting, which may be better suited for carbon sequestration. Rapeseed and Siberian kale have favorable C:N ratios for nutrient recycling, but rapeseed may invest more into lateral root formation and have a higher potential to “catch” excess nutrients. Conclusion Selection of cover crops for ecosystem services should account for root system architecture and their suitability for these ecosystem services. Differences in root traits among cultivars within the same family highlight the potential to breed cover crop root system architecture to further enhance ecosystem service efficacy.

Methane flux from transplanted soil monoliths depends on moisture, but not origin - Kendalynn A. Morris; Mitchell Smith; Vanessa L. Bailey; Roberta Bittencourt-Peixoto; Donnie J. Day; Nora Hamovit; Anya M. Hopple; Jaehyun Lee; Kaizad F. Patel; Peter Regier; Stephanie J. Wilson; Stephanie A. Yarwood; et al. (Soil Biology and Biochemistry, 2024)

Life in the PFAS lane: The impact of perfluoroalkyl substances on photosynthesis, cellular exudates, nutrient cycling, and composition of a marine microbial community - Sarah N. Davis; Shaley M. Klumker; Alexis A. Mitchell; Marshall A. Coppage; Jessica M. Labonté; Antonietta Quigg (Science of The Total Environment, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

An investigation of binding interactions of tumor-targeted peptide conjugated polyphenols with the kinase domain of ephrin B4 and B2 receptors - Saige M. Mitchell; Ryan M. Heise; Molly E. Murray; Dominic J. Lambo; Rachel E. Daso; Ipsita A. Banerjee (Molecular Diversity, 2024)

(R)-(+)-γ-Decalactone is Conserved in North America as a Pheromone Component of Osmoderma eremicola (Coleoptera: Scarabaeidae) and a Kairomone of Elater abruptus (Coleoptera: Elateridae) - Geryd L. Steffek; Anna S. Grommes; Lawrence M. Hanks; Robert F. Mitchell (Journal of Chemical Ecology, 2024)

Measuring changes in background dissolved gases to evaluate multi-component gas dissolution: Laboratory experiments and implications for stray gas monitoring - Madeline M. Calvert; Mitchell A. Davidson; Ariel Nunez Garcia; Kevin G. Mumford (Advances in Water Resources, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Evaluating top‐down, bottom‐up, and environmental drivers of pelagic food web dynamics along an estuarine gradient - Tanya L. Rogers; Samuel M. Bashevkin; Christina E. Burdi; Denise D. Colombano; Peter N. Dudley; Brian Mahardja; Lara Mitchell; Sarah Perry; Parsa Saffarinia (Ecology, 2024)
Identification of the key biotic and abiotic drivers within food webs is important for understanding species abundance changes in ecosystems, particularly across ecotones where there may be strong variation in interaction strengths. Using structural equation models (SEMs) and four decades of integrated data from the San Francisco Estuary, we investigated the relative effects of top‐down, bottom‐up, and environmental drivers on multiple trophic levels of the pelagic food web along an estuarine salinity gradient and at both annual and monthly temporal resolutions. We found that interactions varied across the estuarine gradient and that the detectability of different interactions depended on timescale. For example, for zooplankton and estuarine fishes, bottom‐up effects appeared to be stronger in the freshwater upstream regions, while top‐down effects were stronger in the brackish downstream regions. Some relationships (e.g., bottom‐up effects of phytoplankton on zooplankton) were seen primarily at annual timescales, whereas others (e.g., temperature effects) were only observed at monthly timescales. We also found that the net effect of environmental drivers was similar to or greater than bottom‐up and top‐down effects for all food web components. These findings can help identify which trophic levels or environmental factors could be targeted by management actions to have the greatest impact on estuarine forage fishes and the spatial and temporal scale at which responses might be observed. More broadly, this study highlights how environmental gradients can structure community interactions and how long‐term data sets can be leveraged to generate insights across multiple scales.

Textural evidence of fragmentation and densification processes in a fossilised shallow conduit on the flank of Nevados de Chillán Volcanic Complex - Flavia Rojas; John Browning; Hugh Tuffen; José Cembrano; Javier Espinosa-Leal; Holly E. Unwin; Thomas M. Mitchell; Karin Hofer-Apostolidis; Philip G. Meredith (Journal of Volcanology and Geothermal Research, 2024)

Biomonitoring tool for New Zealand peatlands: Testate amoebae and vascular plants as promising bioindicators - Michelle M. McKeown; Olivia R. Burge; Sarah J. Richardson; Jamie R. Wood; Edward A.D. Mitchell; Janet M. Wilmshurst (Journal of Environmental Management, 2024)

The potential to manage releases of Bacillus anthracis using bioretention and a high flow media filter: Results of simulated runoff testing with tracer spores Bacillus globigii - Kathryn M. Boening-Ulman; Anne M. Mikelonis; J. Lee Heckman; M. Worth Calfee; Katherine Ratliff; Sungmin Youn; Joseph S. Smith; Caleb E. Mitchell; William F. Hunt; Ryan J. Winston (Journal of Environmental Management, 2024)

Increased incidence of vibriosis in Maryland, U.S.A., 2006–2019 - Michele E. Morgado; Kyle D. Brumfield; Clifford Mitchell; Michelle M. Boyle; Rita R. Colwell; Amy R. Sapkota (Environmental Research, 2024)

Where the leatherbacks roam: movement behavior analyses reveal novel foraging locations along the Northwest Atlantic shelf - Mitchell J. Rider; Larisa Avens; Heather L. Haas; Joshua M. Hatch; Samir H. Patel; Christopher R. Sasso (Frontiers in Marine Science, 2024)
Leatherback sea turtles ( Dermochelys coriacea ) migrate along the east coast of the United States, traversing the South and Mid-Atlantic Bights (SAB and MAB) while traveling to and from well-known northern foraging areas off Southern New England (SNE) and Nova Scotia. However, there is limited information on leatherback movement behavior in these regions. To identify leatherback movement patterns, we fit hidden Markov models (HMMs) to satellite transmitter data from 52 leatherbacks tagged between 2017 and 2022 off the coasts of Massachusetts and North Carolina to estimate locations of area restricted searching (ARS) and transient behaviors. Depth-temperature profiles were then paired to locations associated with ARS behavior to understand the vertical use of the water column. We observed leatherbacks displaying ARS behavior in SNE as expected, but also in the MAB and SAB. The HMM results indicated that leatherbacks were primarily foraging in SNE between Nantucket and Long Island Sound and depth-temperature plots from ARS behavior on Nantucket Shoals implied turtles foraging throughout the entire water column. In the MAB, ARS behavior was concentrated between Cape Hatteras, North Carolina, and the mouth of Delaware Bay during the summer. Turtles were closely associated with a well-defined thermocline, but still appeared to dive to deeper cooler waters, which may be a sign of thermoregulatory behavior. There was evidence of foraging in the SAB along the coast as well as along the continental shelf edge. The ARS behavior we documented within the MAB and SAB is the first published empirical evidence that both areas may be important foraging grounds. Our results lay a path for future research to understand how leatherbacks use these areas and the potential anthropogenic threats encountered while moving through these regions.

Photochemical reactivity of water-soluble dissolved organic matter from microplastics and microfibers - Mitchell M. Schutte; Shimaa M. Kteeba; Laodong Guo (Science of The Total Environment, 2024)

Leaf yield and mineral content of mizuna in response to cut-and-come-again harvest, substrate particle size, and fertilizer formulation in a simulated spaceflight environment - Asmaa H. Morsi; Gioia D. Massa; Robert C. Morrow; Raymond M. Wheeler; Mokhles A. Elsysy; Cary A. Mitchell (Life Sciences in Space Research, 2024)

DNA, RNA, and prokaryote community sample stability at different ultra-low temperature storage conditions - Lotta A. I. Landor; Thomas Stevenson; Kyle M. J. Mayers; Mitchell S. Fleming; Sven Le Moine Bauer; Hannah R. Babel; Stefan Thiele (Environmental Sustainability, 2024)
Long-term storage of extracted DNA, RNA, and samples for DNA and RNA extractions is usually done in ultra-low temperature freezers using the standard temperature of −80°C. While this standard was based on the maximum capacity of early generation ultra-low temperature freezers, this paradigm is challenged and initiatives support a switch to −70°C to save energy, reduce heat production, and increase the life expectancy of the freezers. The question arising from these initiatives regards the safety of the samples. Especially in complex biological samples, such as sediments, changes in long-term storage temperature have not been studied in detail. Here, we show that the concentration of extracted nucleic acids and nucleic acids in tissue or cells stored at both temperatures does not differ significantly from each other. The only significant differences found were explained by the variability within the samples over time but not between different temperatures or by dilution factor. In addition, we show that prokaryote community composition in sediment and DNA samples also remain stable at both temperatures. Only two treatments were significantly different in temperature, indicating that for RNA, storage at −70°C might be preferable. Consequently, we recommend storing samples for nucleic acid work at −70°C to reduce energy consumption and support more sustainable lab practices.

Genotypic variation, phylogeography, unified species concept, and the ‘grey zone’ of taxonomic uncertainty in kānuka: recognition of Kunzea ericoides (A.Rich.) Joy Thomps. sens. lat. (Myrtaceae) - Peter B. Heenan; Matt S. McGlone; Caroline M. Mitchell; James K. McCarthy; Gary J. Houliston (New Zealand Journal of Botany, 2024)

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Correction to: Immunoinformatic Risk Assessment of Host Cell Proteins During Process Development for Biologic Therapeutics - Kirk Haltaufderhyde; Brian J. Roberts; Sundos Khan; Frances Terry; Christine M. Boyle; Mitchell McAllister; William Martin; Amy Rosenberg; Anne S. De Groot (The AAPS Journal, 2023)

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Correction to: Changes in school feeding operations during the COVID‑19 pandemic: evidence from 139 countries - Elisabetta M. Ferrero; Ayala Wineman; Arlene Mitchell (Food Security, 2023)

Changes in school feeding operations during the COVID-19 pandemic: evidence from 139 countries - Elisabetta M. Ferrero; Ayala Wineman; Arlene Mitchell (Food Security, 2023)
School meal programs, which provide students with meals, snacks, or take-home rations and serve as a safety net for vulnerable children worldwide, were severely disrupted by the COVID-19 pandemic. This study draws on the 2021 Global Survey of School Meal Programs to explore changes in school feeding operations during the COVID-19 pandemic and identify factors that can facilitate program resilience. The survey, inclusive of both closed and open-ended questions, gathered data on 183 programs operating in 139 countries. Findings suggest that, even though school meal programs were negatively affected by the pandemic and associated school closures, they responded with creativity, employing new feeding modalities, venues of distribution, and approaches to targeting. Regression results further show that involvement of nutritionists was associated with continuity (a lack of interruption) of feeding services. Flexibility and preparedness were highlighted as factors that strengthened programs in a time of crisis. At the same time, the experience of emergencies that occur simultaneously or in quick succession (“stacked” emergencies) hampered their ability to operate. Survey results confirm that attention must be given to school meal programs in low-income settings, as school feeding coverage is lowest in such settings, these programs often have limited resources, and they are more likely to experience stacked emergencies.

Utilising geochemical data for the identification and characterisation of mineral exploration sample media within cover sequence materials - C. J. Tiddy; S. M. Hill; D. Giles; B. G. van der Hoek; V. J. Normington; R. R. Anand; E. Baudet; K. Custance; R. Hill; A. Johnson; S. McLennan; C. Mitchell; et al. (Australian Journal of Earth Sciences, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Prediction of the Renal Organic Anion Transporter 1 (OAT1)- Mediated Drug Interactions for LY404039, the Active Metabolite of Pomaglumetad Methionil - Y. Anne Pak; Maria M. Posada; James Bacon; Amanda Long; William Annes; Jennifer Witcher; Malcolm Mitchell; Rommel G. Tirona; Stephen D. Hall; Kathleen M. Hillgren (Pharmaceutical Research, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

What data are needed to detect wildfire effects on coastal ecosystems? A case study during the Thomas Fire - Sasha J. Kramer; Kelsey M. Bisson; Catherine Mitchell (Frontiers in Marine Science, 2023)
Wildfires are growing in frequency and severity worldwide, with anthropogenic climate change predicted to worsen the effects of wildfires in the future. While most wildfire impacts occur on land, coastal fires can also affect the ocean via smoke production and ash deposition. The impacts of wildfires on marine ecology and biogeochemistry have been studied infrequently, as it is difficult to conduct fieldwork rapidly and safely during unpredictable natural disasters. Increasingly, remote sensing measurements are used to study the impacts of wildfires on marine ecosystems through optical proxies. Given the optical impacts of smoke and in-water ash, these measurements may be limited in their scope and accuracy. Here, we evaluate the potential and limitations of remote sensing data collected from MODIS-Aqua to describe the effects of wildfires on optics and phytoplankton observations. Using samples collected in the Santa Barbara Channel (California, USA) during the Thomas Fire in December 2017, we found that MODIS-Aqua data were unsuited for interpreting ecosystem effects during a wildfire. Our results identified a persistent overestimation of chlorophyll- a concentration from MODIS-Aqua compared to in situ measurements. Optical models applied to in situ radiometry data overestimated the absorption by colored dissolved organic matter (CDOM) during the wildfire. Satellites will remain an important tool to measure the impacts of wildfires on marine ecosystems, but this analysis demonstrates the importance of in situ sampling to quantify the impacts of wildfires on ocean ecology and biogeochemistry due to the difficulty of interpreting remote sensing data during these events.

Laboratory Performance Testing of Aqueous Nasal Inhalation Products for Droplet/Particle Size Distribution: an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - William H. Doub; Julie M. Suman; Mark Copley; Adrian P. Goodey; Sana Hosseini; Jolyon P. Mitchell (AAPS PharmSciTech, 2023)
Although nasal inhalation products are becoming more and more important for the delivery of medicines, characterization of these products for quality control and assessment of bioequivalence is complicated. Most of the problems encountered are associated with the assessment of aerodynamic droplet/particle size distribution (APSD). The droplets produced by the various nasal devices are large, and for suspension products, individual droplets may contain multiple drug particles or none at all. Assessment of suspension products is further complicated by the presence of solid excipient particles. These complications make it imperative that the limitations of the instruments used for characterization as well as the underlying assumptions that govern the interpretation of data produced by these instruments are understood. In this paper, we describe various methodologies used to assess APSD for nasal inhalation products and discuss proper use, limitations, and new methodologies on the horizon.

Parascaris spp. eggs shedding patterns in juvenile horses - Nichol E. Ripley; Holli S. Gravatte; Leah N. Britton; Sarah M. Davis; Grace M. Perrin; Shaelin Mitchell; Elizabeth K. Rexroat; Abigail L. Vetter; Emily E.S. Maron; Constance A. Finnerty; Victoria Stanton; Martin K. Nielsen (Veterinary Parasitology, 2023)

Interactions between parasitism and migration in monarch butterflies - Mitchell J Kendzel; Sonia M Altizer; Jacobus C de Roode (Current Opinion in Insect Science, 2023)

Towards hyperlocal source identification of pollutants in cities by combining mobile measurements with atmospheric modeling - John C. Lin; Ben Fasoli; Logan Mitchell; Ryan Bares; Francesca Hopkins; Tammy M. Thompson; Ramón A. Alvarez (Atmospheric Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Convergent evolution of skim feeding in baleen whales - Ludovic Dutoit; Kieren J. Mitchell; Nicolas Dussex; Catherine M. Kemper; Petter Larsson; Love Dalén; Nicolas J. Rawlence; Felix G. Marx (Marine Mammal Science, 2023)

Optimal heat stress metric for modelling heat‐related mortality varies from country to country - Y. T. Eunice Lo; Dann M. Mitchell; Jonathan R. Buzan; Jakob Zscheischler; Rochelle Schneider; Malcolm N. Mistry; Jan Kyselý; Éric Lavigne; Susana Pereira da Silva; Dominic Royé; Aleš Urban; Ben Armstrong; et al. (International Journal of Climatology, 2023)
Combined heat and humidity is frequently described as the main driver of human heat‐related mortality, more so than dry‐bulb temperature alone. While based on physiological thinking, this assumption has not been robustly supported by epidemiological evidence. By performing the first systematic comparison of eight heat stress metrics (i.e., temperature combined with humidity and other climate variables) with warm‐season mortality, in 604 locations over 39 countries, we find that the optimal metric for modelling mortality varies from country to country. Temperature metrics with no or little humidity modification associates best with mortality in ~40% of the studied countries. Apparent temperature (combined temperature, humidity and wind speed) dominates in another 40% of countries. There is no obvious climate grouping in these results. We recommend, where possible, that researchers use the optimal metric for each country. However, dry‐bulb temperature performs similarly to humidity‐based heat stress metrics in estimating heat‐related mortality in present‐day climate.

Functional network disorganization and cognitive decline following fractionated whole-brain radiation in mice - Benjamin A. Seitzman; Francisco J. Reynoso; Timothy J. Mitchell; Annie R. Bice; Anmol Jarang; Xiaodan Wang; Cedric Mpoy; Lori Strong; Buck E. Rogers; Carla M. Yuede; Joshua B. Rubin; Stephanie M. Perkins; et al. (GeroScience, 2023)
Cognitive dysfunction following radiotherapy (RT) is one of the most common complications associated with RT delivered to the brain, but the precise mechanisms behind this dysfunction are not well understood, and to date, there are no preventative measures or effective treatments. To improve patient outcomes, a better understanding of the effects of radiation on the brain’s functional systems is required. Functional magnetic resonance imaging (fMRI) has shown promise in this regard, however, compared to neural activity, hemodynamic measures of brain function are slow and indirect. Understanding how RT acutely and chronically affects functional brain organization requires more direct examination of temporally evolving neural dynamics as they relate to cerebral hemodynamics for bridging with human studies. In order to adequately study the underlying mechanisms of RT-induced cognitive dysfunction, the development of clinically mimetic RT protocols in animal models is needed. To address these challenges, we developed a fractionated whole-brain RT protocol (3Gy/day for 10 days) and applied longitudinal wide field optical imaging (WFOI) of neural and hemodynamic brain activity at 1, 2, and 3 months post RT. At each time point, mice were subject to repeated behavioral testing across a variety of sensorimotor and cognitive domains. Disruptions in cortical neuronal and hemodynamic activity observed 1 month post RT were significantly worsened by 3 months. While broad changes were observed in functional brain organization post RT, brain regions most impacted by RT occurred within those overlapping with the mouse default mode network and other association areas similar to prior reports in human subjects. Further, significant cognitive deficits were observed following tests of novel object investigation and responses to auditory and contextual cues after fear conditioning. Our results fill a much-needed gap in understanding the effects of whole-brain RT on systems level brain organization and how RT affects neuronal versus hemodynamic signaling in the cortex. Having established a clinically-relevant injury model, future studies can examine therapeutic interventions designed to reduce neuroinflammation-based injury following RT. Given the overlap of sequelae that occur following RT with and without chemotherapy, these tools can also be easily incorporated to examine chemotherapy-related cognitive impairment.

Immunoinformatic Risk Assessment of Host Cell Proteins During Process Development for Biologic Therapeutics - Kirk Haltaufderhyde; Brian J. Roberts; Sundos Khan; Frances Terry; Christine M. Boyle; Mitchell McAllister; William Martin; Amy Rosenberg; Anne S. De Groot (The AAPS Journal, 2023)
The identification and removal of host cell proteins (HCPs) from biologic products is a critical step in drug development. Despite recent improvements to purification processes, biologics such as monoclonal antibodies, enzyme replacement therapies, and vaccines that are manufactured in a range of cell lines and purified using diverse processes may contain HCP impurities, making it necessary for developers to identify and quantify impurities during process development for each drug product. HCPs that contain sequences that are less conserved with human homologs may be more immunogenic than those that are more conserved. We have developed a computational tool, ISPRI-HCP, that estimates the immunogenic potential of HCP sequences by evaluating and quantifying T cell epitope density and relative conservation with similar T cell epitopes in the human proteome. Here we describe several case studies that support the use of this method for classifying candidate HCP impurities according to their immunogenicity risk. Graphical Abstract

Exploring Connections Between Perceived and Actual Nutrition Risk Among Low-income, Uninsured Patients, and Their Healthcare Providers - J. Gnau; B. Bowers; J. Willis; K. Maben; S. Mitchell Urich; M. Kurth (Journal of the Academy of Nutrition and Dietetics, 2023)

A complex interplay among agricultural land uses, urbanization, and landscape attributes shapes the concentration-discharge relationships in Ontario, Canada - M. Georgina Kaltenecker; Carl P.J. Mitchell; E. Todd Howell; George Arhonditsis (Journal of Hydrology, 2023)

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Food web structure and energy flux dynamics, but not taxonomic richness, influence microbial ecosystem functions in a Sphagnum-dominated peatland - Vincent E.J. Jassey; Owen L. Petchey; Philippe Binet; Alexandre Buttler; Geneviève Chiapusio; Frédéric Delarue; Fatima Laggoun-Défarge; Daniel Gilbert; Edward A.D. Mitchell; Janna M. Barel (European Journal of Soil Biology, 2023)

A Microplane-Based Anisotropic Damage Model for Deformation and Fracturing of Brittle Rocks - Yang Yuan; Tao Xu; Philip G. Meredith; Thomas M. Mitchell; Michael J. Heap; Guanglei Zhou; Ashley Stanton-Yonge Sesnic (Rock Mechanics and Rock Engineering, 2023)

Rapid changes in functional trait expression and decomposition following high severity fire and experimental warming - Ethan M. Taber; Rachel M. Mitchell (Forest Ecology and Management, 2023)

Characterization of Divergent Metabolic Pathways in Elucidating an Unexpected, Slow-Forming, and Long Half-Life Major Metabolite of Iclepertin - Tom S. Chan; Alexander J. Byer-Alcorace; Bachir Latli; Pingrong Liu; Hlaing H. Maw; Klairynne G. Raymond; Young-Sun Scaringella; Aaron M. Teitelbaum; Ting Wang; Andrea Whitcher-Johnstone; Mitchell E. Taub (Pharmaceutical Research, 2023)

Artisanal gold mining in Kakamega and Vihiga counties, Kenya: potential human exposure and health risk - Maureene Auma Ondayo; Michael J. Watts; Elliott M. Hamilton; Clive Mitchell; Joseph Mankelow; Odipo Osano (Environmental Geochemistry and Health, 2023)
Artisanal and small-scale gold mining (ASGM) represents 20% of gold supply and 90% of gold mining workforce globally, which operates in highly informal setups. Pollutants from mined ores and chemicals introduced during gold processing pose occupational and inadvertent health risks to the extent that has not been well elucidated in Africa. Trace and major elements were analysed using inductively coupled plasma mass spectrometry in soil, sediment and water samples from 19 ASGM villages in Kakamega and Vihiga counties. Associated health risks for residents and ASGM workers were assessed. This paper focuses on As, Cd, Cr, Hg, Ni and Pb for which 96% of soil samples from mining and ore processing sites had As concentrations up to 7937 times higher than the US EPA 12 mg kg −1 standard for residential soils. Soil Cr, Hg and Ni concentrations in 98%, 49% and 68% of the samples exceeded respective USEPA and CCME standards, with 1–72% bioaccessibility. Twenty-five percentage of community drinking water sources were higher than the WHO 10 µg L −1 drinking water guideline. Pollution indices indicated significant enrichment and pollution of soils, sediment and water in decreasing order of As > Cr > Hg > Ni > Pb > Cd. The study revealed increased risks of non-cancer health effects (98.6) and cancer in adults (4.93 × 10 −2 ) and children (1.75 × 10 −1 ). The findings will help environment managers and public health authorities better understand the potential health risks in ASGM and support evidence-based interventions in ASGM processes, industrial hygiene and formulation of public health policy to protect residents and ASGM workers’ health in Kenya.

Neisseria montereyensis sp. nov., Isolated from Oropharynx of California Sea Lion (Zalophus californianus): Genomic, Phylogenetic, and Phenotypic Study - Dmitriy V. Volokhov; Tatiana A. Zagorodnyaya; Vyacheslav A. Furtak; Geetha Nattanmai; Linnell Randall; Sherly Jose; Yamei Gao; Frances M. Gulland; Tobias Eisenberg; Pierluigi Delmonte; Jochen Blom; Kara K. Mitchell (Current Microbiology, 2023)

Evolution of immunogenetic components encoding ultralong CDR H3 - Jeannine A. Ott; Christian Mitchell; Morgan Sheppard; Thad C. Deiss; J. M. Cody Horton; Jeremy K. Haakenson; Ruiqi Huang; Abigail R. Kelley; Brian W. Davis; James N. Derr; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Solar wind driven influences on the Martian oxygen corona: Constraints on atmospheric sputtering from a synthesis of MAVEN measurements during solar minimum - Robin Ramstad; David A. Brain; Yaxue Dong; Jasper S. Halekas; James M. McFadden; David L. Mitchell; Jared Espley; Francis G. Eparvier; Bruce M. Jakosky (Icarus, 2023)

A pair of cadmium-exposed zebrafish affect social behavior of the un-exposed majority - Delia S. Shelton; Zoe M. Dinges; Anuj Khemka; Delawrence J. Sykes; Piyumika S. Suriyampola; Dolores E.P. Shelton; Ploypenmas Boyd; Jeffrey R. Kelly; Myra Bower; Halima Amro; Stephen P. Glaholt; Mitchell B. Latta; et al. (Environmental Toxicology and Pharmacology, 2023)

Shear design of RC members strengthened with steel reinforcing bars embedded through section - M. Fiset; J. Bastien; D. Mitchell (Engineering Structures, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

The verification of wildland–urban interface fire evacuation models - E. Ronchi; J. Wahlqvist; A. Ardinge; A. Rohaert; S. M. V. Gwynne; G. Rein; H. Mitchell; N. Kalogeropoulos; M. Kinateder; N. Bénichou; E. Kuligowski; A. Kimball (Natural Hazards, 2023)
This paper introduces a protocol for the verification of multi-physics wildfire evacuation models, including a set of tests used to ensure that the conceptual modelling representation of each modelling layer is accurately implemented, as well as the interactions between different modelling layers and sub-models (wildfire spread, pedestrian movement, traffic evacuation, and trigger buffers). This work presents a total of 24 verification tests, including (1) 4 tests related to pedestrians, (2) 15 tests for traffic evacuation, (3) 5 tests concerning the interaction between different modelling layers, along with 5 tests for wildfire spread and trigger buffers. The evacuation tests are organized in accordance with different core components related to evacuation modelling, namely Population, Pre-evacuation, Movement, Route/destination selection, Flow constraints, Events, Wildfire spread and Trigger buffers. A reporting template has also been developed to facilitate the application of the verification testing protocol. An example application of the testing protocol has been performed using an open wildfire evacuation modelling platform called WUI-NITY and its associated trigger buffer model k-PERIL. The verification testing protocol is deemed to improve the credibility of wildfire evacuation model results and stimulate future modelling efforts in this domain.

91 Horse owners’ perspectives of horse weight management - M. Ross; K. Proudfoot; K. Merkies; M. Mills; I. Elsohaby; J. Mitchell; K. MacMillan; S. McKenna; C. Ritter (Journal of Equine Veterinary Science, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Oral formulation of Wnt inhibitor complex reduces inflammation and fibrosis in intraperitoneal implants in vivo - Ana Luíza de Castro Santos; Natália Jordana Alves da Silva; Celso Tarso Rodrigues Viana; Letícia Cristine Cardoso dos Santos; Gabriel Henrique Costa da Silva; Sérgio Ricardo Aluotto Scalzo Júnior; Pedro Augusto Carvalho Costa; Walison Nunes da Silva; Itamar Couto Guedes de Jesus; Alexander Birbrair; Mariana T. Q. de Magalhães; Frédéric Frézard; et al. (Drug Delivery and Translational Research, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Processing of micro-CT images of granodiorite rock samples using convolutional neural networks (CNN). Part III: Enhancement of Scanco micro-CT images of granodiorite rocks using a 3D convolutional neural network super-resolution algorithm - A. Roslin; M. Lebedev; T.R. Mitchell; I.A. Onederra; C.R. Leonardi (Minerals Engineering, 2023)

Processing of micro-CT images of granodiorite rock samples using convolutional neural networks (CNN), Part II: Semantic segmentation using a 2.5D CNN - A. Roslin; M. Marsh; B. Provencher; T.R. Mitchell; I.A. Onederra; C.R. Leonardi (Minerals Engineering, 2023)

Remote sensing algorithms for particulate inorganic carbon (PIC) and the global cycle of PIC - William M. Balch; Catherine Mitchell (Earth-Science Reviews, 2023)

Experimental and Numerical Investigation into the Fracture Patterns Induced by Blast-Loading Under Unconfined and Confined Conditions - T. R. Mitchell; Z. Wang; M. Araos; C. R. Leonardi; P. R. Gefken; I. A. Onederra (Rock Mechanics and Rock Engineering, 2023)

Effects of climate on fall migration phenology of monarch butterflies departing the northeastern breeding grounds in Canada - Danielle M. Ethier; Greg W. Mitchell (Global Change Biology, 2023)
Monarch butterflies ( Danaus plexippus ) undergo an iconic multi‐generational migration, traveling thousands of kilometers from the summer breeding grounds in southern Canada to overwintering sites in central Mexico. This migration phenomena can be affected by climate change, which may have important implications on fitness and ultimately populations status. We investigated the long‐term trends in fall migration phenology of monarchs using a 25‐year dataset collected along the coast of Lake Erie in Ontario, Canada. We also investigated local long‐term trends in weather covariates that have the potential to influence migration phenology at this site. Patterns in standardized daily counts of monarchs were compared with local weather covariates using two methods (i.e., monthly averages and moving windows) to assess difference in outputs between analytical approaches. Our results suggest that monarch migration timing (migration midpoint, average peak, first peak, and late passage) and weather covariates have been consistent over time, in direct contrast to a similar study in Cape May, New Jersey, which showed a significant increase in both fall temperature and a 16‐ to 19‐day shift in monarch migration timing. Furthermore, our results differed between analytical approaches. With respect to annual variability in air temperature, our monthly average analysis suggested that for each degree increase in September air temperature, late season passage would advance 4.71 days (±1.59 SE, p = .01). However, the moving window analysis suggested that this result is likely spurious and found no significant correlations between migration timing and any weather covariates. Importantly, our results caution against extrapolating the effects of climate change on the migration phenology of the monarch across study regions and the need for more long‐term monitoring efforts to better understand regional drivers of variability in migration timing.

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Methyl methacrylate thermal decomposition: Modeling and laser spectroscopy of species time-histories behind reflected shock waves - Isabelle C. Sanders; Nicholas M. Kuenning; Nicolas Q. Minesi; Daniel I. Pineda; R. Mitchell Spearrin (Fuel, 2023)

Fur removal promotes an earlier expression of involution-related genes in mammary gland of lactating mice - Elżbieta Król; Frances Turner; Davina Derous; Sharon E. Mitchell; Samuel A. M. Martin; Alex Douglas; John R. Speakman (Journal of Comparative Physiology B, 2023)
Peak lactation occurs when milk production is at its highest. The factors limiting peak lactation performance have been subject of intense debate. Milk production at peak lactation appears limited by the capacity of lactating females to dissipate body heat generated as a by-product of processing food and producing milk. As a result, manipulations that enhance capacity to dissipate body heat (such as fur removal) increase peak milk production. We investigated the potential correlates of shaving-induced increases in peak milk production in laboratory mice. By transcriptomic profiling of the mammary gland, we searched for the mechanisms underlying experimentally increased milk production and its consequences for mother–young conflict over weaning, manifested by advanced or delayed involution of mammary gland. We demonstrated that shaving-induced increases in milk production were paradoxically linked to reduced expression of some milk synthesis-related genes. Moreover, the mammary glands of shaved mice had a gene expression profile indicative of earlier involution relative to unshaved mice. Once provided with enhanced capacity to dissipate body heat, shaved mice were likely to rear their young to independence faster than unshaved mothers.

Controlled air exchange rate method to evaluate reduction of volatile organic compounds by indoor air cleaners - Maneeshin Y. Rajapakse; Theresa E. Pistochini; Eva Borras; Mitchell M. McCartney; Cristina E. Davis (Chemosphere, 2023)

An age-depth model and revised stratigraphy of vertebrate-bearing units in Natural Trap Cave, Wyoming - David M. Lovelace; Cory M. Redman; Thomas A. Minckley; Blaine W. Schubert; Shannon Mahan; John R. Wood; Jenny L. McGuire; Juan Laden; Kathleen Bitterman; Holly Heiniger; Lindsey Fenderson; Alan Cooper; et al. (Quaternary International, 2023)

Time-dependent cracking and brittle creep in macrofractured sandstone - Yanchao Xue; Tao Xu; Michael J. Heap; Philip G. Meredith; Thomas M. Mitchell; P.L.P. Wasantha (International Journal of Rock Mechanics and Mining Sciences, 2023)

Dhurrin stability and hydrogen cyanide release in dried sorghum samples - Shelby M. Gruss; Keith D. Johnson; Manoj Ghaste; Joshua R. Widhalm; Sandy K. Johnson; Johnathon D. Holman; Augustine Obour; Robert M. Aiken; Mitchell R. Tuinstra (Field Crops Research, 2023)

Monitoring threatened species with environmental DNA and open ecological data: Local distribution and habitat preferences of scalloped hammerhead sharks (Sphyrna lewini) - Alyssa M. Budd; Tom Schils; Madalyn K. Cooper; Mitchell B. Lyons; Matthew S. Mills; Mari E. Deinhart; Agnès Le Port; Roger Huerlimann; Jan M. Strugnell (Biological Conservation, 2023)

Melanism in a Wild Sifaka Population: Darker Where Cold and Fragmented - Elizabeth Tapanes; Jason M. Kamilar; Maanas A. Nukala; Mitchell T. Irwin; Brenda J. Bradley (International Journal of Primatology, 2023)

Genetic diversity of Tradescantia fluminensis complex (Commelinaceae) naturalised in Australia, New Zealand and South Africa - Peter B. Heenan; Dagmar F. Cheeseman; Caroline M. Mitchell; Murray I. Dawson; Lindsay A. Smith; Gary J. Houliston (New Zealand Journal of Botany, 2023)

Efficacy of quick-start nitrifying products in controlled fresh-water aquaria - Alyssa M. Scagnelli; Sirah Javier; Mark Mitchell; Mark Acierno (Journal of Exotic Pet Medicine, 2023)

Reconstruction of magma chamber processes preserved in olivine-phlogopite micro-ijolites from the Oldoinyo Lengai, Tanzania - Noémi Halász; Márta Berkesi; Tivadar M. Tóth; Roger H. Mitchell; Ralf Milke; Tibor Guzmics (Journal of African Earth Sciences, 2023)

Characterisation of P2Y receptor subtypes mediating vasodilation and vasoconstriction of rat pulmonary artery using selective antagonists - Markie O. Dales; Callum Mitchell; Alison M. Gurney; Robert M. Drummond; Charles Kennedy (Purinergic Signalling, 2022)
Pulmonary vascular tone is modulated by nucleotides, but which P2 receptors mediate these actions is largely unclear. The aim of this study, therefore, was to use subtype-selective antagonists to determine the roles of individual P2Y receptor subtypes in nucleotide-evoked pulmonary vasodilation and vasoconstriction. Isometric tension was recorded from rat intrapulmonary artery rings (i.d. 200–500 µm) mounted on a wire myograph. Nucleotides evoked concentration- and endothelium-dependent vasodilation of precontracted tissues, but the concentration–response curves were shallow and did not reach a plateau. The selective P2Y 2 antagonist, AR-C118925XX, inhibited uridine 5′-triphosphate (UTP)- but not adenosine 5′-triphosphate (ATP)-evoked relaxation, whereas the P2Y 6 receptor antagonist, MRS2578, had no effect on UTP but inhibited relaxation elicited by uridine 5′-diphosphate (UDP). ATP-evoked relaxations were unaffected by the P2Y 1 receptor antagonist, MRS2179, which substantially inhibited responses to adenosine 5′-diphosphate (ADP), and by the P2Y 12/13 receptor antagonist, cangrelor, which potentiated responses to ADP. Both agonists were unaffected by CGS1593, an adenosine receptor antagonist. Finally, AR-C118925XX had no effect on vasoconstriction elicited by UTP or ATP at resting tone, although P2Y 2 receptor mRNA was extracted from endothelium-denuded tissues using reverse transcription polymerase chain reaction with specific oligonucleotide primers. In conclusion, UTP elicits pulmonary vasodilation via P2Y 2 receptors, whereas UDP acts at P2Y 6 and ADP at P2Y 1 receptors, respectively. How ATP induces vasodilation is unclear, but it does not involve P2Y 1 , P2Y 2 , P2Y 12 , P2Y 13 , or adenosine receptors. UTP- and ATP-evoked vasoconstriction was not mediated by P2Y 2 receptors. Thus, this study advances our understanding of how nucleotides modulate pulmonary vascular tone.

Innovation in Resident Core Oncology Education: Switching from an Inpatient Ward Rotation to a Hybrid Model of Inpatient Consultations and Outpatient Clinics - Jennifer M. King; Reem Akel; Antoine N. Saliba; Cynthia Wei; Bilal Anouti; Naveen Manchanda; Noelle C. Sinex; Sara Jo Grethlein; Mitchell Goldman (Journal of Cancer Education, 2022)

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

Relating QRS voltages to left ventricular mass and body composition in elite endurance athletes - Ruben De Bosscher; Jonathan Moeyersons; Christophe Dausin; Mathias Claeys; Kristel Janssens; Piet Claus; Kaatje Goetschalckx; Jan Bogaert; Caroline M. Van De Heyning; Bernard Paelinck; Prashanthan Sanders; Jonathan Kalman; et al. (European Journal of Applied Physiology, 2022)

Breeding oat for resistance to the crown rust pathogen Puccinia coronata f. sp. avenae: achievements and prospects - R. F. Park; W. H. P. Boshoff; A. L. Cabral; J. Chong; J. A. Martinelli; M. S. McMullen; J. W. Mitchell Fetch; E. Paczos-Grzęda; E. Prats; J. Roake; S. Sowa; L. Ziems; et al. (Theoretical and Applied Genetics, 2022)
Crown rust, caused by Puccinia coronata f. sp. avenae ( Pca ), is a significant impediment to global oat production. Some 98 alleles at 92 loci conferring resistance to Pca in Avena have been designated; however, allelic relationships and chromosomal locations of many of these are unknown. Long-term monitoring of Pca in Australia, North America and elsewhere has shown that it is highly variable even in the absence of sexual recombination, likely due to large pathogen populations that cycle between wild oat communities and oat crops. Efforts to develop cultivars with genetic resistance to Pca began in the 1950s. Based almost solely on all all-stage resistance, this has had temporary benefits but very limited success. The inability to eradicate wild oats, and their common occurrence in many oat growing regions, means that future strategies to control Pca must be based on the assumption of a large and variable prevailing pathogen population with high evolutionary potential, even if cultivars with durable resistance are deployed and grown widely. The presence of minor gene, additive APR to Pca in hexaploid oat germplasm opens the possibility of pyramiding several such genes to give high levels of resistance. The recent availability of reference genomes for diploid and hexaploid oat will undoubtedly accelerate efforts to discover, characterise and develop high throughput diagnostic markers to introgress and pyramid resistance to Pca in high yielding adapted oat germplasm.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

How Machine Learning is Powering Neuroimaging to Improve Brain Health - Nalini M. Singh; Jordan B. Harrod; Sandya Subramanian; Mitchell Robinson; Ken Chang; Suheyla Cetin-Karayumak; Adrian Vasile Dalca; Simon Eickhoff; Michael Fox; Loraine Franke; Polina Golland; Daniel Haehn; et al. (Neuroinformatics, 2022)
This report presents an overview of how machine learning is rapidly advancing clinical translational imaging in ways that will aid in the early detection, prediction, and treatment of diseases that threaten brain health. Towards this goal, we aresharing the information presented at a symposium, “Neuroimaging Indicators of Brain Structure and Function - Closing the Gap Between Research and Clinical Application”, co-hosted by the McCance Center for Brain Health at Mass General Hospital and the MIT HST Neuroimaging Training Program on February 12, 2021. The symposium focused on the potential for machine learning approaches, applied to increasingly large-scale neuroimaging datasets, to transform healthcare delivery and change the trajectory of brain health by addressing brain care earlier in the lifespan. While not exhaustive, this overview uniquely addresses many of the technical challenges from image formation, to analysis and visualization, to synthesis and incorporation into the clinical workflow. Some of the ethical challenges inherent to this work are also explored, as are some of the regulatory requirements for implementation. We seek to educate, motivate, and inspire graduate students, postdoctoral fellows, and early career investigators to contribute to a future where neuroimaging meaningfully contributes to the maintenance of brain health.

Molecular dynamics simulations, docking and MMGBSA studies of newly designed peptide-conjugated glucosyloxy stilbene derivatives with tumor cell receptors - Mia I. Rico; Charlotta G. Lebedenko; Saige M. Mitchell; Ipsita A. Banerjee (Molecular Diversity, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Microsatellite characterisation of the extinct Sophora toromiro (Fabaceae) and confirmation of the identities of Allan Herbarium specimens and the fabled Christchurch ‘Victoria Park toromiro’ - Peter B. Heenan; Caroline M. Mitchell; Lara D. Shepherd; Gary J. Houliston (New Zealand Journal of Botany, 2022)
We analysed nine microsatellite markers for 260 individuals representing Sophora tomentosa and 15 species from across the geographic range of Sophora sect. Edwardsia . The purpose of the study was to characterise the Sophora species from Pacific Ocean islands and South America and determine their relationships to the eight New Zealand species, with relationships of the extinct Rapa Nui/Easter Island S. toromiro a particular focus. Structure, PCoA and NeighborNet analyses showed S. tomentosa was distinct from species of sect. Edwardsia . Among the species of sect. Edwardsia , S. cassioides , S. howinsula , S. longicarinata , S. prostrata and S. toromiro were genetically distinct as each comprised a high proportion of membership of individuals assigned to them. The remaining species were assigned to four genetic groups, each of which had one species with a high proportion of membership and other species with lower proportions of membership. The S. chrysophylla group also included high proportions of S. macrocarpa , S. denudata and S. raivavaeensis . The S. fulvida , S. godleyi and S. molloyi genetic groups mostly included low proportions of other New Zealand species. In the PCoA, S. toromiro specimens clustered together and were placed at the margin of a large sect. Edwardsia group. Sophora toromiro comprised four specimens representing the Melbourne Botanic Gardens (Australia) genotype and two specimens in the Allan Herbarium (CHR) obtained from cultivated specimens in Valparaíso (Chile) during the early 1970s. One specimen from Valparaíso was originally identified as S. toromiro , while the other was misidentified as Sophora macnabiana (now S. cassioides ). The lack of genetic variation in S. toromiro suggests they were perhaps derived from the last surviving tree on Rapa Nui / Easter Island. A cultivated plant from New Zealand known as the ‘Victoria Park toromiro’ had its identity confirmed as S. godleyi , which is consistent with its morphological identification.

The genetic basis for panicle trait variation in switchgrass (Panicum virgatum) - Li Zhang; Alice MacQueen; Xiaoyu Weng; Kathrine D. Behrman; Jason Bonnette; John L. Reilley; Francis M. Rouquette; Philip A. Fay; Yanqi Wu; Felix B. Fritschi; Robert B. Mitchell; David B. Lowry; et al. (Theoretical and Applied Genetics, 2022)
Key message We investigate the genetic basis of panicle architecture in switchgrass in two mapping populations across a latitudinal gradient, and find many stable, repeatable genetic effects and limited genetic interactions with the environment. Abstract Grass species exhibit large diversity in panicle architecture influenced by genes, the environment, and their interaction. The genetic study of panicle architecture in perennial grasses is limited. In this study, we evaluate the genetic basis of panicle architecture including panicle length, primary branching number, and secondary branching number in an outcrossed switchgrass QTL population grown across ten field sites in the central USA through multi-environment mixed QTL analysis. We also evaluate genetic effects in a diversity panel of switchgrass grown at three of the ten field sites using genome-wide association (GWAS) and multivariate adaptive shrinkage. Furthermore, we search for candidate genes underlying panicle traits in both of these independent mapping populations. Overall, 18 QTL were detected in the QTL mapping population for the three panicle traits, and 146 unlinked genomic regions in the diversity panel affected one or more panicle trait. Twelve of the QTL exhibited consistent effects (i.e., no QTL by environment interactions or no QTL × E), and most (four of six) of the effects with QTL × E exhibited site-specific effects. Most (59.3%) significant partially linked diversity panel SNPs had significant effects in all panicle traits and all field sites and showed pervasive pleiotropy and limited environment interactions. Panicle QTL co-localized with significant SNPs found using GWAS, providing additional power to distinguish between true and false associations in the diversity panel.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Water quality inequality: a non-targeted hotspot analysis for ambient water quality injustices - Justine A. Neville; Jaclyn Guz; Helen M. Rosko; Mitchell C. Owens (Hydrological Sciences Journal, 2022)

Behavior of potentially toxic elements from stoker-boiler fly ash in Interior Alaska: paired batch leaching and solid-phase characterization - Kyle P. Milke; Kiana L. Mitchell; Sarah M. Hayes; Carlin J. Green; Jennifer J. Guerard (Environmental Science and Pollution Research, 2022)
Despite significant investigation of fly ash spills and mineralogical controls on the release of potentially toxic elements (PTEs) from fly ash, interactions with the surficial environment remain relatively poorly understood. We conducted 90-day batch leaching studies with paired analysis of supernatant and solid-phase mineralogy to assess the elemental release and transformation of fly ash upon reaction with aquatic media (18 MΩ cm −1 water and simulated rainwater). The fly ash in this study, collected from the University of Alaska Fairbanks stoker-boiler power plant, is high in unburned carbon (~20% LOI) and highly enriched in several PTEs relative to the upper continental crust. Supernatant concentrations of oxyanion-forming elements (e.g., As, Se, Mo, Sb) remained relatively low and constant, suggesting equilibrium with the solid phase, possibly ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 •26H 2 O], which is known to incorporate and sorb oxyanion-forming PTEs and was identified by X-ray diffraction. Synthetic precipitation leaching procedure (SPLP) results failed to capture important temporal trends. Lead and Ba supernatant concentrations consistently exceeded drinking water standards, as well as others upon exposure to simulated physiological solutions. Seven-day experiments with dissolved organic matter-isolate solutions indicated that for certain elements, liberation was influenced by carbon concentration and/or the identity of the isolate. Overall, this paired approach can serve as a model for future studies, bridging existing gaps between batch leaching and single-element mineralogical, sorption, or speciation studies.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Neotropical Anacardiaceae (cashew family) - John D. Mitchell; Susan K. Pell; Julien B. Bachelier; Emily J. Warschefsky; Elizabeth M. Joyce; Laura Calvillo Canadell; Cíntia Luíza da Silva-Luz; Clement Coiffard (Brazilian Journal of Botany, 2022)
Anacardiaceae is an ecologically and economically important plant family of about 200 species in 32 genera in the Neotropics. The family is particularly diverse in leaf architecture and fruit morphology, making it a model family to study the evolution of structural diversity as it correlates with lineage diversification. This fruit diversity is the primary reason 11 of the Neotropical genera are monotypic and that so many genera are recognized in the Anacardiaceae. The economic value of the family is driven by the global markets for cashews, mangoes, and pistachios, but there is great potential value in its medicinal properties. At least 10 Neotropical genera cause contact dermatitis, which is a rich area for research in the family. Here presented is a review of the systematics and structural diversity of the family. Particular attention is given to the morphology, economic botany, paleobotany, ecology, and taxonomy of native and naturalized genera. Keys to Neotropical Anacardiaceae subfamilies and genera are provided along with descriptions of native genera.

Sexual assault and white matter hyperintensities among midlife women - Rebecca C. Thurston; Karen P. Jakubowski; Minjie Wu; Howard J. Aizenstein; Yuefang Chang; Carol A. Derby; Karestan C. Koenen; Emma Barinas-Mitchell; Pauline M. Maki (Brain Imaging and Behavior, 2022)

Description of two new bird species from the Meratus Mountains of southeast Borneo, Indonesia - Mohammad Irham; Tri Haryoko; Subir B. Shakya; Simon L. Mitchell; Ryan C. Burner; Carlos Bocos; James A. Eaton; Frank E. Rheindt; Suparno Suparno; Frederick H. Sheldon; Dewi M. Prawiradilaga (Journal of Ornithology, 2022)

Methionol, a Sulfur-Containing Pheromone Component from the North American Cerambycid Beetle Knulliana cincta cincta - Marlin E. Rice; Lawrence M. Hanks; Sean Halloran; Judith A. Mongold-Diers; Anna C. Grommes; Robert F. Mitchell; Ann M. Ray; Jocelyn G. Millar (Journal of Chemical Ecology, 2022)

Drivers of fine‐scale diurnal space use by a coral‐reef mesopredatory fish - Alastair R. Harborne; David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Drew W. Butkowski; Manuel González‐Rivero (Journal of Fish Biology, 2022)
The habitat preferences of many reef fishes are well established, but the use of space within these habitats by non‐site‐attached species is poorly studied. The authors examined the space use of a functionally important mesopredator, graysby ( Cephalopholis cruentata ), on six patch reefs in the Florida Keys. A 1 m 2 ‐scale grid was constructed on each reef and 16 individual C. cruentata were tracked diurnally in situ to identify space use. At the patch reef scale, larger C. cruentata were more active and had larger observed home ranges, although home ranges were also affected by fish density and the abundances of prey and predators. The total time in each 1 m 2 grid cell was regressed against a range of fine‐scale biotic variables, including multiple variables derived from structure‐from‐motion three‐dimensional digital reconstructions of each reef. Nonetheless, time in grid cells (preferred microhabitats) was only significantly positively correlated with the height of carbonate structures, likely because the cavities they enclose are particularly suitable for predator avoidance, resting and ambushing prey. The ongoing flattening of reefs in the region caused by negative carbonate budgets is thus likely to have significant effects on the abundance and space use of C. cruentata . In addition to examining spatial patterns, we analysed C. cruentata waiting times in each grid cell before moving. These times were best approximated by a truncated power‐law (heavy‐tailed) distribution, indicating a “bursty” pattern of relatively long periods of inactivity interspersed with multiple periods of activity. Such a pattern has previously been identified in a range of temperate ambush predators, and the authors extend this move‐wait behaviour, which may optimize foraging success, to a reef fish for the first time. Understanding how C. cruentata uses space and time is critical to fully identify their functional role and better predict the implications of fishing and loss of reef structure.

Seedling growth and fall armyworm feeding preference influenced by dhurrin production in sorghum - Shelby M. Gruss; Manoj Ghaste; Joshua R. Widhalm; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2022)
Cyanogenic glucosides (CGs) play a key role in host-plant defense to insect feeding; however, the metabolic tradeoffs between synthesis of CGs and plant growth are not well understood. In this study, genetic mutants coupled with nondestructive phenotyping techniques were used to study the impact of the CG dhurrin on fall armyworm [ Spodoptera frugiperda (J.E. Smith)] (FAW) feeding and plant growth in sorghum [ Sorghum bicolor (L.) Moench]. A genetic mutation in CYP79A1 gene that disrupts dhurrin biosynthesis was used to develop sets of near-isogenic lines (NILs) with contrasting dhurrin contents in the Tx623 bmr6 genetic background. The NILs were evaluated for differences in plant growth and FAW feeding damage in replicated greenhouse and field trials. Greenhouse studies showed that dhurrin-free Tx623 bmr6 cyp79a1 plants grew more quickly than wild-type plants but were more susceptible to insect feeding based on changes in green plant area (GPA), total leaf area, and total dry weight over time. The NILs exhibited similar patterns of growth in field trials with significant differences in leaf area and dry weight of dhurrin-free plants between the infested and non-infested treatments. Taken together, these studies reveal a significant metabolic tradeoff between CG biosynthesis and plant growth in sorghum seedlings. Disruption of dhurrin biosynthesis produces plants with higher growth rates than wild-type plants but these plants have greater susceptibility to FAW feeding.

Mesenchymal Stromal Cell‐derived Extracellular Vesicles in Preclinical Animal Models of Tumor Growth: Systematic Review and Meta‐analysis - Adrian J.M. Bailey; Alvin Tieu; Manika Gupta; Mitchell Slobodian; Risa Shorr; Tim Ramsay; Rosendo A. Rodriguez; Dean A. Fergusson; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2022)

Genetic variation reveals broad‐scale biogeographic patterns and challenges species’ classification in the Kunzea ericoides (kānuka; Myrtaceae) complex from New Zealand - Peter B. Heenan; Matt S. McGlone; Caroline M. Mitchell; Dagmar F. Cheeseman; Gary J. Houliston (New Zealand Journal of Botany, 2022)
Kunzea (kānuka) in New Zealand comprises ten endemic species following a recent taxonomic revision, several of which are abundant, widespread and ecologically important as early successional colonisers. The species are difficult to recognise in the field in many areas, some plants appear intermediate between species and it has been argued hybrids are common. Microsatellite markers are used to investigate genetic variation in these ten species. The species are only weakly supported as they are characterised by low differentiation as reported by F ST and high allele migration (Nm). F ST varied between 0.027 ( K. robusta ) and 0.084 ( K. triregensis ). The allopatric K. triregensis and K. salterae had the highest difference in pairwise F ST at 0.155 and the sympatric K. robusta and K. serotina the lowest at 0.005. Allele pairwise net migration (Nm) varied between 1.36 ( K. triregensis and K. salterae ) and 45.24 ( K. robusta and K. serotina ). The two most widespread species, K. robusta and K. serotina , are genetically indistinguishable and share northern and southern genotypic clusters. Six species or groups of species are recognised in the Structure analysis but these too are characterised by low F ST and high allele migration (Nm). Four genotypic clusters shown by Structure analysis are distributed along a north to south latitudinal gradient cutting across species boundaries and corresponding with established biogeographic regions of New Zealand. This provides the strongest pattern of genotypic variation in the study. The weak level of genetic support for the ten Kunzea species, lack of breeding barriers between them, and problems in recognising some of the species in the field, raises questions as to their validity. However, given the ecological, conservation and economic importance of Kunzea , the ten species currently circumscribed should be retained until decisions are made as to how to recognise the variation within the species complex.

Ocean warming alters the distributional range, migratory timing, and spatial protections of an apex predator, the tiger shark ( Galeocerdo cuvier ) - Neil Hammerschlag; Laura H. McDonnell; Mitchell J. Rider; Garrett M. Street; Elliott L. Hazen; Lisa J. Natanson; Camilla T. McCandless; Melanie R. Boudreau; Austin J. Gallagher; Malin L. Pinsky; Ben Kirtman (Global Change Biology, 2022)
Given climate change threats to ecosystems, it is critical to understand the responses of species to warming. This is especially important in the case of apex predators since they exhibit relatively high extinction risk, and changes to their distribution could impact predator–prey interactions that can initiate trophic cascades. Here we used a combined analysis of animal tracking, remotely sensed environmental data, habitat modeling, and capture data to evaluate the effects of climate variability and change on the distributional range and migratory phenology of an ectothermic apex predator, the tiger shark ( Galeocerdo cuvier ). Tiger sharks satellite tracked in the western North Atlantic between 2010 and 2019 revealed significant annual variability in the geographic extent and timing of their migrations to northern latitudes from ocean warming. Specifically, tiger shark migrations have extended farther poleward and arrival times to northern latitudes have occurred earlier in the year during periods with anomalously high sea‐surface temperatures. A complementary analysis of nearly 40 years of tiger shark captures in the region revealed decadal‐scale changes in the distribution and timing of shark captures in parallel with long‐term ocean warming. Specifically, areas of highest catch densities have progressively increased poleward and catches have occurred earlier in the year off the North American shelf. During periods of anomalously high sea‐surface temperatures, movements of tracked sharks shifted beyond spatial management zones that had been affording them protection from commercial fishing and bycatch. Taken together, these study results have implications for fisheries management, human–wildlife conflict, and ecosystem functioning.

Natal experience and pre‐breeding environmental conditions affect lay date plasticity in Savannah Sparrows - Joseph B. Burant; Eric W. Heisey; Nathaniel T. Wheelwright; Amy E. M. Newman; Shannon Whelan; Daniel J. Mennill; Stéphanie M. Doucet; Greg W. Mitchell; Bradley K. Woodworth; D. Ryan Norris (Ecology, 2022)
Phenotypic plasticity allows organisms to adjust the timing of life‐history events in response to environmental and demographic conditions. Shifts by individuals in the timing of breeding with respect to variation in age and temperature are well documented in nature, and these changes are known to scale to affect population dynamics. However, relatively little is known about how organisms alter phenology in response to other demographic and environmental factors. We investigated how pre‐breeding temperature, breeding population density, age, and rainfall in the first month of life influenced the timing and plasticity of lay date in a population of Savannah Sparrows ( Passerculus sandwichensis ) monitored over 33 yr (1987–2019). Females that experienced warmer pre‐breeding temperatures tended to lay eggs earlier, as did older females, but breeding population density had no effect on lay date. Natal precipitation interacted with age to influence lay date plasticity, with females that experienced high precipitation levels as nestlings advancing lay dates more strongly over the course of their lives. We also found evidence for varied pace of life; females that experienced high natal precipitation had shorter lifespans and reduced fecundity, but more nesting attempts over their lifetimes. Rainfall during the nestling period increased through time, while population density and fecundity declined, suggesting that increased precipitation on the breeding grounds may be detrimental to breeding females and ultimately the viability of the population as a whole. Our results suggest that females adjust their laying date in response to pre‐breeding temperature, and as they age, while presenting new evidence that environmental conditions during the natal period can affect phenological plasticity and generate downstream, population‐level effects.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Microsatellite markers for Gingidia enysii and G. baxterae (Apiaceae) and their taxonomic utility - Peter B. Heenan; Gary J. Houliston; Caroline M. Mitchell (New Zealand Journal of Botany, 2021)
Gingidia comprises nine species of perennial herbaceous plants from New Zealand and three species from Australia. Microsatellite markers were developed for Gingidia enysii sens. lat. and G. baxterae for genetic and systematic studies of the two species in New Zealand. From sequencing a total genomic DNA library (using Roche 454), we developed nine polymorphic microsatellite markers. We tested these markers on 142 individuals from 19 populations of G. enysii sens. lat. and 10 individuals from two populations of G. baxterae . All loci amplified in both species, and exhibited species‐specific alleles. In populations of G. enysii sens. lat. and G. baxterae the observed and expected heterozygosities ranged from 0.04–0.34 and from 0.31–0.80, respectively, with alleles per locus ranging from 7 to 25. Analyses of population genetic data show G. enysii sens. lat. to be naturally variable throughout its distributional range, and the suggested taxonomic novelties within G. enysii are mostly not distinct. However, populations from Banks Peninsula (Canterbury), previously referred to as Gingidium enysii var. peninsulare , are genetically discrete, and re‐examination of their morphological characters is warranted. The developed markers will be valuable for future studies of taxonomy, phylogenetics, population structure, and mating system.

Climate drivers of adult insect activity are conditioned by life history traits - Michael W. Belitz; Vijay Barve; Joshua R. Doby; Maggie M. Hantak; Elise A. Larsen; Daijiang Li; Jessica A. Oswald; Neeka Sewnath; Mitchell Walters; Narayani Barve; Kamala Earl; Nicholas Gardner; et al. (Ecology Letters, 2021)
Insect phenological lability is key for determining which species will adapt under environmental change. However, little is known about when adult insect activity terminates and overall activity duration. We used community‐science and museum specimen data to investigate the effects of climate and urbanisation on timing of adult insect activity for 101 species varying in life history traits. We found detritivores and species with aquatic larval stages extend activity periods most rapidly in response to increasing regional temperature. Conversely, species with subterranean larval stages have relatively constant durations regardless of regional temperature. Species extended their period of adult activity similarly in warmer conditions regardless of voltinism classification. Longer adult durations may represent a general response to warming, but voltinism data in subtropical environments are likely underreported. This effort provides a framework to address the drivers of adult insect phenology at continental scales and a basis for predicting species response to environmental change.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Field testing cellulose-water oxygen isotope relations in periphyton for paleohydrological reconstructions - Cory A. M. Savage; Casey R. Remmer; James V. Telford; Mitchell L. Kay; Eva Mehler; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Molecular Dynamics Simulations and Experimental Results Provide Insight into Clinical Performance Differences between Sandimmune® and Neoral® Lipid-Based Formulations - Dallas B. Warren; Shadabul Haque; Mitchell P. McInerney; Karen M. Corbett; Endri Kastrati; Leigh Ford; Hywel D. Williams; Vincent Jannin; Hassan Benameur; Christopher J.H. Porter; David K. Chalmers; Colin W. Pouton (Pharmaceutical Research, 2021)

Dumpsters and other anthropogenic structures as habitat for invasive African rock agama lizards in Florida - Timothy S. Mitchell; Brian Folt; Joshua M. Hall (Biological Invasions, 2021)

Pleistocene origins, western ghost lineages, and the emerging phylogeographic history of the red wolf and coyote - Benjamin N. Sacks; Kieren J. Mitchell; Cate B. Quinn; Lauren M. Hennelly; Mikkel‐Holger S. Sinding; Mark J. Statham; Sophie Preckler‐Quisquater; Steven R. Fain; Logan Kistler; Stevi L. Vanderzwan; Julie A. Meachen; Elaine A. Ostrander; et al. (Molecular Ecology, 2021)
The red wolf ( Canis rufus ) of the eastern US was driven to near‐extinction by colonial‐era persecution and habitat conversion, which facilitated coyote ( C . latrans ) range expansion and widespread hybridization with red wolves. The observation of some grey wolf ( C . lupus ) ancestry within red wolves sparked controversy over whether it was historically a subspecies of grey wolf with its predominant “coyote‐like” ancestry obtained from post‐colonial coyote hybridization (2‐species hypothesis) versus a distinct species closely related to the coyote that hybridized with grey wolf (3‐species hypothesis). We analysed mitogenomes sourced from before the 20th century bottleneck and coyote invasion, along with hundreds of modern amplicons, which led us to reject the 2‐species model and to investigate a broader phylogeographic 3‐species model suggested by the fossil record. Our findings broadly support this model, in which red wolves ranged the width of the American continent prior to arrival of the grey wolf to the mid‐continent 60–80 ka; red wolves subsequently disappeared from the mid‐continent, relegated to California and the eastern forests, which ushered in emergence of the coyote in their place (50–30 ka); by the early Holocene (12–10 ka), coyotes had expanded into California, where they admixed with and phenotypically replaced western red wolves in a process analogous to the 20th century coyote invasion of the eastern forests. Findings indicate that the red wolf pre‐dated not only European colonization but human, and possibly coyote, presence in North America. These findings highlight the urgency of expanding conservation efforts for the red wolf.

The AGE Presents Introduction to Geroscience video lecture series - Alessandro Bitto; Mitchell B. Lee; Cristal M. Hill; Ron Korstanje; Matt Kaeberlein (GeroScience, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.

Long-Term Application of Cerebellar Transcranial Direct Current Stimulation Does Not Improve Motor Learning in Parkinson’s Disease - Lidio Lima de Albuquerque; Milan Pantovic; Mitchell G. Clingo; Katherine M. Fischer; Sharon Jalene; Merrill R. Landers; Zoltan Mari; Brach Poston (The Cerebellum, 2021)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

Preclinical Studies of MSC-Derived Extracellular Vesicles to Treat or Prevent Graft Versus Host Disease: a Systematic Review of the Literature - Manika Gupta; Alvin Tieu; Mitchell Slobodian; Risa Shorr; Dylan Burger; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2021)

Plasma anti-CD4 IgG is associated with brain abnormalities in people with HIV on antiretroviral therapy - Scott Bowler; Brooks I. Mitchell; Kalpana J. Kallianpur; Dominic Chow; Wei Jiang; Cecilia M. Shikuma; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2021)

Hotspots of invasive plant abundance are geographically distinct from hotspots of establishment - Mitchell W. O’Neill; Bethany A. Bradley; Jenica M. Allen (Biological Invasions, 2021)

The mangrove CO 2 pump: Tidally driven pore‐water exchange - Xiaogang Chen; Isaac R. Santos; Mitchell Call; Gloria M. S. Reithmaier; Damien Maher; Ceylena Holloway; Praktan D. Wadnerkar; Paula Gómez‐Álvarez; Christian J. Sanders; Ling Li (Limnology and Oceanography, 2021)
Atmospheric carbon dioxide (CO 2 ) is fixed by mangrove vegetation and stored in its biomass and sediments. Part of the sediment carbon can be exported to coastal waters via tidally driven pore‐water exchange. Here, we quantify pore water‐derived dissolved CO 2 export using in situ, high‐resolution observations of 222 Rn and CO 2 over a spring‐neap tidal cycle in a mangrove‐fringed estuary (Coffs Creek, Australia). 222 Rn‐derived pore‐water exchange rates were 11.5–34.9 cm d −1 (23.0 ± 6.7) over 30 tidal cycles. Pore‐water exchange released CO 2 from intertidal sediment at rates of 61–213 (136 ± 43) mmol m −2 d −1 . This is equivalent to ~ 94% of the total CO 2 input into the estuary and approximately two times of the water‐atmosphere CO 2 emission. These observations reveal that tidal pumping is a major regulator of both mangrove pore‐water exchange and associated dissolved CO 2 export to the ocean. Combining our estimates with literature data, a first‐order global pore water‐derived dissolved CO 2 export from mangroves was estimated to be 83 ± 50 Tg C yr −1 . This is higher than an earlier estimates of global mangrove CO 2 emissions to the atmosphere (34.1 ± 5.4 Tg C yr −1 ) and carbon burial in sediments (18.4–34.4 Tg C yr −1 ), implying that pore water‐derived CO 2 escapes to the atmosphere within and beyond mangrove waters. Overall, CO 2 ‐rich pore water seems to be a widespread, important pathway of CO 2 into mangrove‐dominated estuaries and should be considered in mangrove carbon assessments in the context of global climate change and blue carbon.

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Uniparental isodisomy of chromosome 2 causing MRPL44-related multisystem mitochondrial disease - Alejandro Horga; Andreea Manole; Alice L. Mitchell; Enrico Bugiardini; Iain P. Hargreaves; Walied Mowafi; Conceição Bettencourt; Emma L. Blakely; Langping He; James M. Polke; Catherine E. Woodward; Ilaria Dalla Rosa; et al. (Molecular Biology Reports, 2021)

Dependence on a human structure influences the extinction of a non-native lizard population after a major environmental change - Daniel A. Warner; Joshua M. Hall; Amélie Fargevieille; Austin C. Hulbert; Sarin Tiatragul; Jenna E. Pruett; Timothy S. Mitchell (Biological Invasions, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Functional and ecosystem service differences between tree species: implications for tree species replacement - R. J. Mitchell; R. L. Hewison; R. K. Haghi; A. H. J. Robertson; A. M. Main; I. J. Owen (Trees, 2021)

Highly diverse mesophotic reef fish communities in Raja Ampat, West Papua - Dominic A. Andradi-Brown; Angela J. E. Beer; Luigi Colin; Hastuti; Catherine E. I. Head; Nur Ismu Hidayat; Steven J. Lindfield; Catherine R. Mitchell; Defy N. Pada; Nikola M. Piesinger; Purwanto; Gabby N. Ahmadia (Coral Reefs, 2021)
Mesophotic coral ecosystems (MCEs; reefs 30–150 m depth) are poorly studied, with existing research heavily geographically biased away from the most species-rich reef regions. Yet, MCEs are of high interest because of their unique species and potential to act as refuges from the impacts of fishing. Using baited remote underwater video systems, we surveyed reef fish communities from 2 to 85 m depths throughout the Raja Ampat archipelago in West Papua, Indonesia—an area considered the heart of the Coral Triangle where coral reef biodiversity is greatest. We sought to provide the first assessment of fish communities across this depth gradient in the region and identify whether human population density and market access differently affected fish abundance based on depth. Here we show that—similar to shallow reefs—Raja Ampat MCEs are exceptionally diverse, with 152 fish species recorded at depths greater than 40 m. We found that fish community structures were highly depth driven, with declines in fish abundance at increased depth. In contrast to previous studies elsewhere in the world, we found that the proportion of planktivores declined across the shallow reef to MCE depth gradient. While greater human population density correlated with lower Epinephelidae and Lutjanidae abundance (two key fisheries families), we did not find evidence that MCEs provide a depth refuge from fishing. Surprisingly, we also found that fish abundance declined at greater distances from the major regional market—likely caused by historical fisheries pressure in more remote areas. These results both expand upon and contrast some previously established MCE-depth patterns and human impact patterns on fish communities, suggesting that regional context and historical pressures matters. Our findings highlight the need for future MCE studies within the Coral Triangle region.

Characterization of Anchorless Human PrP With Q227X Stop Mutation Linked to Gerstmann-Sträussler-Scheinker Syndrome In Vivo and In Vitro - Pingping Shen; Johnny Dang; Zerui Wang; Weiguanliu Zhang; Jue Yuan; Yue Lang; Mingxuan Ding; Marcus Mitchell; Qingzhong Kong; Jiachun Feng; Annemiek J. M. Rozemuller; Li Cui; et al. (Molecular Neurobiology, 2021)
Alteration in cellular prion protein (PrP C ) localization on the cell surface through mediation of the glycosylphosphatidylinositol (GPI) anchor has been reported to dramatically affect the formation and infectivity of its pathological isoform (PrP Sc ). A patient with Gerstmann-Sträussler-Scheinker (GSS) syndrome was previously found to have a nonsense heterozygous PrP-Q227X mutation resulting in an anchorless PrP. However, the allelic origin of this anchorless PrP Sc and cellular trafficking of PrP Q227X remain to be determined. Here, we show that PrP Sc in the brain of this GSS patient is mainly composed of the mutant but not wild-type PrP (PrP Wt ), suggesting pathological PrP Q227X is incapable of recruiting PrP Wt in vivo. This mutant anchorless protein, however, is able to recruit PrP Wt from humanized transgenic mouse brain but not from autopsied human brain homogenates to produce a protease-resistant PrP Sc -like form in vitro by protein misfolding cyclic amplification (PMCA). To further investigate the characteristics of this mutation, constructs expressing human PrP Q227X or PrP Wt were transfected into neuroblastoma cells (M17). Fractionation of the M17 cells demonstrated that most PrP Wt is recovered in the cell lysate fraction, while most of the mutant PrP Q227X is recovered in the medium fraction, consistent with the results obtained by immunofluorescence microscopy. Two-dimensional gel-electrophoresis and Western blotting showed that cellular PrP Q227X spots clustered at molecular weights of 22–25 kDa with an isoelectric point ( p I) of 3.5–5.5, whereas protein spots from the medium are at 18–26 kDa with a p I of 7–10. Our findings suggest that the role of GPI anchor in prion propagation between the anchorless mutant PrP and wild-type PrP relies on the cellular distribution of the protein.

C-band synthetic aperture radar (SAR) imagery for the classification of diverse cropping systems - Laura Dingle Robertson; Andrew M. Davidson; Heather McNairn; Mehdi Hosseini; Scott Mitchell; Diego de Abelleyra; Santiago Verón; Guerric le Maire; Milena Plannells; Silvia Valero; Nima Ahmadian; Alisa Coffin; et al. (International Journal of Remote Sensing, 2020)

Mesoscopic Damage and Fracturing of Heterogeneous Brittle Rocks Based on Three-dimensional Polycrystalline Discrete Element Method - Tao Xu; Teng-Fei Fu; Michael J. Heap; Philip G. Meredith; Thomas M. Mitchell; Patrick Baud (Rock Mechanics and Rock Engineering, 2020)

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

The catechol-O-methyltransferase inhibitor tolcapone modulates alcohol consumption and impulsive choice in alcohol use disorder - Allison R. Coker; Dawn N. Weinstein; Taylor A. Vega; Catriona S. Miller; Andrew S. Kayser; Jennifer M. Mitchell (Psychopharmacology, 2020)

Evaluation of implementation of risk management guidelines for carriers of pathogenic variants in mismatch repair genes: a nationwide audit of familial cancer clinics - B. Meiser; R. Kaur; J. Kirk; A. Morrow; M. Peate; W. K. T. Wong; E. McPike; E. Cops; C. Dowson; R. Austin; M. Fine; L. Thrupp; et al. (Familial Cancer, 2020)

Response to Letter to the Editor: Are five 60-min sessions of isothermic heat acclimation sufficient to elicit beneficial physiological adaptations? - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)

Prostate-specific antigen testing after the US Preventive Services Task Force recommendation: a population-based analysis of electronic health data - Daniel M. Frendl; Mara M. Epstein; Hassan Fouayzi; Richard Krajenta; Benjamin A. Rybicki; Mitchell H. Sokoloff (Cancer Causes & Control, 2020)

Calibration of a common shortwave multispectral camera system for quantitative agricultural applications - J. Burdette Barker; Wayne E. Woldt; Brian D. Wardlow; Christopher M. U. Neale; Mitchell S. Maguire; Bryan C. Leavitt; Derek M. Heeren (Precision Agriculture, 2020)

Characteristics that make trophy hunting of giant pandas inconceivable - Robert A. Montgomery; Madeline Carr; Charlie R. Booher; Abigail M. Pointer; Brendan M. Mitchell; Natalie Smith; Keegan Calnan; Georgina M. Montgomery; Mordecai Ogada; Daniel B. Kramer (Conservation Biology, 2020)
In November 1928, Theodore Jr. and Kermit Roosevelt led an expedition to China with the expressed purpose of being the first Westerners to kill the giant panda (Ailuropoda melanoleuca). The expedition lasted 8 months and resulted in the brothers shooting a giant panda in the mountains of Sichuan Province. Given the concurrent attention in the popular press describing this celebrated expedition, the giant panda was poised to be trophy hunted much like other large mammals around the world. Today, however, the killing of giant pandas, even for the generation of conservation revenue, is unthinkable for reasons related to the species itself and the context, in time and space, in which the species was popularized in the West. We found that the giant panda's status as a conservation symbol, exceptional charisma and gentle disposition, rarity, value as a nonconsumptive ecotourism attraction, and endemism are integral to the explanation of why the species is not trophy hunted. We compared these intrinsic and extrinsic characteristics with 20 of the most common trophy‐hunted mammals to determine whether the principles applying to giant pandas are generalizable to other species. Although certain characteristics of the 20 trophy‐hunted mammals aligned with the giant panda, many did not. Charisma, economic value, and endemism, in particular, were comparatively unique to the giant panda. Our analysis suggests that, at present, exceptional characteristics may be necessary for certain mammals to be excepted from trophy hunting. However, because discourse relating to the role of trophy hunting in supporting conservation outcomes is dynamic in both science and society, we suspect these valuations will also change in future.

Evaluation of Structured and Unstructured Models for Application in Operational Ocean Forecasting in Nearshore Waters - Shannon Nudds; Youyu Lu; Simon Higginson; Susan P. Haigh; Jean-Philippe Paquin; Mitchell O’Flaherty-Sproul; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Gregory C. Smith; Natacha B. Bernier; Phillip MacAulay; et al. (Journal of Marine Science and Engineering, 2020)
The oceanography sub-initiative of Canada’s Oceans Protection Plan was tasked to develop high-resolution nearshore ocean models for enhanced marine safety and emergency response, fitting into the multi-scale, multi-level nested operational ocean forecasting systems. For decision making on eventual 24/7 operational support, two ocean models (a structured grid model, NEMO (Nucleus for European Modelling of the Ocean); and an unstructured grid model, FVCOM (Finite Volume Coastal Ocean Model), were evaluated. The evaluation process includes the selection of the study area, the requirements for model setup, and the evaluation metrics. The chosen study area, Saint John Harbour in the Bay of Fundy, features strong tides, significant river runoff and a narrow tidal-river channel. Both models were configured with the same sources of bathymetry and forcing data. FVCOM achieved 50-100 m horizontal resolution in the inner harbour and included wetting/drying. NEMO achieved 100 m resolution in the harbour with a three-level one-way nesting configuration. Statistical metrics showed that one-year simulations with both models achieved comparable accuracies against the observed tidal and non-tidal water levels and currents, temperature and salinity, and the trajectories of surface drifters, but the computational cost of FVCOM was significantly less than that of NEMO.

The importance of diversity and outreach in geroscience research: Insights from the Annual Biomedical Research Conference for Minority Students - Mitchell B. Lee; Dibyadeep Datta; Cristal M. Hill; Alessandro Bitto (GeroScience, 2020)

Cyclodextrins in drug delivery: applications in gene and combination therapy - Rebecca M. Haley; Riccardo Gottardi; Robert Langer; Michael J. Mitchell (Drug Delivery and Translational Research, 2020)

Use of human-made structures facilitates persistence of a non-native ectotherm - Austin C. Hulbert; Joshua M. Hall; Timothy S. Mitchell; Daniel A. Warner (Biological Invasions, 2020)

Test–Retest Reliability of Functional Magnetic Resonance Imaging Activation for a Vergence Eye Movement Task - Cristian Morales; Suril Gohel; Xiaobo Li; Mitchell Scheiman; Bharat B. Biswal; Elio M. Santos; Chang Yaramothu; Tara L. Alvarez (Neuroscience Bulletin, 2020)

Rock avalanche runout prediction using stochastic analysis of a regional dataset - A. Mitchell; S. McDougall; N. Nolde; M.-A. Brideau; J. Whittall; J. B. Aaron (Landslides, 2020)

Strain-specificity in the hydrogen sulphide signalling network following dietary restriction in recombinant inbred mice - Stephen E. Wilkie; Lorna Mulvey; William A. Sands; Diana E. Marcu; Roderick N. Carter; Nicholas M. Morton; Christopher Hine; James R. Mitchell; Colin Selman (GeroScience, 2020)
Modulation of the ageing process by dietary restriction (DR) across multiple taxa is well established. While the exact mechanism through which DR acts remains elusive, the gasotransmitter hydrogen sulphide (H 2 S) may play an important role. We employed a comparative-type approach using females from three ILSXISS recombinant inbred mouse strains previously reported to show differential lifespan responses following 40% DR. Following long-term (10 months) 40% DR, strain TejJ89—reported to show lifespan extension under DR—exhibited elevated hepatic H 2 S production relative to its strain-specific ad libitum (AL) control. Strain TejJ48 (no reported lifespan effect following 40% DR) exhibited significantly reduced hepatic H 2 S production, while H 2 S production was unaffected by DR in strain TejJ114 (shortened lifespan reported following 40% DR). These differences in H 2 S production were reflected in highly divergent gene and protein expression profiles of the major H 2 S production and disposal enzymes across strains. Increased hepatic H 2 S production in TejJ89 mice was associated with elevation of the mitochondrial H 2 S-producing enzyme 3-mercaptopyruvate sulfurtransferase (MPST). Our findings further support the potential role of H 2 S in DR-induced longevity and indicate the presence of genotypic-specificity in the production and disposal of hepatic H 2 S in response to 40% DR in mice.

Examining HPV Vaccination Practices and Differences Among Providers in Virginia - Héctor E. Alcalá; George Larry Maxwell; Brianna Lindsay; Jessica Keim-Malpass; Emma M. Mitchell; Rajesh Balkrishnan (Journal of Cancer Education, 2020)

Dietary Ecology of the Nigeria–Cameroon Chimpanzee (Pan troglodytes ellioti) - Ekwoge E. Abwe; Bethan J. Morgan; Roger Doudja; Fabrice Kentatchime; Flaubert Mba; Alvine Dadjo; Dana M. Venditti; Matthew W. Mitchell; Bernard Fosso; Albert Mounga; Roger C. Fotso; Mary Katherine Gonder (International Journal of Primatology, 2020)

Short-term isothermic heat acclimation elicits beneficial adaptations but medium-term elicits a more complete adaptation - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)
Purpose To investigate the effects of 60 min daily, short-term (STHA) and medium-term (MTHA) isothermic heat acclimation (HA) on the physiological and perceptual responses to exercise heat stress. Methods Sixteen, ultra-endurance runners (female = 3) visited the laboratory on 13 occasions. A 45 min sub-maximal (40% W max ) cycling heat stress test (HST) was completed in the heat (40 °C, 50% relative humidity) on the first (HST PRE ), seventh (HST STHA ) and thirteenth (HST MTHA ) visit. Participants completed 5 consecutive days of a 60 min isothermic HA protocol (target T re 38.5 °C) between HST PRE and HST STHA and 5 more between HST STHA and HST MTHA . Heart rate (HR), rectal ( T re ), skin ( T sk ) and mean body temperature ( T body ), perceived exertion (RPE), thermal comfort (TC) and sensation (TS) were recorded every 5 min. During HSTs, cortisol was measured pre and post and expired air was collected at 15, 30 and 45 min. Results At rest, T re and T body were lower in HST STHA and HST MTHA compared to HST PRE, but resting HR was not different between trials. Mean exercising T re , T sk , T body , and HR were lower in both HST STHA and HST MTHA compared to HST PRE . There were no differences between HST STHA and HST MTHA . Perceptual measurements were lowered by HA and further reduced during HST MTHA . Conclusion A 60 min a day isothermic STHA was successful at reducing physiological and perceptual strain experienced when exercising in the heat; however, MTHA offered a more complete adaptation.

The importance of turtle populations to wetland restoration in the Upper Mississippi Embayment of the Mississippi Alluvial Valley - Max A. Nickerson; Joseph C. Mitchell; Brad M. Glorioso (Wetlands Ecology and Management, 2019)

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

S100B and its association with HIV-associated neurocognitive disorders - Nath Limpruttidham; Brooks I. Mitchell; Kalpana J. Kallianpur; Beau K. Nakamoto; Scott A. Souza; Bruce Shiramizu; Lishomwa C. Ndhlovu; Dominic C. Chow; Cecilia M. Shikuma (Journal of NeuroVirology, 2019)

Relationship between West African ancestry with lung cancer risk and survival in African Americans - Khadijah A. Mitchell; Ebony Shah; Elise D. Bowman; Adriana Zingone; Noah Nichols; Sharon R. Pine; Rick A. Kittles; Bríd M. Ryan (Cancer Causes & Control, 2019)

Colloid Transport in Porous Media: A Review of Classical Mechanisms and Emerging Topics - Ian L. Molnar; Erica Pensini; Md Abdullah Asad; Chven A. Mitchell; Ludwig C. Nitsche; Laura J. Pyrak-Nolte; Gastón L. Miño; Magdalena M. Krol (Transport in Porous Media, 2019)

Different as night and day: Behavioural and life history responses to varied photoperiods in Daphnia magna - Kurt A. Gust; Alan J. Kennedy; Jennifer G. Laird; Mitchell S. Wilbanks; Natalie D. Barker; Xin Guan; Nicolas L. Melby; Lyle D. Burgoon; Michael E. Kjelland; Todd M. Swannack (Molecular Ecology, 2019)
Nearly all animal species have utilized photoperiod to cue seasonal behaviours and life history traits. We investigated photoperiod responses in keystone species, Daphnia magna , to identify molecular processes underlying ecologically important behaviours and traits using functional transcriptomic analyses. Daphnia magna were photoperiod‐entrained immediately posthatch to a standard control photoperiod of 16 light/ 8 dark hours (16L:8D) relative to shorter (4L:20D, 8L:16D, 12L:12L) and longer (20L:4D) day length photoperiods. Short‐day photoperiods induced significantly increased light‐avoidance behaviours relative to controls. Correspondingly, significant differential transcript expression for genes involved in glutamate signalling was observed, a critical signalling pathway in arthropod light‐avoidance behaviour. Additionally, period circadian protein and proteins coding F‐box/LRR‐repeat domains were differentially expressed which are recognized to establish circadian rhythms in arthropods. Indicators of metabolic rate increased in short‐day photoperiods which corresponded with broadscale changes in transcriptional expression across system‐level energy metabolism pathways. The most striking observations included significantly decreased neonate production at the shortest day length photoperiod (4L:20D) and significantly increased male production across short‐day and equinox photoperiods (4L:20D, 8L:16D and 12L:12D). Transcriptional expression consistent with putative mechanisms of male production was observed including photoperiod‐dependent expression of transformer‐2 sex‐determining protein and small nuclear ribonucleoprotein particles (snRNPs) which control splice variant expression for genes like transformer. Finally, increased transcriptional expression of glutamate has also been shown to induce male production in Daphnia pulex via photoperiod‐sensitive mechanisms. Overall, photoperiod entrainment affected molecular pathways that underpin critical behavioural and life history traits in D. magna providing fundamental insights into biological responses to this primary environmental cue.

A Targeted Mutation Disrupting Mitochondrial Complex IV Function in Primary Afferent Neurons Leads to Pain Hypersensitivity Through P2Y1 Receptor Activation - Rory Mitchell; Graham Campbell; Marta Mikolajczak; Katie McGill; Don Mahad; Sue M. Fleetwood-Walker (Molecular Neurobiology, 2019)

The role of simulated spring water stress in interactions between eastern larch and larch casebearer - Samuel F. Ward; Aubree M. Kees; Mitchell P. Maddox; Rebecca A. Montgomery; Brian H. Aukema (Arthropod-Plant Interactions, 2019)

Time to revisit? A predator’s previous successes and failures in prey capture determine its return time to patches - S. Vijayan; J. K. Lee; J. Balaban-Feld; W. A. Mitchell; B. P. Kotler; M. L. Rosenzweig; T. T. Lotan; Z. Abramsky (Oecologia, 2019)

Assessing water-quality changes in US rivers at multiple geographic scales using results from probabilistic and targeted monitoring - Lori A. Sprague; Richard M. Mitchell; Amina I. Pollard; James A. Falcone (Environmental Monitoring and Assessment, 2019)

Deeply conserved susceptibility in a multi‐host, multi‐parasite system - Lisa N. Barrow; Sabrina M. McNew; Nora Mitchell; Spencer C. Galen; Holly L. Lutz; Heather Skeen; Thomas Valqui; Jason D. Weckstein; Christopher C. Witt (Ecology Letters, 2019)
Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection status, we applied Bayesian phylogenetic multilevel models that included a suite of environmental, spatial, temporal, life history and ecological predictors. We found evidence of deeply conserved susceptibility across the avian tree; host phylogeny explained substantial variation in infection status, and results were robust to phylogenetic uncertainty. Our study suggests that susceptibility is governed, in part, by conserved, latent aspects of anti‐parasite defence. This demonstrates the importance of deep phylogeny for understanding present‐day ecological interactions.

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Functional MRI and delay discounting in patients infected with hepatitis C - Holly McCready; Milky Kohno; Michael Kolessar; Laura Dennis; Daniel Kriz; Hannah Luber; Renee Anderson; Michael Chang; Anna Sasaki; Kenneth Flora; Arthur Vandenbark; Suzanne H. Mitchell; et al. (Journal of NeuroVirology, 2018)

Dopamine, time perception, and future time perspective - Jennifer M. Mitchell; Dawn Weinstein; Taylor Vega; Andrew S. Kayser (Psychopharmacology, 2018)

Interspecific interactions are conditional on temperature in an Appalachian stream salamander community - Mary Lou Hoffacker; Kristen K. Cecala; Joshua R. Ennen; Shawna M. Mitchell; Jon M. Davenport (Oecologia, 2018)

Combinatorial Preconditioning of Rat Brain Cultures with Subprotective Ethanol and Resveratrol Concentrations Promotes Synergistic Neuroprotection - N. Khodaie; N. Tajuddin; R. M. Mitchell; E. J. Neafsey; M. A. Collins (Neurotoxicity Research, 2018)

Differences in vascular function between trained and untrained limbs assessed by near-infrared spectroscopy - Rogério Nogueira Soares; Mitchell A. George; David N. Proctor; Juan M. Murias (European Journal of Applied Physiology, 2018)

Enhanced cutaneous wound healing in rats following topical delivery of insulin-loaded nanoparticles embedded in poly(vinyl alcohol)-borate hydrogels - Dalia H. Abdelkader; Murtaza M Tambuwala; Christopher A. Mitchell; Mohamed A. Osman; Sanaa A. El-Gizawy; Ahmed M. Faheem; Mohamed El-Tanani; Paul A. McCarron (Drug Delivery and Translational Research, 2018)

Engaging stakeholders in research to address water–energy–food (WEF) nexus challenges - C. Hoolohan; A. Larkin; C. McLachlan; R. Falconer; I. Soutar; J. Suckling; L. Varga; I. Haltas; A. Druckman; D. Lumbroso; M. Scott; D. Gilmour; et al. (Sustainability Science, 2018)

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Characterization of isolated liver sinusoidal endothelial cells for liver bioengineering - A. M. Dingle; K. K. Yap; Y-W. Gerrand; C. J. Taylor; E. Keramidaris; Z. Lokmic; A. M. Kong; H. L. Peters; W. A. Morrison; G. M. Mitchell (Angiogenesis, 2018)

Respiratory syncytial virus prophylaxis in cystic fibrosis: the Canadian registry of palivizumab data (2005–2016) - Ian Mitchell; S. K. Wong; B. Paes; M. Ruff; C. Bjornson; A. Li; K. L. Lanctôt (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Interdisciplinary Oncology Education: a National Survey of Trainees and Program Directors in the United States - Adil S. Akthar; Christopher D. Hellekson; Sabha Ganai; Olwen M. Hahn; Ronald J. Maggiore; Ezra E. Cohen; Mitchell C. Posner; Steven J. Chmura; Andrew R. Howard; Daniel W. Golden (Journal of Cancer Education, 2018)

Female investment in offspring size and number shifts seasonally in a lizard with single-egg clutches - Timothy S. Mitchell; Joshua M. Hall; Daniel A. Warner (Evolutionary Ecology, 2018)

A pharmacokinetic model for amiodarone in infants developed from an opportunistic sampling trial and published literature data - Samantha H. Dallefeld; Andrew M. Atz; Ram Yogev; Janice E. Sullivan; Amira Al-Uzri; Susan R. Mendley; Matthew Laughon; Christoph P. Hornik; Chiara Melloni; Barrie Harper; Andrew Lewandowski; Jeff Mitchell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

An update in international trends in incidence rates of thyroid cancer, 1973–2007 - Benjamin C. James; Janeil M. Mitchell; Heedo D. Jeon; Nektarios Vasilottos; Raymon H. Grogan; Briseis Aschebrook-Kilfoy (Cancer Causes & Control, 2018)

Colletotrichum species associated with pre-and post-harvest diseases of avocado and mango in eastern Australia - F. R. Giblin; Y. P. Tan; R. Mitchell; L. M. Coates; J. A. G. Irwin; R. G. Shivas (Australasian Plant Pathology, 2018)

Constant water table sub-irrigation of pots allows derivation of root weights (without physical recovery) and repeated measures of in situ growth and water use efficiencies - M. Hunter; G. Leong; J. Mitchell; M. Dieters; R. Fujinuma (Plant and Soil, 2018)

Species’ traits do not converge on optimum values in preferred habitats - Rachel M. Mitchell; Justin P. Wright; Greg M. Ames (Oecologia, 2018)

Heterogeneous impacts: adverse childhood experiences and cancer screening - Héctor E. Alcalá; Emma M. Mitchell; Jessica Keim-Malpass (Cancer Causes & Control, 2018)

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

(2E,6Z,9Z)-2,6,9-Pentadecatrienal as a Male-Produced Aggregation-Sex Pheromone of the Cerambycid Beetle Elaphidion mucronatum - Jocelyn G. Millar; Robert F. Mitchell; Linnea R. Meier; Todd D. Johnson; Judith A. Mongold-Diers; Lawrence M. Hanks (Journal of Chemical Ecology, 2017)

Conceptualizing Social Outcomes of Large Marine Protected Areas - Rebecca L. Gruby; Luke Fairbanks; Leslie Acton; Evan Artis; Lisa M. Campbell; Noella J. Gray; Lillian Mitchell; Sarah Bess Jones Zigler; Katie Wilson (Coastal Management, 2017)

Erratum to: Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

A synoptic survey of microbial respiration, organic matter decomposition, and carbon efflux in U.S. streams and rivers - Brian H. Hill; Colleen M. Elonen; Alan T. Herlihy; Terri M. Jicha; Richard M. Mitchell (Limnology and Oceanography, 2017)
We analyzed ecoenzyme activities related to organic matter processing in 1879 streams and rivers across the continental U.S. as part of the USEPA's National Rivers and Streams Assessment. Ecoenzymatic stoichiometry was used to construct models for carbon use efficiency (CUE) and decomposition (− k ). Microbial respiration ( R m ) was estimated from sediment organic carbon stocks, CUE, and − k . The streams and rivers were classified by size (headwaters: 1 st ‐order; streams: 2 nd –3 rd order; small rivers: 4 th –5 th order; big rivers 6 th –7 th order; and great rivers ≥ 8 th order) and condition class (least, intermediate, and most disturbed), and grouped into nine ecoregions. There were ecoregion, stream size, and condition class effects for CUE, − k , and R m , with R m increasing from eastern ecoregions through the plains to the western ecoregions. CUE, − k , and R m decreased with increasing streams size and increased with increasing disturbance. R m , CUE, and − k were correlated with water and sediment chemistry; CUE and − k were also correlated with stream bed fine sediments; and CUE was further correlated with catchment land cover. R m was extrapolated to ecoregional and national scales, and the results suggest that microbial assemblages account for 12% of the total CO 2 outgassing, and nearly 50% of the aquatic metabolism C losses, from U.S. streams and rivers. Cumulative respiratory C losses increased from headwaters to small streams, then decreased with increasing stream size. This U‐shaped respiration curve was not evident when streams were viewed by disturbance classes, suggesting that anthropogenic disturbances mask the expected organic matter processing signature of the river continuum.

Piscirickettsia salmonis infection in cultured lumpfish ( Cyclopterus lumpus L.) - M Marcos‐López; N M Ruane; F Scholz; M Bolton‐Warberg; S O Mitchell; S Murphy O'Sullivan; A Irwin Moore; H D Rodger (Journal of Fish Diseases, 2017)
A Piscirickettsia salmonis infection was diagnosed in lumpfish ( Cyclopterus lumpus L.) juveniles held in a marine research facility on the west coast of Ireland. The main clinical signs and pathology included marked ascites, severe multifocal liver necrosis and severe diffuse inflammation and necrosis of the exocrine pancreas and peri‐pancreatic adipose tissue. Numerous Piscirickettsia ‐like organisms were observed by histopathology in the affected organs, and the bacterial species was characterized by molecular analysis. Sequencing of the partial 16S rDNA gene and internal transcribed spacer region showed the lumpfish sequences to be closely related to previously identified Atlantic salmon ( Salmo salar L.) sequences from Ireland. To the authors’ knowledge, this is the first detection of P. salmonis in lumpfish worldwide. The infection is considered potentially significant in terms of lumpfish health and biosecurity.

Identification of a Bipolar Disorder Vulnerable Gene CHDH at 3p21.1 - Hong Chang; Lingyi Li; Tao Peng; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; et al. (Molecular Neurobiology, 2017)

Pre-operative Screening and Manual Drilling Strategies to Reduce the Risk of Thermal Injury During Minimally Invasive Cochlear Implantation Surgery - Neal P. Dillon; Loris Fichera; Kyle Kesler; M. Geraldine Zuniga; Jason E. Mitchell; Robert J. Webster; Robert F. Labadie (Annals of Biomedical Engineering, 2017)

Psychosocial morbidity in TP53 mutation carriers: is whole-body cancer screening beneficial? - Kate A. McBride; Mandy L. Ballinger; Timothy E. Schlub; Mary-Anne Young; Martin H. N. Tattersall; Judy Kirk; Ros Eeles; Emma Killick; Leslie G. Walker; Sue Shanley; David M. Thomas; Gillian Mitchell (Familial Cancer, 2017)

Generation of Octaploid Switchgrass by Seedling Treatment with Mitotic Inhibitors - Sangwoong Yoon; Sheyla Aucar; Bradley J. Hernlem; Serge Edme; Nathan Palmer; Gautam Sarath; Robert Mitchell; Eduardo Blumwald; Christian M . Tobias (BioEnergy Research, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Utilization of inulin-containing waste in industrial fermentations to produce biofuels and bio-based chemicals - Stephen R. Hughes; Nasib Qureshi; Juan Carlos López-Núñez; Marjorie A. Jones; Joshua M. Jarodsky; Luz Ángela Galindo-Leva; Mitchell R. Lindquist (World Journal of Microbiology and Biotechnology, 2017)

Revealing pMDI Spray Initial Conditions: Flashing, Atomisation and the Effect of Ethanol - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2017)

Local Radiation Treatment of HER2-Positive Breast Cancer Using Trastuzumab-Modified Gold Nanoparticles Labeled with 177Lu - Zhongli Cai; Simmyung Yook; Yijie Lu; Dane Bergstrom; Mitchell A. Winnik; Jean-Philippe Pignol; Raymond M. Reilly (Pharmaceutical Research, 2017)

Modeled ecohydrological responses to climate change at seven small watersheds in the northeastern United States - Afshin Pourmokhtarian; Charles T. Driscoll; John L. Campbell; Katharine Hayhoe; Anne M. K. Stoner; Mary Beth Adams; Douglas Burns; Ivan Fernandez; Myron J. Mitchell; James B. Shanley (Global Change Biology, 2017)
A cross‐site analysis was conducted on seven diverse, forested watersheds in the northeastern United States to evaluate hydrological responses (evapotranspiration, soil moisture, seasonal and annual streamflow, and water stress) to projections of future climate. We used output from four atmosphere–ocean general circulation models ( AOGCM s; CCSM 4, Had GEM 2‐ CC , MIROC 5, and MRI ‐ CGCM 3) included in Phase 5 of the Coupled Model Intercomparison Project, coupled with two Representative Concentration Pathways ( RCP 8.5 and 4.5). The coarse resolution AOGCM s outputs were statistically downscaled using an asynchronous regional regression model to provide finer resolution future climate projections as inputs to the deterministic dynamic ecosystem model Pn ET ‐ BGC . Simulation results indicated that projected warmer temperatures and longer growing seasons in the northeastern United States are anticipated to increase evapotranspiration across all sites, although invoking CO 2 effects on vegetation (growth enhancement and increases in water use efficiency ( WUE )) diminish this response. The model showed enhanced evapotranspiration resulted in drier growing season conditions across all sites and all scenarios in the future. Spruce‐fir conifer forests have a lower optimum temperature for photosynthesis, making them more susceptible to temperature stress than more tolerant hardwood species, potentially giving hardwoods a competitive advantage in the future. However, some hardwood forests are projected to experience seasonal water stress, despite anticipated increases in precipitation, due to the higher temperatures, earlier loss of snow packs, longer growing seasons, and associated water deficits. Considering future CO 2 effects on WUE in the model alleviated water stress across all sites. Modeled streamflow responses were highly variable, with some sites showing significant increases in annual water yield, while others showed decreases. This variability in streamflow responses poses a challenge to water resource management in the northeastern United States. Our analyses suggest that dominant vegetation type and soil type are important attributes in determining future hydrological responses to climate change.

Evidence that Cerambycid Beetles Mimic Vespid Wasps in Odor as well as Appearance - Robert F. Mitchell; Tomislav Curkovic; Judith A. Mongold-Diers; Lara Neuteboom; Hans-Martin Galbrecht; Armin Tröger; Jan Bergmann; Wittko Francke; Lawrence M. Hanks (Journal of Chemical Ecology, 2017)

Variations in carbon dioxide fluxes within a city landscape: Identifying a vehicular influence - Shannon M. Buckley; Myron J. Mitchell; Patrick J. McHale; Geoffrey D. Millard (Urban Ecosystems, 2016)

Convergent Lines of Evidence Support LRP8 as a Susceptibility Gene for Psychosis - Ming Li; Liang Huang; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; Andreas Reif; et al. (Molecular Neurobiology, 2016)

Relative importance of local- and large-scale drivers of alpine soil microarthropod communities - Ruth J. Mitchell; Hannah M. Urpeth; Andrea J. Britton; Helaina Black; Astrid R. Taylor (Oecologia, 2016)

Colletotrichum species in Australia - Roger G. Shivas; Yu Pei Tan; Jacqueline Edwards; Quang Dinh; Aaron Maxwell; Vera Andjic; José R. Liberato; Chris Anderson; Dean R. Beasley; Kaylene Bransgrove; Lindy M. Coates; Karren Cowan; et al. (Australasian Plant Pathology, 2016)

African American Patients’ Psychosocial Support Needs and Barriers to Treatment: Patient Needs Assessment - Maureen P. Davey; Brianna Bilkins; Guy Diamond; Alliric I. Willis; Edith P. Mitchell; Adam Davey; Faith M. Young (Journal of Cancer Education, 2016)

Syntrophic associations from hypersaline soda lakes converting organic acids and alcohols to methane at extremely haloalkaline conditions - Dimitry Y. Sorokin; Ben Abbas; Mitchell Geleijnse; Tatjana V. Kolganova; Robbert Kleerebezem; Mark C. M. van Loosdrecht (Environmental Microbiology, 2016)
Summary Until now anaerobic oxidation of VFA at high salt‐pH has been demonstrated only at sulfate‐reducing conditions. Here, we present results of a microbiological investigation of anaerobic conversion of organic acids and alcohols at methanogenic conditions by syntrophic associations enriched from hypersaline soda lakes in Central Asia. Sediment incubation experiments showed active, albeit very slow, methane formation from acetate, propionate, butyrate and C 2 C 4 alcohols at pH 10 and various levels of salinity. Enrichments of syntrophic associations using hydrogenotrophic members of the genus Methanocalculus from soda lakes as partners resulted in several highly enriched cultures converting acetate, propionate, butyrate, benzoate and EtOH to methane. Most syntrophs belonged to Firmicutes , while the propionate‐oxidizer formed a novel lineage within the family Syntrophobacteraceae in the Deltaproteobacteria . The acetate‐oxidizing syntroph was identified as ‘ Ca . Syntrophonatronum acetioxidans’ previously found to oxidize acetate at sulfate‐reducing conditions up to salt‐saturating concentrations. Butyrate and a benzoate‐degrading syntrophs represent novel genus‐level lineages in Syntrophomonadales which are proposed as Candidatus taxons ‘Syntrophobaca’, ‘Syntrophocurvum’ and ‘Syntropholuna’. Overall, despite very slow growth, the results indicated the presence of a functionally competent syntrophic community in hypersaline soda lakes, capable of efficient oxidation of fermentation products to methane at extremely haloalkaline conditions.

Productivity and species richness in longleaf pine woodlands: resource‐disturbance influences across an edaphic gradient - L. K. Kirkman; L. M. Giencke; R. S. Taylor; L. R. Boring; C. L. Staudhammer; R. J. Mitchell (Ecology, 2016)
This study examines the complex feedback mechanisms that regulate a positive relationship between species richness and productivity in a longleaf pine‐wiregrass woodland. Across a natural soil moisture gradient spanning wet‐mesic to xeric conditions, two large scale manipulations over a 10‐yr period were used to determine how limiting resources and fire regulate plant species diversity and productivity at multiple scales. A fully factorial experiment was used to examine productivity and species richness responses to N and water additions. A separate experiment examined standing crop and richness responses to N addition in the presence and absence of fire. Specifically, these manipulations addressed the following questions: (1) How do N and water addition influence annual aboveground net primary productivity of the midstory/overstory and ground cover? (2) How do species richness responses to resource manipulations vary with scale and among functional groups of ground cover species? (3) How does standing crop (including overstory, understory/midstory, and ground cover components) differ between frequently burned and fire excluded plots after a decade without fire? (4) What is the role of fire in regulating species richness responses to N addition? This long‐term study across a soil moisture gradient provides empirical evidence that species richness and productivity in longleaf pine woodlands are strongly regulated by soil moisture. After a decade of treatment, there was an overall species richness decline with N addition, an increase in richness of some functional groups with irrigation, and a substantial decline in species richness with fire exclusion. Changes in species richness in response to treatments were scale‐dependent, occurring primarily at small scales (≤10 m 2 ). Further, with fire exclusion, standing crop of ground cover decreased with N addition and non‐pine understory/midstory increased in wet‐mesic sites. Non‐pine understory/midstory standing crop increased in xeric sites with fire exclusion, but there was no influence of N addition. This study highlights the complexity of interactions among multiple limiting resources, frequent fire, and characteristics of dominant functional groups that link species richness and productivity.

Estimated lead (Pb) exposures for a population of urban community gardeners - Henry M. Spliethoff; Rebecca G. Mitchell; Hannah Shayler; Lydia G. Marquez-Bravo; Jonathan Russell-Anelli; Gretchen Ferenz; Murray McBride (Environmental Geochemistry and Health, 2016)

Daphnia magna’s sense of competition: intra-specific interactions (ISI) alter life history strategies and increase metals toxicity - Kurt A. Gust; Alan J. Kennedy; Nicolas L. Melby; Mitchell S. Wilbanks; Jennifer Laird; Barbara Meeks; Erik B. Muller; Roger M. Nisbet; Edward J. Perkins (Ecotoxicology, 2016)

Assessing the health effects of climate change in Alaska with community-based surveillance - David L. Driscoll; Erica Mitchell; Rebecca Barker; Janet M. Johnston; Sue Renes (Climatic Change, 2016)

Invariant natural killer T cells: front line fighters in the war against pathogenic microbes - Catherine M. Crosby; Mitchell Kronenberg (Immunogenetics, 2016)

Last interglacial (MIS 5e) sea-level determined from a tectonically stable, far-field location, Eyre Peninsula, southern Australia - C. V. Murray-Wallace; A. P. Belperio; A. Dosseto; W. A. Nicholas; C. Mitchell; R. P. Bourman; S. M. Eggins; R. Grün (Australian Journal of Earth Sciences, 2016)

Differential migration and the link between winter latitude, timing of migration, and breeding in a songbird - Bradley K. Woodworth; Amy E. M. Newman; Sheela P. Turbek; Bryant C. Dossman; Keith A. Hobson; Leonard I. Wassenaar; Greg W. Mitchell; Nathaniel T. Wheelwright; D. Ryan Norris (Oecologia, 2016)

The chemical coding of 5-hydroxytryptamine containing enteroendocrine cells in the mouse gastrointestinal tract - Yohan Reynaud; Josiane Fakhry; Linda Fothergill; Brid Callaghan; Mitchell Ringuet; Billie Hunne; David M. Bravo; John B. Furness (Cell and Tissue Research, 2016)

Immune ageing and susceptibility to Streptococcus pneumoniae - Mariana Torrente Gonçalves; Timothy J. Mitchell; Janet M. Lord (Biogerontology, 2016)

Dedicated Energy Crops and Crop Residues for Bioenergy Feedstocks in the Central and Eastern USA - R. B. Mitchell; M. R. Schmer; W. F. Anderson; V. Jin; K. S. Balkcom; J. Kiniry; A. Coffin; P. White (BioEnergy Research, 2016)
Dedicated energy crops and crop residues will meet herbaceous feedstock demands for the new bioeconomy in the Central and Eastern USA. Perennial warm-season grasses and corn stover are well-suited to the eastern half of the USA and provide opportunities for expanding agricultural operations in the region. A suite of warm-season grasses and associated management practices have been developed by researchers from the Agricultural Research Service of the US Department of Agriculture (USDA) and collaborators associated with USDA Regional Biomass Research Centers. Second generation biofuel feedstocks provide an opportunity to increase the production of transportation fuels from recently fixed plant carbon rather than from fossil fuels. Although there is no “one-size-fits-all” bioenergy feedstock, crop residues like corn ( Zea mays L.) stover are the most readily available bioenergy feedstocks. However, on marginally productive cropland, perennial grasses provide a feedstock supply while enhancing ecosystem services. Twenty-five years of research has demonstrated that perennial grasses like switchgrass ( Panicum virgatum L.) are profitable and environmentally sustainable on marginally productive cropland in the western Corn Belt and Southeastern USA.

Dedicated Herbaceous Biomass Feedstock Genetics and Development - W. F. Anderson; G. Sarath; S. Edme; M. D. Casler; R. B. Mitchell; C. M. Tobias; A. L. Hale; S. E. Sattler; J. E. Knoll (BioEnergy Research, 2016)

Insights into Spray Development from Metered-Dose Inhalers Through Quantitative X-ray Radiography - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Peter J. Stewart; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Julio Soria; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Temporally and Spatially Resolved x-ray Fluorescence Measurements of in-situ Drug Concentration in Metered-Dose Inhaler Sprays - Daniel J. Duke; Alan L. Kastengren; Nicholas Mason-Smith; Yang Chen; Paul M. Young; Daniela Traini; David Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Ikaros, Helios, and Aiolos protein levels increase in human thymocytes after β selection - Julie L. Mitchell; Amara Seng; Thomas M. Yankee (Immunologic Research, 2016)

Soil microorganisms behave like macroscopic organisms: patterns in the global distribution of soil euglyphid testate amoebae - Enrique Lara; Ludovic Roussel‐Delif; Bertrand Fournier; David M. Wilkinson; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Patterns of α‐ and β‐diversity of soil protist communities and the factors that shape them remain largely unknown. We undertook a world‐wide survey of forest litter to investigate the patterns of diversity in a group of testate amoebae. We aimed to assess: (1) whether there is a latitudinal gradient in α‐diversity, and (2) whether β‐diversity was correlated solely with environmental factors commonly used in soil biology research or if it was also independently explained by geographical barriers. Location World‐wide. Methods We studied the diversity of Euglyphida, a common group of testate amoebae, in 35 samples of forest litter and moss samples from a global survey, using small subunit rRNA gene sequences. We assessed the relationship between sample α‐diversity and latitude using generalized additive models ( GAM ). Furthermore, we determined the relationships between community composition and geographical models (distance‐based Moran's Eigenvector Maps – db‐ MEM ) using Generalized UniFrac distances ( GU niFrac). We also investigated the relationship between individual measured soil parameters, WorldClim data and diversity (alpha plus beta) using both raw data and synthetic variables obtained through principal components analysis. Results We recorded 245 phylotypes belonging to 6 out of 7 known Euglyphida families, plus four novel deep clades. Euglyphid α‐diversity was positively correlated with temperature and negatively with latitude and litter C/N ratio. Euglyphida community structure was correlated with the spatial eigenvector Db‐ MEM 31, independently of all measured environmental variables. Db‐ MEM 31 corresponds to a natural barrier constituted by the Northern Hemisphere desert belt. Beta diversity was correlated with other environmental variables, such as pH , isothermality and temperature in the coldest month of the year. Main conclusions Soil euglyphid α‐diversity displays a latitudinal gradient, and β‐diversity is not only correlated with climatic and physicochemical parameters but also with geographical barriers. Such patterns of diversity were until recently believed to be characteristic only for macroscopic organisms.

Altered relaxin family receptors RXFP1 and RXFP3 in the neocortex of depressed Alzheimer’s disease patients - Jasinda H. Lee; Shu Qing Koh; Simone Guadagna; Paul T. Francis; Margaret M. Esiri; Christopher P. Chen; Peter T.-H. Wong; Gavin S. Dawe; Mitchell K. P. Lai (Psychopharmacology, 2016)

Network analysis of human fMRI data suggests modular restructuring after simulated acquired brain injury - E. Ruiz Vargas; D. G. V. Mitchell; S. G. Greening; L. M. Wahl (Medical & Biological Engineering & Computing, 2016)

Timing and context: important considerations in the return of genetic results to research participants - Kate A. McBride; Nina Hallowell; Martin H. N. Tattersall; Judy Kirk; Mandy L. Ballinger; David M. Thomas; Gillian Mitchell; Mary-Anne Young (Journal of Community Genetics, 2016)

Rapid purging of genetic load in a metapopulation and consequences for range expansion in an invasive plant - Gina L. Marchini; Nena Cole Sherlock; Alisa P. Ramakrishnan; David M. Rosenthal; Mitchell B. Cruzan (Biological Invasions, 2016)

Aliidiomarina minuta sp. nov., a haloalkaliphilic bacterium that forms ultra-small cells under non-optimal conditions - Saad M. Farooqui; Mitchell H. Wright; Anthony C. Greene (Antonie van Leeuwenhoek, 2016)

Pathology and mortality associated with the mauve stinger jellyfish P elagia noctiluca in farmed A tlantic salmon S almo salar L. - M Marcos‐López; S O Mitchell; H D Rodger (Journal of Fish Diseases, 2016)

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Acute response to cluster sets in trained and untrained men - Jonathan M. Oliver; Andreas Kreutzer; Shane Jenke; Melody D. Phillips; Joel B. Mitchell; Margaret T. Jones (European Journal of Applied Physiology, 2015)

Hot Spots and Hot Times: Wildlife Road Mortality in a Regional Conservation Corridor - Evelyn Garrah; Ryan K. Danby; Ewen Eberhardt; Glenn M. Cunnington; Scott Mitchell (Environmental Management, 2015)

Whole-exome sequencing identifies novel ECHS1 mutations in Leigh syndrome - Martine Tetreault; Somayyeh Fahiminiya; Hana Antonicka; Grant A. Mitchell; Michael T. Geraghty; Matthew Lines; Kym M. Boycott; Eric A. Shoubridge; John J. Mitchell; Jacques L. Michaud; Jacek Majewski (Human Genetics, 2015)

Measurement of Forest Above-Ground Biomass Using Active and Passive Remote Sensing at Large (Subnational to Global) Scales - Richard M. Lucas; Anthea L. Mitchell; John Armston (Current Forestry Reports, 2015)

Absence of hybridisation between Fuscospora species at a site in Arthur's Pass National Park, New Zealand - RD Smissen; C Mitchell; M Roth; PB Heenan (New Zealand Journal of Botany, 2015)
We analysed simple sequence repeat markers for a selection of red beech ( Fuscospora fusca ) and mountain beech ( Fuscospora cliffortioides ) trees growing together and for seeds collected from them. Our analysis detected neither hybrid trees nor hybrid seeds within our sample. We suggest pre‐zygotic reproductive isolating mechanisms such as differences in flowering time may be important in maintaining boundaries between Fuscospora species despite extensive sympatry.

Psychopharmacological characterisation of the successive negative contrast effect in rats - C. E. Phelps; E. N. Mitchell; D. J. Nutt; H. M. Marston; E. S. J. Robinson (Psychopharmacology, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

The stratopause evolution during different types of sudden stratospheric warming event - Etienne Vignon; Daniel M. Mitchell (Climate Dynamics, 2015)

SNP development in North American burying beetles (Coleoptera: Silphidae): a tool to inform conservation decisions - Derek D. Houston; Kevin S. Mitchell; Jared W. Clouse; Peter J. Maughan; J. Curtis Creighton; Ashlee N. Smith; Seth M. Bybee; Mark C. Belk (Conservation Genetics Resources, 2015)

Cerambycid Beetle Species with Similar Pheromones are Segregated by Phenology and Minor Pheromone Components - Robert F. Mitchell; Peter F. Reagel; Joseph C. H. Wong; Linnea R. Meier; Weliton Dias Silva; Judith Mongold-Diers; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2015)

Spatial soil heterogeneity has a greater effect on symbiotic arbuscular mycorrhizal fungal communities and plant growth than genetic modification with B acillus thuringiensis toxin genes - Tanya E. Cheeke; Ursel M. Schütte; Chris M. Hemmerich; Mitchell B. Cruzan; Todd N. Rosenstiel; James D. Bever (Molecular Ecology, 2015)
Maize, genetically modified with the insect toxin genes of B acillus thuringiensis ( Bt ) , is widely cultivated, yet its impacts on soil organisms are poorly understood. Arbuscular mycorrhizal fungi ( AMF ) form symbiotic associations with plant roots and may be uniquely sensitive to genetic changes within a plant host. In this field study, the effects of nine different lines of B t maize and their corresponding non‐ B t parental isolines were evaluated on AMF colonization and community diversity in plant roots. Plants were harvested 60 days after sowing, and data were collected on plant growth and per cent AMF colonization of roots. AMF community composition in roots was assessed using 454 pyrosequencing of the 28 S r RNA genes, and spatial variation in mycorrhizal communities within replicated experimental field plots was examined. Growth responses, per cent AMF colonization of roots and AMF community diversity in roots did not differ between B t and non‐ B t maize, but root and shoot biomass and per cent colonization by arbuscules varied by maize cultivar. Plot identity had the most significant effect on plant growth, AMF colonization and AMF community composition in roots, indicating spatial heterogeneity in the field. Mycorrhizal fungal communities in maize roots were autocorrelated within approximately 1 m, but at greater distances, AMF community composition of roots differed between plants. Our findings indicate that spatial variation and heterogeneity in the field has a greater effect on the structure of AMF communities than host plant cultivar or modification by B t toxin genes.

Genetic diversity and population structure of the threatened freshwater catfish, Tandanus tandanus, in Victoria, Australia - Erin Hill; Brett A. Ingram; Meaghan Rourke; John Mitchell; Jan M. Strugnell (Conservation Genetics, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Antibiotic Degradation During Thermophilic Composting - S. M. Mitchell; J. L. Ullman; A. Bary; C. G. Cogger; A. L. Teel; R. J. Watts (Water, Air, & Soil Pollution, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Lack of in vitro–in vivo correlation for a UC781-releasing vaginal ring in macaques - Christopher McConville; James M. Smith; Clare F. McCoy; Priya Srinivasan; James Mitchell; Angela Holder; Ron A. Otten; Salvatore Butera; Gustavo F. Doncel; David R. Friend; R. Karl Malcolm (Drug Delivery and Translational Research, 2015)

Pollen‐based quantitative reconstructions of Holocene regional vegetation cover (plant‐functional types and land‐cover types) in Europe suitable for climate modelling - A.‐K. Trondman; M.‐J. Gaillard; F. Mazier; S. Sugita; R. Fyfe; A. B. Nielsen; C. Twiddle; P. Barratt; H. J. B. Birks; A. E. Bjune; L. Björkman; A. Broström; et al. (Global Change Biology, 2015)
We present quantitative reconstructions of regional vegetation cover in north‐western Europe, western Europe north of the Alps, and eastern Europe for five time windows in the Holocene [around 6k, 3k, 0.5k, 0.2k, and 0.05k calendar years before present ( bp )] at a 1° × 1° spatial scale with the objective of producing vegetation descriptions suitable for climate modelling. The REVEALS model was applied on 636 pollen records from lakes and bogs to reconstruct the past cover of 25 plant taxa grouped into 10 plant‐functional types and three land‐cover types [evergreen trees, summer‐green (deciduous) trees, and open land]. The model corrects for some of the biases in pollen percentages by using pollen productivity estimates and fall speeds of pollen, and by applying simple but robust models of pollen dispersal and deposition. The emerging patterns of tree migration and deforestation between 6k bp and modern time in the REVEALS estimates agree with our general understanding of the vegetation history of Europe based on pollen percentages. However, the degree of anthropogenic deforestation (i.e. cover of cultivated and grazing land) at 3k, 0.5k, and 0.2k bp is significantly higher than deduced from pollen percentages. This is also the case at 6k in some parts of Europe, in particular Britain and Ireland. Furthermore, the relationship between summer‐green and evergreen trees, and between individual tree taxa, differs significantly when expressed as pollen percentages or as REVEALS estimates of tree cover. For instance, when Pinus is dominant over Picea as pollen percentages, Picea is dominant over Pinus as REVEALS estimates. These differences play a major role in the reconstruction of European landscapes and for the study of land cover–climate interactions, biodiversity and human resources.

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Experimental evidence that invasive grasses use allelopathic biochemicals as a potential mechanism for invasion: chemical warfare in nature - Mitchell J. Greer; Gail W. T. Wilson; Karen R. Hickman; Stuart M. Wilson (Plant and Soil, 2014)

A Novel High-Speed Imaging Technique to Predict the Macroscopic Spray Characteristics of Solution Based Pressurised Metered Dose Inhalers - Nicolas A. Buchmann; Daniel J. Duke; Sayed A. Shakiba; Daniel M. Mitchell; Peter J. Stewart; Daniela Traini; Paul M. Young; David A. Lewis; Julio Soria; Damon Honnery (Pharmaceutical Research, 2014)

Mercury proxies and mercury dynamics in a forested watershed of the US Northeast - P. Vidon; W. Carleton; M. J. Mitchell (Environmental Monitoring and Assessment, 2014)

Winter climate change affects growing‐season soil microbial biomass and activity in northern hardwood forests - Jorge Durán; Jennifer L. Morse; Peter M. Groffman; John L. Campbell; Lynn M. Christenson; Charles T. Driscoll; Timothy J. Fahey; Melany C. Fisk; Myron J. Mitchell; Pamela H. Templer (Global Change Biology, 2014)
Understanding the responses of terrestrial ecosystems to global change remains a major challenge of ecological research. We exploited a natural elevation gradient in a northern hardwood forest to determine how reductions in snow accumulation, expected with climate change, directly affect dynamics of soil winter frost, and indirectly soil microbial biomass and activity during the growing season. Soils from lower elevation plots, which accumulated less snow and experienced more soil temperature variability during the winter (and likely more freeze/thaw events), had less extractable inorganic nitrogen (N), lower rates of microbial N production via potential net N mineralization and nitrification, and higher potential microbial respiration during the growing season. Potential nitrate production rates during the growing season were particularly sensitive to changes in winter snow pack accumulation and winter soil temperature variability, especially in spring. Effects of elevation and winter conditions on N transformation rates differed from those on potential microbial respiration, suggesting that N‐related processes might respond differently to winter climate change in northern hardwood forests than C‐related processes.

Characterization of T gene sequence variants and germline duplications in familial and sporadic chordoma - Michael J. Kelley; Jianxin Shi; Bari Ballew; Paula L. Hyland; Wen-Qing Li; Melissa Rotunno; David A. Alcorta; Norbert J. Liebsch; Jason Mitchell; Sara Bass; David Roberson; Joseph Boland; et al. (Human Genetics, 2014)

Delineation of Coastal Marsh Types Along the Central Texas Coast - Michael K. Mitchell; Bart M. Ballard; Jenneke M. Visser; Michael G. Brasher; Eric J. Redeker (Wetlands, 2014)

Lead in New York City community garden chicken eggs: influential factors and health implications - Henry M. Spliethoff; Rebecca G. Mitchell; Lisa N. Ribaudo; Owen Taylor; Hannah A. Shayler; Virginia Greene; Debra Oglesby (Environmental Geochemistry and Health, 2014)

Facial Emotion Processing in Borderline Personality Disorder: A Systematic Review and Meta-Analysis - Amy E. Mitchell; Geoffrey L. Dickens; Marco M. Picchioni (Neuropsychology Review, 2014)

The influence of a single bout of aerobic exercise on short-interval intracortical excitability - Ashleigh E. Smith; Mitchell R. Goldsworthy; Tessa Garside; Fiona M. Wood; Michael C. Ridding (Experimental Brain Research, 2014)

Comprehensive Analysis of Monomeric Phenolics in Dilute Acid Plant Hydrolysates - Valerie D. Mitchell; Caroline M. Taylor; Stefan Bauer (BioEnergy Research, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Interhemispheric and intrahemispheric connectivity and manual skills in children with unilateral cerebral palsy - Maya Weinstein; Dido Green; Ronny Geva; Mitchell Schertz; Aviva Fattal-Valevski; Moran Artzi; Vicki Myers; Shelly Shiran; Andrew M. Gordon; Varda Gross-Tsur; Dafna Ben Bashat (Brain Structure and Function, 2014)

Wnt5a, TLR2 and TLR4 are elevated in advanced human atherosclerotic lesions - Ramiro Malgor; Pooja M. Bhatt; Beth A. Connolly; Denise L. Jacoby; Kyle J. Feldmann; Mitchell J. Silver; Masato Nakazawa; Kelly D. McCall; Douglas J. Goetz (Inflammation Research, 2014)

Cascading Effects of Climate Change on Forest Ecosystems: Biogeochemical Links Between Trees and Moose in the Northeast USA - L. M. Christenson; M. J. Mitchell; P. M. Groffman; G. M. Lovett (Ecosystems, 2014)

When depth is no refuge: cumulative thermal stress increases with depth in Bocas del Toro, Panama - B. P. Neal; C. Condit; G. Liu; S. dos Santos; M. Kahru; B. G. Mitchell; D. I. Kline (Coral Reefs, 2014)

The value of plantation forests for plant, invertebrate and bird diversity and the potential for cross-taxon surrogacy - Sandra Irwin; Scott M. Pedley; Linda Coote; Anke C. Dietzsch; Mark W. Wilson; Anne Oxbrough; Oisín Sweeney; Karen M. Moore; Rebecca Martin; Daniel L. Kelly; Fraser J. G. Mitchell; Thomas C. Kelly; et al. (Biodiversity and Conservation, 2014)

Activity of the plant-based repellent, TT-4302 against the ticks Amblyomma americanum, Dermacentor variabilis, Ixodes scapularis and Rhipicephalus sanguineus (Acari: Ixodidae) - B. W. Bissinger; J. P. Schmidt; J. J. Owens; S. M. Mitchell; M. K. Kennedy (Experimental and Applied Acarology, 2014)

6-Pentyl-2H-pyran-2-one: A Potent Peach-Derived Kairomone for New Zealand Flower Thrips, Thrips obscuratus - A. M. El-Sayed; V. J. Mitchell; D. M. Suckling (Journal of Chemical Ecology, 2014)

Isolation of human lymphatic malformation endothelial cells, their in vitro characterization and in vivo survival in a mouse xenograft model - Zerina Lokmic; Geraldine M. Mitchell; Nicholas Koh Wee Chong; Jacqueline Bastiaanse; Yi-Wen Gerrand; Yiping Zeng; Elizabeth D. Williams; Anthony J. Penington (Angiogenesis, 2014)

On the origin and evolution of apomixis in Boechera - John T. Lovell; Olawale M. Aliyu; Martin Mau; M. Eric Schranz; Marcus Koch; Christiane Kiefer; Bao-Hua Song; Thomas Mitchell-Olds; Timothy F. Sharbel (Plant Reproduction, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Community‐specific impacts of exotic earthworm invasions on soil carbon dynamics in a sandy temperate forest - Jasmine M. Crumsey; James M. Le Moine; Yvan Capowiez; Mitchell M. Goodsitt; Sandra C Larson; George W. Kling; Knute J. Nadelhoffer (Ecology, 2013)
Exotic earthworm introductions can alter above‐ and belowground properties of temperate forests, but the net impacts on forest soil carbon (C) dynamics are poorly understood. We used a mesocosm experiment to examine the impacts of earthworm species belonging to three different ecological groups ( Lumbricus terrestris [anecic], Aporrectodea trapezoides [endogeic], and Eisenia fetida [epigeic]) on C distributions and storage in reconstructed soil profiles from a sandy temperate forest soil by measuring CO 2 and dissolved organic carbon (DOC) losses, litter C incorporation into soil, and soil C storage with monospecific and species combinations as treatments. Soil CO 2 loss was 30% greater from the Endogeic × Epigeic treatment than from controls (no earthworms) over the first 45 days; CO 2 losses from monospecific treatments did not differ from controls. DOC losses were three orders of magnitude lower than CO 2 losses, and were similar across earthworm community treatments. Communities with the anecic species accelerated litter C mass loss by 31–39% with differential mass loss of litter types ( Acer rubrum > Populus grandidentata > Fagus grandifolia > Quercus rubra ≥ Pinus strobus ) indicative of leaf litter preference. Burrow system volume, continuity, and size distribution differed across earthworm treatments but did not affect cumulative CO 2 or DOC losses. However, burrow system structure controlled vertical C redistribution by mediating the contributions of leaf litter to A‐horizon C and N pools, as indicated by strong correlations between (1) subsurface vertical burrows made by anecic species, and accelerated leaf litter mass losses (with the exception of P. strobus ); and (2) dense burrow networks in the A‐horizon and the C and N properties of these pools. Final soil C storage was slightly lower in earthworm treatments, indicating that increased leaf litter C inputs into soil were more than offset by losses as CO 2 and DOC across earthworm community treatments.

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Light and nutrient control of photosynthesis in natural phytoplankton populations from the Chukchi and Beaufort seas, Arctic Ocean - Molly A. Palmer; Gert L. van Dijken; B. Greg Mitchell; Brian J. Seegers; Kate E. Lowry; Matthew M. Mills; Kevin R. Arrigo (Limnology and Oceanography, 2013)
During the 2010–2011 ‘Impacts of Climate Change on the EcoSystems and Chemistry of the Arctic Pacific Environment’ project, we measured photosynthetic parameters in natural Arctic phytoplankton assemblages from the Chukchi and Beaufort seas. Water‐column samples were taken from the near surface (3.1 ± 0.9 m) and subsurface (28 ± 10.3 m) at ∼ 85 stations each year representing a wide range of ecological conditions, including under sea ice (UI) and in open water (OW). The physiological response of phytoplankton to light was used to assess photo‐acclimation, photosynthetic efficiency, and maximum chlorophyll a (Chl a ) normalized rates of carbon fixation. Phytoplankton from the subsurface were acclimated to lower irradiance, as evidenced by higher photosynthetic efficiencies ( α * ), reduced mean absorption spectra ( ā * ) associated with heavy pigment packaging, higher maximum quantum yields of photosynthesis (Φ m ), increased Chl a content (Chl a : POC), and higher potential growth rates ( μ m ) than surface samples. In addition, phytoplankton growing in the UI subsurface had higher μ m , increased Φ m , and higher Chl a content, as well as reduced ā * compared with those found in OW. P * m did not vary between habitats despite vastly different nutrient and light conditions (averaging ∼ 1 mg C mg −1 Chl a h −1 ), except where nitrate exceeded > 10 mg m −3 , in which case P * m averaged 5–6 mg C mg −1 Chl a h −1 . Results from a stepwise regression analysis of photosynthetic parameters vs. environmental factors indicate that the concentration of inorganic nitrogen (significant relationships with P * m , α * , Φ m , μ m , and Chl a : POC) and temperature at sample depth (a strong indicator of habitat type; significant relationship with β * , ā * , Φ m , μ m , and Chl a : POC) are the best predictors of photosynthetic variables. In addition, the amount of light available at sample depth significantly predicted both E k and Chl a : POC. Our results suggest that it is the balance between light and nutrient availability in the various environments encountered in the seasonal sea ice zone that result in the pattern of photo‐physiological data presented here. A significant proportion of primary production has now been observed to occur under the sea ice; therefore, our results may be a change from prior conditions in the region.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

The new sequencer on the block: comparison of Life Technology’s Proton sequencer to an Illumina HiSeq for whole-exome sequencing - Joseph F. Boland; Charles C. Chung; David Roberson; Jason Mitchell; Xijun Zhang; Kate M. Im; Ji He; Stephen J. Chanock; Meredith Yeager; Michael Dean (Human Genetics, 2013)

Methamphetamine and core temperature in the rat: Ambient temperature, dose, and the effect of a D2 receptor blocker - Karen E. Sabol; Danielle M. Yancey; H. Anton Speaker; Scott L. Mitchell (Psychopharmacology, 2013)

Linking Landscape Connectivity and Ecosystem Service Provision: Current Knowledge and Research Gaps - Matthew G. E. Mitchell; Elena M. Bennett; Andrew Gonzalez (Ecosystems, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Sewage reflects the distribution of human faecal L achnospiraceae - Sandra L. McLellan; Ryan J. Newton; Jessica L. Vandewalle; Orin C. Shanks; Susan M. Huse; A. Murat Eren; Mitchell L. Sogin (Environmental Microbiology, 2013)
Summary Faecal pollution contains a rich and diverse community of bacteria derived from animals and humans, many of which might serve as alternatives to the traditional enterococci and E scherichia coli faecal indicators. We used massively parallel sequencing ( MPS ) of the 16 S rRNA gene to characterize microbial communities from wastewater treatment plant ( WWTP ) influent sewage from 12 cities geographically distributed across the USA . We examined members of the C lostridiales , which included the families C lostridiaceae , L achnospiraceae and R uminococcaceae for their potential as sewage indicators. L achnospiraceae was one of the most abundant groups of faecal bacteria in sewage, and several L achnospiraceae high‐abundance sewage pyrotags occurred in at least 46 of 48 human faecal samples. Clone libraries targeting C lostridium coccoides ( C . coccoides ) in sewage samples demonstrated that Lachnospiraceae ‐annotated V 6 pyrotags encompassed the previously reported C . coccoides group. We used oligotyping to profile the genus B lautia within L achnospiraceae and found oligotypes comprised of 24 entropy components that showed patterns of host specificity. These findings suggest that indicators based on B lautia might have the capacity to discriminate between different faecal pollution sources. Development of source‐specific alternative indicators would enhance water quality assessments, which leads to improved ecosystem health and reduced human health risk due to waterborne disease.

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

The tolerance of Pinus patula × Pinus tecunumanii, and other pine hybrids, to Fusarium circinatum in greenhouse trials - R. G. Mitchell; M. J. Wingfield; G. R. Hodge; E. T. Steenkamp; T. A. Coutinho (New Forests, 2013)

Macroecological patterns of marine bacteria on a global scale - Anthony S. Amend; Tom A. Oliver; Linda A. Amaral‐Zettler; Antje Boetius; Jed A. Fuhrman; M. Claire Horner‐Devine; Susan M. Huse; David B. Mark Welch; Adam C. Martiny; Alban Ramette; Lucie Zinger; Mitchell L. Sogin; et al. (Journal of Biogeography, 2013)
Aim To test whether within‐species and among‐species patterns of abundance and latitudinal range in marine bacteria resemble those found for macro‐organisms, and whether these patterns differ along latitudinal clines. Location Global pelagic marine environments. Methods Taxon‐specific sequence abundance and location were retrieved from the open‐access V6‐ rRNA pyrotag sequence data base VAMPS ( http://vamps.mbl.edu/ ), which holds a massive collection of marine bacterial community data sets from the I nternational C ensus of M arine M icrobes sampling effort of global ocean water masses. Data were randomly subsampled to correct for spatial bias and for differences in sampling effort. Results We show that bacterial latitudinal ranges are narrower than expected by chance. When present in both N orthern and S outhern hemispheres, taxa occupy restricted ranges at similar latitudes on both sides of the equator. A significant and positive relationship exists between sequence abundance and latitudinal range, although this pattern contains a large amount of variance. Abundant taxa in the tropics and in the N orthern H emisphere generally have smaller ranges than those in the S outhern H emisphere. We show that the mean latitudinal range of bacterial taxa increases with latitude, supporting the existence of a R apoport effect in marine bacterioplankton. Finally, we show that bacterioplankton communities contain a higher proportion of abundant taxa as they approach the poles. Main conclusions Macroecological patterns such as the abundance–range relationship, in general, extend to marine bacteria. However, differences in the shape of these relationships between bacteria and macro‐organisms call into question whether the processes and their relative importance in shaping global marine bacteria and macro‐organism distributions are the same.

Effects of shade on growth, biomass allocation and leaf morphology in European yew (Taxus baccata L.) - Philip M. Perrin; Fraser J. G. Mitchell (European Journal of Forest Research, 2013)

Remucal et al. Respond: - Jonathan M. Remucal; Jason D. McGee; Matthew M. Fehrenbacher; Constance Best; Robert J. Mitchell (Journal of Forestry, 2013)

Good Cascade Impactor Practice (GCIP) and Considerations for “In-Use” Specifications - S. C. Nichols; J. P. Mitchell; C. M. Shelton; D. L. Roberts (AAPS PharmSciTech, 2013)

The Effect of Metal-Chelating Polymers (MCPs) for 111In Complexed via the Streptavidin-Biotin System to Trastuzumab Fab Fragments on Tumor and Normal Tissue Distribution in Mice - Amanda J. Boyle; Peng Liu; Yijie Lu; Dirk Weinrich; Deborah A. Scollard; Ghislaine Ngo Njock Mbong; Mitchell A. Winnik; Raymond M. Reilly (Pharmaceutical Research, 2013)

Susceptibility of provenances and families of Pinus maximinoi and Pinus tecunumanii to frost in South Africa - R. G. Mitchell; M. J. Wingfield; G. R. Hodge; W. S. Dvorak; T. A. Coutinho (New Forests, 2013)

Compositional variations and morphological evolution in platinum beach placers, southern New Zealand - D. Craw; M. Mitchell; R. McCann; A. Reay (Mineralium Deposita, 2013)

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Current state of knowledge regarding the world’s wetlands and their future under global climate change: a synthesis - Wolfgang J. Junk; Shuqing An; C. M. Finlayson; Brij Gopal; Jan Květ; Stephen A. Mitchell; William J. Mitsch; Richard D. Robarts (Aquatic Sciences, 2013)

Genetic markers of ovarian follicle number and menopause in women of multiple ethnicities - Sonya M. Schuh-Huerta; Nicholas A. Johnson; Mitchell P. Rosen; Barbara Sternfeld; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2012)

Multiple environmental stressors elicit complex interactive effects in the western fence lizard (Sceloporus occidentalis) - Craig A. McFarland; Larry G. Talent; Michael J. Quinn; Matthew A. Bazar; Mitchell S. Wilbanks; Mandana Nisanian; Robert M. Gogal; Mark S. Johnson; Edward J. Perkins; Kurt A. Gust (Ecotoxicology, 2012)

Understanding disparities in leukemia: a national study - M. I. Patel; Y. Ma; B. S. Mitchell; K. F. Rhoads (Cancer Causes & Control, 2012)

Varenicline decreases alcohol consumption in heavy-drinking smokers - Jennifer M. Mitchell; Candice H. Teague; Andrew S. Kayser; Selena E. Bartlett; Howard L. Fields (Psychopharmacology, 2012)

Seaweed Allelopathy Against Coral: Surface Distribution of a Seaweed Secondary Metabolite by Imaging Mass Spectrometry - Tiffany D. Andras; Troy S. Alexander; Asiri Gahlena; R. Mitchell Parry; Facundo M. Fernandez; Julia Kubanek; May D. Wang; Mark E. Hay (Journal of Chemical Ecology, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Behavioral inhibition in mice bred for high vs. low levels of methamphetamine consumption or sensitization - Travis M. Moschak; Katherine A. Stang; Tamara J. Phillips; Suzanne H. Mitchell (Psychopharmacology, 2012)

Selection of Pinus spp. in South Africa for tolerance to infection by the pitch canker fungus - R. G. Mitchell; M. J. Wingfield; G. R. Hodge; E. T. Steenkamp; T. A. Coutinho (New Forests, 2012)

Elemental composition of sediments in Lake Jinzai, Japan: Assessment of sources and pollution - Faruque Ahmed; M. Hawa Bibi; Takashi Asaeda; Carl P. J. Mitchell; Hiroaki Ishiga; Takehiko Fukushima (Environmental Monitoring and Assessment, 2012)

Overstory and understory vegetation interact to alter soil community composition and activity - Ruth Joy Mitchell; Adian M. Keith; Jackie M. Potts; Jasmine Ross; Eileen Reid; Lorna A. Dawson (Plant and Soil, 2012)

Explaining the variation in the soil microbial community: do vegetation composition and soil chemistry explain the same or different parts of the microbial variation? - Ruth Joy Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2012)

Characterisation of MHC haplotypes in a breeding colony of Indonesian cynomolgus macaques reveals a high level of diversity - Jane L. Mitchell; Edward T. Mee; Neil M. Almond; Keith Cutler; Nicola J. Rose (Immunogenetics, 2012)

Modelling the effect of size on the aerial dispersal of microorganisms - David M. Wilkinson; Symeon Koumoutsaris; Edward A. D. Mitchell; Isabelle Bey (Journal of Biogeography, 2012)
Aim We investigate the long‐standing question of whether the small size of microbes allows most microbial species to colonize all suitable sites around the globe or whether their ranges are limited by opportunities for dispersal. In this study we use a modelling approach to investigate the effect of size on the probability of between‐continent dispersal using virtual microorganisms in a global model of the Earth’s atmosphere. Location Global. Methods We use a computer model of global atmospheric circulation to investigate the effect of microbe size (effective diameters of 9, 20, 40 and 60 μm) on the probability of aerial dispersal. Results We found that for smaller microbes, once airborne, dispersal is remarkably successful over a 1‐year period. The most striking results are the extensive within‐hemisphere distribution of virtual microbes of 9 and 20 μm diameter and the lack of dispersal between the Northern and Southern Hemispheres during the year‐long time‐scale of our simulations. Main conclusions Above a diameter of 20 μm wind dispersal of virtual microbes between continents becomes increasingly unlikely, and it does not occur at all (within our simulated 1‐year period) for those of 60 μm diameter. Within our simulation, the success of small microbes in long‐distance dispersal is due both to their greater abundance and to their longer time in the atmosphere – once airborne – compared with larger microbes.

Effects of acute administration of nicotine, amphetamine, diazepam, morphine, and ethanol on risky decision-making in rats - Marci R. Mitchell; Colin M. Vokes; Amy L. Blankenship; Nicholas W. Simon; Barry Setlow (Psychopharmacology, 2011)

Fibrocyte-like cells recruited to the spleen support innate and adaptive immune responses to acute injury or infection - Tatiana Kisseleva; Maren von Köckritz-Blickwede; Donna Reichart; Shauna M. McGillvray; Gerhard Wingender; Mitchell Kronenberg; Christopher K. Glass; Victor Nizet; David A. Brenner (Journal of Molecular Medicine, 2011)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

Enzymatic digestion in stomachless fishes: how a simple gut accommodates both herbivory and carnivory - Ryan D. Day; Donovan P. German; Jennifer M. Manjakasy; Ingrid Farr; Mitchell Jay Hansen; Ian R. Tibbetts (Journal of Comparative Physiology B, 2011)

New Sex Pheromone Blend for the Lightbrown Apple Moth, Epiphyas postvittana - Ashraf M. El-Sayed; Vanessa J. Mitchell; Lee-Anne M. Manning; David Max Suckling (Journal of Chemical Ecology, 2011)

Histone H2A.Z acid patch residues required for deposition and function - Kurt Jensen; Maria Soledad Santisteban; Craig Urekar; M. Mitchell Smith (Molecular Genetics and Genomics, 2011)

Development of a multiplexed bead-based immunoassay for the simultaneous detection of antibodies to 17 pneumococcal proteins - S. Shoma; N. J. Verkaik; C. P. de Vogel; P. W. M. Hermans; S. van Selm; T. J. Mitchell; M. van Roosmalen; S. Hossain; M. Rahman; H. Ph. Endtz; W. J. B. van Wamel; A. van Belkum (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Postdiagnosis diet quality, the combination of diet quality and recreational physical activity, and prognosis after early-stage breast cancer - Stephanie M. George; Melinda L. Irwin; Ashley W. Smith; Marian L. Neuhouser; Jill Reedy; Anne McTiernan; Catherine M. Alfano; Leslie Bernstein; Cornelia M. Ulrich; Kathy B. Baumgartner; Steven C. Moore; Demetrius Albanes; et al. (Cancer Causes & Control, 2011)

Differential involvement of hippocampal serotonin1A receptors and re-uptake sites in non-cognitive behaviors of Alzheimer’s disease - Mitchell K. P. Lai; Shirley W. Tsang; Margaret M. Esiri; Paul T. Francis; Peter T.-H. Wong; Christopher P. Chen (Psychopharmacology, 2011)

Improvements in Urban Air Quality: Case Studies from New York State, USA - Shannon M. Buckley; Myron J. Mitchell (Water, Air, & Soil Pollution, 2011)

Role of the atmospheric mean state on the initiation of the Madden-Julian oscillation in a tropical channel model - Pallav Ray; Chidong Zhang; Mitchell W. Moncrieff; Jim Dudhia; Julie M. Caron; L. Ruby Leung; Cindy Bruyere (Climate Dynamics, 2011)

Soil Fungi Respond More Strongly than Fine Roots to Elevated CO2 in a Model Regenerating Longleaf Pine-Wiregrass Ecosystem - M. Luke McCormack; Seth G. Pritchard; Sabrie Breland; Michael A. Davis; Stephen A. Prior; G. Brett Runion; Robert J. Mitchell; Hugo H. Rogers (Ecosystems, 2010)

Minimally invasive assessment of tumor angiogenesis by fine needle aspiration and flow cytometry - Joseph L. Sottnik; Amanda M. Guth; Leah A. Mitchell; Steven W. Dow (Angiogenesis, 2010)

Winter climate change implications for decomposition in northeastern forests: comparisons of sugar maple litter with herbivore fecal inputs - LYNN M. CHRISTENSON; MYLON J. MITCHELL; PETER M. GROFFMAN; GARY M. LOVETT (Global Change Biology, 2010)
Forests in northeastern North America are influenced by varying climatic and biotic factors; however, there is concern that rapid changes in these factors may lead to important changes in ecosystem processes such as decomposition. Climate change (especially warming) is predicted to increase rates of decomposition in northern latitudes. Warming in winter may result in complex effects including decreased levels of snow cover and an increased incidence of soil freezing that will effect decomposition. Along with these changes in climate, moose densities have also been increasing in this region, likely affecting nutrient dynamics. We measured decomposition and N release from 15 N‐labeled sugar maple leaf litter and moose feces over 20 months in reference and snow removal treatment (to induce soil freezing) plots in two separate experiments at the Hubbard Brook Experimental Forest in New Hampshire, USA. Snow removal/soil freezing decreased decomposition of maple litter, but stimulated N transfer to soil and microbial biomass. Feces decomposed more rapidly than maple litter, and feces N moved into the mineral soil more than N derived from litter, likely due to the lower C : N ratio of feces. Feces decomposition was not affected by the snow removal treatment. Total microbial biomass (measured as microbial N and C) was not significantly affected by the treatments in either the litter or feces plots. These results suggest that increases in soil freezing and/or large herbivore populations, increase the transfer rate of N from plant detritus or digested plants into the mineral soil. Such changes suggest that altering the spatial and temporal patterns of soil freezing and moose density have important implications for ecosystem N cycling.

Effects of chronic and intermittent cocaine treatment on dominance, aggression, and oxytocin levels in post-lactational rats - Josephine M. Johns; Matthew S. McMurray; Paul W. Joyner; Thomas M. Jarrett; Sarah K. Williams; Elizabeth T. Cox; Mitchell A. Black; Christopher L. Middleton; Cheryl H. Walker (Psychopharmacology, 2010)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Is vegetation composition or soil chemistry the best predictor of the soil microbial community? - Ruth J. Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Ironing out the wrinkles in the rare biosphere through improved OTU clustering - Susan M. Huse; David Mark Welch; Hilary G. Morrison; Mitchell L. Sogin (Environmental Microbiology, 2010)
Summary Deep sequencing of PCR amplicon libraries facilitates the detection of low‐abundance populations in environmental DNA surveys of complex microbial communities. At the same time, deep sequencing can lead to overestimates of microbial diversity through the generation of low‐frequency, error‐prone reads. Even with sequencing error rates below 0.005 per nucleotide position, the common method of generating operational taxonomic units (OTUs) by multiple sequence alignment and complete‐linkage clustering significantly increases the number of predicted OTUs and inflates richness estimates. We show that a 2% single‐linkage preclustering methodology followed by an average‐linkage clustering based on pairwise alignments more accurately predicts expected OTUs in both single and pooled template preparations of known taxonomic composition. This new clustering method can reduce the OTU richness in environmental samples by as much as 30–60% but does not reduce the fraction of OTUs in long‐tailed rank abundance curves that defines the rare biosphere.

Moderate Ethanol Preconditioning of Rat Brain Cultures Engenders Neuroprotection Against Dementia-Inducing Neuroinflammatory Proteins: Possible Signaling Mechanisms - Michael A. Collins; Edward J. Neafsey; Kewei Wang; Nicholas J. Achille; Robert M. Mitchell; Sreevidya Sivaswamy (Molecular Neurobiology, 2010)

Spatial and Temporal Effects on Switchgrass Stands and Yield in the Great Plains - M. R. Schmer; R. B. Mitchell; K. P. Vogel; W. H. Schacht; D.B. Marx (BioEnergy Research, 2010)

Short-term endurance training does not alter the oxidative capacity of human subcutaneous adipose tissue - Donny M. Camera; Mitchell J. Anderson; John A. Hawley; Andrew L. Carey (European Journal of Applied Physiology, 2010)

Second Harmonic Generation Imaging and Fourier Transform Spectral Analysis Reveal Damage in Fatigue-Loaded Tendons - David T. Fung; Jedd B. Sereysky; Jelena Basta-Pljakic; Damien M. Laudier; Rumana Huq; Karl J. Jepsen; Mitchell B. Schaffler; Evan L. Flatow (Annals of Biomedical Engineering, 2010)

Testate amoeba analysis of lake sediments: impact of filter size and total count on estimates of density, species richness and assemblage structure - A. A. J. Wall; D. Gilbert; M. Magny; E. A. D. Mitchell (Journal of Paleolimnology, 2010)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Long-term effect of re-vegetation on the microbial community of a severely eroded soil in sub-tropical China - Huan Deng; Bin Zhang; Rui Yin; Hui-li Wang; Susan M. Mitchell; Bryan S. Griffiths; Timothy John Daniell (Plant and Soil, 2010)

Natural Variation of Flowering Time and Vernalization Responsiveness in Brachypodium distachyon - Christopher J. Schwartz; Mark R. Doyle; Antonio J. Manzaneda; Pedro J. Rey; Thomas Mitchell-Olds; Richard M. Amasino (BioEnergy Research, 2010)

Efficacy of exclusion fencing to protect ephemeral floodplain lagoon habitats from feral pigs (Sus scrofa) - Robert G. Doupé; Jim Mitchell; Matthew J. Knott; Aaron M. Davis; Alan J. Lymbery (Wetlands Ecology and Management, 2010)

Sustained Release of Multiple Growth Factors from Injectable Polymeric System as a Novel Therapeutic Approach Towards Angiogenesis - Qinghua Sun; Eduardo A Silva; Aixia Wang; James C. Fritton; David J. Mooney; Mitchell B. Schaffler; Paul M. Grossman; Sanjay Rajagopalan (Pharmaceutical Research, 2010)

Glucokinase regulatory protein gene polymorphism affects postprandial lipemic response in a dietary intervention study - Haiqing Shen; Toni I. Pollin; Coleen M. Damcott; John C. McLenithan; Braxton D. Mitchell; Alan R. Shuldiner (Human Genetics, 2009)

Nodulation of Sesbania species by Rhizobium ( Agrobacterium ) strain IRBG74 and other rhizobia - Stephen P. Cummings; Prasad Gyaneshwar; Pablo Vinuesa; Frank T. Farruggia; Mitchell Andrews; David Humphry; Geoffrey N. Elliott; Andrew Nelson; Caroline Orr; Deborah Pettitt; Gopit R. Shah; Scott R. Santos; et al. (Environmental Microbiology, 2009)
Summary Concatenated sequence analysis with 16S rRNA, rpoB and fusA genes identified a bacterial strain (IRBG74) isolated from root nodules of the aquatic legume Sesbania cannabina as a close relative of the plant pathogen Rhizobium radiobacter (syn. Agrobacterium tumefaciens ). However, DNA:DNA hybridization with R. radiobacter , R. rubi , R. vitis and R. huautlense gave only 44%, 5%, 8% and 8% similarity respectively, suggesting that IRBG74 is potentially a new species. Additionally, it contained no vir genes and lacked tumour‐forming ability, but harboured a sym ‐plasmid containing nifH and nodA genes similar to those in other Sesbania symbionts. Indeed, IRBG74 effectively nodulated S. cannabina and seven other Sesbania spp. that nodulate with Ensifer ( Sinorhizobium )/ Rhizobium strains with similar nodA genes to IRBG74, but not species that nodulate with Azorhizobium or Mesorhizobium . Light and electron microscopy revealed that IRBG74 infected Sesbania spp. via lateral root junctions under flooded conditions, but via root hairs under non‐flooded conditions. Thus, IRBG74 is the first confirmed legume‐nodulating symbiont from the Rhizobium ( Agrobacterium ) clade. Cross‐inoculation studies with various Sesbania symbionts showed that S. cannabina could form fully effective symbioses with strains in the genera Rhizobium and Ensifer , only ineffective ones with Azorhizobium strains, and either partially effective ( Mesorhizobium huakii ) or ineffective ( Mesorhizobium plurifarium ) symbioses with Mesorhizobium . These data are discussed in terms of the molecular phylogeny of Sesbania and its symbionts.

Eustrongylides ignotus infecting commercial bass, Morone chrysops female X Morone saxatilis male, and other fish in the southeastern USA - A J Mitchell; R M Overstreet; A E Goodwin (Journal of Fish Diseases, 2009)

A pilot study on iodine in soils of Greater Kabul and Nangarhar provinces of Afghanistan - M. J. Watts; C. J. Mitchell (Environmental Geochemistry and Health, 2009)

Global irrigated area map (GIAM), derived from remote sensing, for the end of the last millennium - Prasad S. Thenkabail; Chandrashekhar M. Biradar; Praveen Noojipady; Venkateswarlu Dheeravath; Yuanjie Li; Manohar Velpuri; Muralikrishna Gumma; Obi Reddy P. Gangalakunta; Hugh Turral; Xueliang Cai; Jagath Vithanage; Mitchell A. Schull; et al. (International Journal of Remote Sensing, 2009)

Woody plant encroachment impacts on soil carbon and microbial processes: results from a hierarchical Bayesian analysis of soil incubation data - Jessica M. Cable; Kiona Ogle; Anna P. Tyler; Mitchell A. Pavao-Zuckerman; Travis E. Huxman (Plant and Soil, 2009)

Attraction of New Zealand Flower Thrips, Thrips obscuratus, to cis-Jasmone, a Volatile Identified from Japanese Honeysuckle Flowers - A. M. El-Sayed; V. J. Mitchell; G. F. McLaren; L. M. Manning; B. Bunn; D. M. Suckling (Journal of Chemical Ecology, 2009)

Evaluation of diquat against an acute experimental infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus (Rafinesque) - A M Darwish; A J Mitchell (Journal of Fish Diseases, 2009)
A trial was performed to evaluate the efficacy of diquat (6,7‐dihydrodipyrido[1,2‐a:2′,1′‐c]pyrazinediium dibromide) against an acute experimental infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus . Diquat is an Environmental Protection Agency‐approved herbicide and has the potential to be legally and practically used against columnaris. Channel catfish were challenged, by cutaneous abrasion, and waterborne exposure to F. columnare and treated once at 22‐h post‐challenge with 2.5, 5.0, 10.0 and 15 mg L −1 of diquat active ingredient for 6 h. At the conclusion of the trial, 21‐day post‐challenge, diquat at 5.0, 10.0 and 15 mg L −1 significantly ( P In vitro , the minimum inhibitory concentration (MIC) of 23 isolates of F. columnare was assayed. The majority of the isolates had an MIC value of 5 μg mL −1 (15 of the 23 isolates). Infected fish exhibited acute clinical signs similar to a natural infection. The skin had severe ulcerative necrotizing dermatitis and the muscles had severe necrotizing myositis. The gills had severe multifocal necrotizing branchitis. The results demonstrate that diquat would reduce mortalities caused by an acute columnaris infection.

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

The Abbreviated Impactor Measurement (AIM) Concept: Part II—Influence of Evaporation of a Volatile Component—Evaluation with a “Droplet-Producing” Pressurized Metered Dose Inhaler (pMDI)-Based Formulation Containing Ethanol as Cosolvent - J. P. Mitchell; M. W. Nagel; V. Avvakoumova; H. MacKay; R. Ali (AAPS PharmSciTech, 2009)

The Abbreviated Impactor Measurement (AIM) Concept: Part 1—Influence of Particle Bounce and Re-Entrainment—Evaluation with a “Dry” Pressurized Metered Dose Inhaler (pMDI)-Based Formulation - J. P. Mitchell; M. W. Nagel; V. Avvakoumova; H. MacKay; R. Ali (AAPS PharmSciTech, 2009)

Phylogenetic relationships of Geranium species indigenous to New Zealand - A. D. Mitchell; P. B. Heenan; A. M. Paterson (New Zealand Journal of Botany, 2009)
New Zealand species of Geranium are shown to be closely related, forming a monophyletic group. Relationships inferred from Bayesian and NeighborNet analyses of internal and external transcribed spacer sequences generally agreed and were congruent with those inferred from study of morphological characters. Two groups of species (G. brevicaule and G. retrorsum groups) are well supported based on morphology and DNA sequence data. A third group, referred to as the G. microphyllum group, is recognised based on morphology but is only partially supported by the DNA sequence data. The DNA sequence and morphological variability in each of the G. brevicaule, G. microphyllum , and G. retrorsum groups support the recognition of additional taxonomic entities from New Zealand, but further study is required to address these issues. Furthermore, additional sampling of Australian and South American species of Geranium must be carried out before a taxonomic re‐evaluation can be made of sections Andina and Chilensia .

Leaf morphological responses to variation in water availability for plants in the Piriqueta caroliniana complex - Joshua J. Picotte; Jennifer M. Rhode; Mitchell B. Cruzan (Plant Ecology, 2009)

Evaluation of potassium permanganate against an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus (Rafinesque) - A M Darwish; A J Mitchell; D L Straus (Journal of Fish Diseases, 2009)
An experiment was performed to evaluate the efficacy of potassium permanganate (KMnO 4 ) as a prophylactic and therapeutic treatment of an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus . Fish were cutaneously abraded and divided into five treatment groups: (i) challenged by waterborne exposure to F. columnare and not treated with KMnO 4 (positive control), (ii) challenged and simultaneously treated with KMnO 4, (iii) challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge, (iv) not challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge (first negative control) and (v) not challenged and not treated (second negative control). The dosing of KMnO 4 was 2.0 mg L −1 above the potassium permanganate demand for 2 h duration. The survival of the group challenged and simultaneously treated with KMnO 4 (99%) was significantly higher than the positive control (78%) and was not significantly different from the negative control groups. The challenged fish treated with KMnO 4 post‐challenge had 7% higher survival than the positive control (85% compared with 78%), but that difference was not statistically significant. The results demonstrate that KMnO 4 has a clear prophylactic value but probably a marginal therapeutic value once the infection has established.

Cascade genetic testing for mismatch repair gene mutations - R. J. Mitchell; R. K. Ferguson; A. Macdonald; M. G. Dunlop; H. Campbell; M. E. Porteous (Familial Cancer, 2008)

Switchgrass Biomass Simulation at Diverse Sites in the Northern Great Plains of the U.S. - J. R. Kiniry; M. R. Schmer; K. P. Vogel; R. B. Mitchell (BioEnergy Research, 2008)

Soil Carbon Storage by Switchgrass Grown for Bioenergy - M. A. Liebig; M. R. Schmer; K. P. Vogel; R. B. Mitchell (BioEnergy Research, 2008)

Increased nitric oxide synthase activity and Hsp90 association in skeletal muscle following chronic exercise - M. Brennan Harris; Brett M. Mitchell; Sarika G. Sood; R. Clinton Webb; Richard C. Venema (European Journal of Applied Physiology, 2008)

Evidence for multiple sources of invasion and intraspecific hybridization in Brachypodium sylvaticum (Hudson) Beauv. in North America - DAVID M. ROSENTHAL; ALISA P. RAMAKRISHNAN; MITCHELL B. CRUZAN (Molecular Ecology, 2008)
We compared the levels and distribution of genetic diversity in Eurasian and North American populations of Brachypodium sylvaticum (Huds.) Beauv. (false brome), a newly invasive perennial bunchgrass in western North America. Our goals were to identify source regions for invasive populations, determine the number of independent invasion events, and assess the possibility that postinvasion bottlenecks and hybridization have affected patterns of genetic diversity in the invaded range. We tested the hypothesis that this Eurasian grass was accidentally introduced into two areas in Oregon and one site in California by examining nuclear microsatellites and chloroplast haplotype variation in 23 introduced and 25 native populations. In the invaded range, there was significantly lower allelic richness ( R S ), observed heterozygosity ( H O ) and within‐population gene diversity ( H S ), although a formal test failed to detect a significant genetic bottleneck. Most of the genetic variation existed among populations in the native range but within populations in the invaded range. All of the allelic variation in the invaded range could be explained based on alleles found in western European populations. The distribution of identified genetic clusters in the North American populations and the unique alleles associated with them is consistent with two historical introductions in Oregon and a separate introduction to California. Further analyses of population structure indicate that intraspecific hybridization among genotypes from geographically distinct regions of western Europe occurred following colonization in Oregon. The California populations, however, are more likely to be derived from one or perhaps several genetically similar regions in the native range. The emergence and spread of novel recombinant genotypes may be facilitating the rapid spread of this invasive species in Oregon.

Progress in assessing the impact of Fusarium head blight on oat in western Canada and screening of avena germplasm for resistance - A. Tekauz; J. Mitchell Fetch; B. Rossnagel; M. Savard (Cereal Research Communications, 2008)

Regional-scale models for relating land cover to basin surface-water quality using remotely sensed data in a GIS - V. L. Versace; D. Ierodiaconou; F. Stagnitti; A. J. Hamilton; M. T. Walter; B. Mitchell; A.-M. Boland (Environmental Monitoring and Assessment, 2008)

An insertion/deletion polymorphism of the dihydrofolate reductase (DHFR) gene is associated with serum and red blood cell folate concentrations in women - Anna Stanisławska-Sachadyn; Karen S. Brown; Laura E. Mitchell; Jayne V. Woodside; Ian S. Young; John M. Scott; Liam Murray; Colin A. Boreham; Helene McNulty; J. J. Strain; Alexander S. Whitehead (Human Genetics, 2008)

Biosynthesis of Dibenzyl Trisulfide (DTS) from somatic embryos and rhizogenous/embryogenic callus derived from Guinea hen weed (Petiveria alliacea L.) leaf explants - S. A. Webster; S. A. Mitchell; W. A. Gallimore; L. A. D. Williams; M. H. Ahmad (In Vitro Cellular & Developmental Biology - Plant, 2008)

Stand-Level Forest Structure and Avian Habitat: Scale Dependencies in Predicting Occurrence in a Heterogeneous Forest - Katherine Manaras Smith; William S. Keeton; Therese M. Donovan; Brian Mitchell (Forest Science, 2008)
We explored the role of stand-level forest structure and spatial extent of forest sampling in models of avian occurrence in northern hardwood-conifer forests for two species: black-throated blue warbler (Dendroica caerulescens) and ovenbird (Seiurus aurocapillus). We estimated site occupancy from point counts at 20 sites and characterized the forest structure at these sites at three spatial extents (0.2, 3.0, and 12.0 ha). Weight of evidence was greatest for habitat models using forest stand structure at the 12.0-ha extent and diminished only slightly at the 3.0-ha extent, a scale that was slightly larger than the average territory size of both species. Habitat models characterized at the 0.2-ha extent had low support, yet are the closest in design to those used in many of the habitat studies we reviewed. These results suggest that the role of stand-level vegetation may have been underestimated in the past, which will be of interest to land managers who use habitat models to assess the suitability of habitat for species of concern.

Gene-environment interactions in a mutant mouse kindred with native airway constrictor hyperresponsiveness - Lawrence H. Pinto; Emily Eaton; Bohao Chen; Jonah Fleisher; Dmitry Shuster; Joel McCauley; Dalius Kedainis; Sandra M. Siepka; Kazuhiro Shimomura; Eun-Joo Song; Aliya Husain; Oren J. Lakser; et al. (Mammalian Genome, 2008)

A powder neutron diffraction study of the crystal structure of the fluoroperovskite NaMgF3 (neighborite) from 300 to 3.6 K - Roger H. Mitchell; Malcolm Alexander; Lachlan M. D. Cranswick; Ian P. Swainson (Physics and Chemistry of Minerals, 2007)

Iron limitation across chlorophyll gradients in the southern Drake Passage: Phytoplankton responses to iron addition and photosynthetic indicators of iron stress - Brian M. Hopkinson; B. Greg Mitchell; Rick A. Reynolds; Haili Wang; Karen E. Selph; Christopher I. Measures; Christopher D. Hewes; Osmund Holm-Hansen; Katherine A. Barbeau (Limnology and Oceanography, 2007)
Processes influencing phytoplankton bloom development in the southern Drake Passage were studied using shipboard iron‐enrichment incubations conducted across a surface chlorophyll gradient near the Antarctic Peninsula, in a region of water mass mixing. Iron incubation assays showed that Antarctic Circumpolar Current (ACC) waters were severely iron limited, while shelf waters with high ambient iron concentrations (1–2 nmol L −1 ) were iron replete, demonstrating that mixing of the two water masses is a plausible mechanism for generation of the high phytoplankton biomass observed downstream of the Antarctic Peninsula. In downstream highchlorophyll mixed waters, phytoplankton growth rates were also iron limited, although responses to iron addition were generally more moderate as compared to ACC waters. Synthesizing results from all experiments, significant correlations were found between the initial measurements of Photosystem II (PSII) parameters ( F v :F m , σ PSII , and p ) and the subsequent responses of these waters to iron addition. These correlations indicate that PSII parameters can be used to assess the degree of iron stress experienced in these waters and likely in other regions where photoinhibition and nitrogen stress are not confounding factors.

Purification and characterization of rhodobactin: a mixed ligand siderophore from Rhodococcus rhodochrous strain OFS - Suraj Dhungana; Ryszard Michalczyk; Hakim Boukhalfa; Joseph G. Lack; Andrew T. Koppisch; Jason M. Fairlee; Mitchell T. Johnson; Christy E. Ruggiero; Seth G. John; Matthew M. Cox; Cindy C. Browder; Jennifer H. Forsythe; et al. (BioMetals, 2007)

Plastic responses to temporal variation in moisture availability: consequences for water use efficiency and plant performance - Joshua J. Picotte; David M. Rosenthal; Jennifer M. Rhode; Mitchell B. Cruzan (Oecologia, 2007)

The Keylong Serai rock avalanche, NW Indian Himalaya: geomorphology and palaeoseismic implications - W. A. Mitchell; M. J. McSaveney; A. Zondervan; K. Kim; S. A. Dunning; P. J. Taylor (Landslides, 2007)

Transport of heterologous proteins to the periplasmic space of Pseudomonas fluorescens using a variety of native signal sequences - Diane M. Retallack; J. Carrie Schneider; Jon Mitchell; Lawrence Chew; Huizhu Liu (Biotechnology Letters, 2007)

Developing habitat models for waterbirds in urban wetlands: a log-linear approach - Cheryl M. Pearce; Milford B. Green; Mitchell R. Baldwin (Urban Ecosystems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reactive oxygen species, ABA and nitric oxide interactions on the germination of warm-season C4-grasses - Gautam Sarath; Guichuan Hou; Lisa M. Baird; Robert B. Mitchell (Planta, 2007)

Peat erosion and atmospheric deposition impacts on an oligotrophic lake in eastern Ireland - M. Leira; E. E. Cole; F. J. G. Mitchell (Journal of Paleolimnology, 2007)

Stereo cloud‐top heights and cloud fraction retrieval from ATSR‐2 - J.‐P. Muller; M.‐A. Denis; R. D. Dundas; K. L. Mitchell; C. Naud; H. Mannstein (International Journal of Remote Sensing, 2007)

Sex differences in the potency of κ opioids and mixed-action opioids administered systemically and at the site of inflammation against capsaicin-induced hyperalgesia in rats - Lisa M. Lomas; Andrew C. Barrett; Jolan M. Terner; Donald T. Lysle; Mitchell J. Picker (Psychopharmacology, 2007)

Phylogenetic assignment and mechanism of action of a crop growth promoting Rhizobium radiobacter strain used as a biofertiliser on graminaceous crops in Russia - David R. Humphry; Mitchell Andrews; Scott R. Santos; Euan K. James; Lioubov V. Vinogradova; Liamara Perin; Veronica M. Reis; Stephen P. Cummings (Antonie van Leeuwenhoek, 2007)

Phylogeny of Bonatea (Orchidaceae: Habenariinae) based on molecular and morphological data - M. E. Ponsie; A. Mitchell; T. J. Edwards; S. D. Johnson (Plant Systematics and Evolution, 2007)

Quantifying anthropogenic influence on recent near-surface temperature change - M. R. Allen; N. P. Gillett; J. A. Kettleborough; G. Hegerl; R. Schnur; P. A. Stott; G. Boer; C. Covey; T. L. Delworth; G. S. Jones; J. F. B. Mitchell; T. P. Barnett (Surveys in Geophysics, 2006)

Neutron diffraction determination of the cell dimensions and thermal expansion of the fluoroperovskite KMgF3 from 293 to 3.6 K - Roger H. Mitchell; Lachlan M. D. Cranswick; Ian Swainson (Physics and Chemistry of Minerals, 2006)

Metabolic analysis of mouse brains that have compromised iron storage - Amanda M. Ill; Todd R. Mitchell; Elizabeth B. Neely; James R. Connor (Metabolic Brain Disease, 2006)

Plastid genome characterisation in Brassica and Brassicaceae using a new set of nine SSRs - M. L. Flannery; F. J. G. Mitchell; S. Coyne; T. A. Kavanagh; J. I. Burke; N. Salamin; P. Dowding; T. R. Hodkinson (Theoretical and Applied Genetics, 2006)

Impact of strain and d-amphetamine on impulsivity (delay discounting) in inbred mice - Christa M. Helms; Jamie M. Reeves; Suzanne H. Mitchell (Psychopharmacology, 2006)

Stimulation of an α1-adrenergic receptor downregulates ecto-5′ nucleotidase activity on the apical membrane of RPE cells - David Reigada; Xiulan Zhang; Ana Crespo; Johnathan Nguyen; Ji Liu; Klara Pendrak; Richard A. Stone; Alan M. Laties; Claire Mitchell (Purinergic Signalling, 2006)

Somatic embryogenesis from leaf and zygotic embryo explants of Blighia sapida ‘Cheese’ ackee - S. A. Webster; S. A. Mitchell; W. A. Reid; M. H. Ahmad (In Vitro Cellular & Developmental Biology - Plant, 2006)

The short-term effects of salinization on anaerobic nutrient cycling and microbial community structure in sediment from a freshwater wetland - Darren S. Baldwin; Gavin N. Rees; Alison M. Mitchell; Garth Watson; Janice Williams (Wetlands, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Nitric oxide accelerates seed germination in warm-season grasses - Gautam Sarath; Paul C. Bethke; Russell Jones; Lisa M. Baird; Guichuan Hou; Robert B. Mitchell (Planta, 2006)

Building and Maintaining Successful Relationships between Reservation and University Programs: Summer School Experiences on the White Earth Reservation - Charles R. Blinn; Deborah M. Zak; Mitchell Vogt (Journal of Forestry, 2006)
Building and maintaining successful relationships between Indian reservations and University faculty create opportunities to improve educational outcomes for American Indian students and increase the diversity of young people who consider attending college. The University of Minnesota and the White Earth Reservation developed an ongoing, outdoor-based summer school program on the Reservation, which has been successful in a number of ways. Factors to consider in the development and maintenance of such a cross-cultural program are presented.

Variants in Deleted in AZoospermia-Like (DAZL) are correlated with reproductive parameters in men and women - Joyce Y. Tung; Mitchell P. Rosen; Lawrence M. Nelson; Paul J. Turek; John S. Witte; Daniel W. Cramer; Marcelle I. Cedars; Renee A. Reijo Pera (Human Genetics, 2006)

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Diversity in the sunflower: Puccinia helianthi pathosystem in Australia - B. C. Sendall; G. A. Kong; K. C. Goulter; E. A. B. Aitken; S. M. Thompson; J. H. M. Mitchell; J. K. Kochman; W. Lawson; T. Shatte; T. J. Gulya (Australasian Plant Pathology, 2006)

An oral carcinogenicity and toxicity study of senna (Tinnevelly senna fruits) in the rat - J. M. Mitchell; U. Mengs; S. McPherson; J. Zijlstra; P. Dettmar; R. Gregson; J. C. Tigner (Archives of Toxicology, 2006)

Variation in the coat protein sequence of British isolates of Turnip yellow mosaic virus and comparison with previously published isolates - E. J. Mitchell; J. M. Bond (Archives of Virology, 2005)

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

Analysis of expressed sequence tags and the identification of associated short tandem repeats in switchgrass - Christian M. Tobias; Paul Twigg; Daniel M. Hayden; Kenneth P. Vogel; Rob M. Mitchell; Gerard R. Lazo; Elaine K. Chow; Gautam Sarath (Theoretical and Applied Genetics, 2005)

Identification of mutations from phenotype-driven ENU mutagenesis in mouse Chromosome 7 - Cymbeline T. Culiat; Mitchell L. Klebig; Zhaowei Liu; Heidi Monroe; Beverly Stanford; Jayashree Desai; Samvit Tandan; Lori Hughes; Marilyn K. Kerley; Donald A. Carpenter; Dabney K. Johnson; Eugene M. Rinchik; et al. (Mammalian Genome, 2005)

Host Blood Proteins and Peptides in the Midgut of the Tick Dermacentor variabilis Contributeto Bacterial Control - Daniel E. Sonenshine; Wayne L. Hynes; Shane M. Ceraul; Robert Mitchell; Tiffany Benzine (Experimental and Applied Acarology, 2005)

Diversity and selection in sorghum: simultaneous analyses using simple sequence repeats - A. M. Casa; S. E. Mitchell; M. T. Hamblin; H. Sun; J. E. Bowers; A. H. Paterson; C. F. Aquadro; S. Kresovich (Theoretical and Applied Genetics, 2005)

Behavioral assessment of temporal summation in the rat: sensitivity to sex, opioids and modulation by NMDA receptor antagonists - Lisa M. Lomas; Mitchell J. Picker (Psychopharmacology, 2005)

Recovery of saccadic dysmetria following localized lesions in monkey superior colliculus - Doug P. Hanes; Mitchell K. Smith; Lance M. Optican; Robert H. Wurtz (Experimental Brain Research, 2005)

Depositional and post‐depositional history of warm stage deposits at Knocknacran, Co. Monaghan, Ireland: implications for preservation of Irish last interglacial deposits - A. P. M. Vaughan; L. A. Dowling; F. J. G. Mitchell; S.‐E. Lauritzen; A. M. McCabe; P. Coxon (Journal of Quaternary Science, 2004)
Organic‐rich deposits, uncovered during overburden removal from mantled gypsum karst at Knocknacran opencast gypsum mine, Co. Monaghan, are the best candidate to date for a last interglacial record in Ireland. The two till and organic‐rich deposits (preserved at different quarry elevations) were emplaced on to a Tertiary dolerite surface during high‐energy flood events and subsequently folded and faulted by movement towards sinkholes in underlying gypsum. Uranium–thorium disequilibrium dating suggests that the organic‐rich deposits in the upper section were hydrologically isolated at ca. 41 ka and those in the lower section at ca. 86 ka. Interpretation of the pollen content, although tentative because of the depositional and post‐depositional history of the material, suggests that the organic material originated in a warm stage possibly warmer than the post‐Eemian interstadials. The unusual setting of preservation may indicate that in situ , last interglacial deposits have generally been removed by erosion in Ireland. Copyright © 2004 John Wiley & Sons, Ltd.

Estimating Spatial Patterns of Effluent Exposure Concentrations in Direct Toxicity Assessment Studies - Andrew E. Girling; Andrew M. Riddle; George M. Mitchell; Philip K. Chown; Derek Tinsley; Clare Buckler; Ian Johnson; Rachel Benstead (Ecotoxicology, 2004)

Antidepressant-like effects of the nociceptin/orphanin FQ receptor antagonist UFP-101: new evidence from rats and mice - E. C. Gavioli; C. W. Vaughan; G. Marzola; R. Guerrini; V. A. Mitchell; S. Zucchini; T. C. M. De Lima; G. A. Rae; S. Salvadori; D. Regoli; G. Calo’ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

TSPY, the Candidate Gonadoblastoma Gene on the Human Y Chromosome, has a Widely Expressed Homologue on the X - Implications for Y Chromosome Evolution - Margaret L. Delbridge; Guy Longepied; Danielle Depetris; Marie-Genevieve Mattei; Christine M. Disteche; Jennifer A. Marshall Graves; Michael J. Mitchell (Chromosome Research, 2004)

Microsatellite identification and characterization in peanut (A. hypogaea L.) - M. E. Ferguson; M. D. Burow; S. R. Schulze; P. J. Bramel; A. H. Paterson; S. Kresovich; S. Mitchell (Theoretical and Applied Genetics, 2004)

Uptake of nitrogen by rice studied with a 15N point-placement technique - J.E. Sheehy; M. Mnzava; K.G. Cassman; P.L. Mitchell; P. Pablico; R.P. Robles; A. Ferrer (Plant and Soil, 2004)

p16 Expression in Squamous Lesions of the Female Genital Tract - Mary M. Finegan; Aaron C. Han; Mitchell I. Edelson; Norman G. Rosenblum (Journal of Molecular Histology, 2004)

Extensive chloroplast haplotype variation indicates Pleistocene hybridization and radiation of North American Arabis drummondii , A. × divaricarpa , and A. holboellii (Brassicaceae) - C. H. Dobeš; T. Mitchell‐Olds; M. A. Koch (Molecular Ecology, 2004)
Arabis drummondii , A. holboellii and their hybrid A. × divaricarpa are widespread perennials of open habitats in North America. A phylogenetic analysis based on noncoding chloroplast DNA sequences ( trn L intron and trn L/F intergenic spacer) resolved A. drummondii as a monophyletic taxon, but found A. holboellii to bear chloroplast haplotypes from highly diverged evolutionary lineages. This raised the question of a possible polyphyletic origin of A. holboellii . Arabis × divaricarpa was found to be of recent and polytopic origin, a result consistent with its presumed hybrid origin. One hundred and three chloroplast haplotypes were detected within 719 Arabis accessions investigated. The majority of chloroplast‐types were estimated to have arisen prior to the Wisconsin glaciation. Phylogeographical analysis using nested clade analysis, suggested for A. holboellii (i) past fragmentation events, partitioning genetic variation in several instances between the Sierra Nevada, the Southern Rocky Mountains and the Colorado Plateau on the one hand and the Central to Northern Rockies of the United States and adjacent Cascades on the other; and for both parental species (ii) recolonization of major areas formerly covered by the Wisconsin glaciation by three haplotypes; and (iii) restricted gene flow indicating isolation by distance in areas south of the last glacial maximum. Arabis × divaricarpa is closely codistributed with its parental species and resampled their haplotypes. The highest genetic diversity was found in the Rocky Mountains from Idaho and Montana south to Utah and Colorado. This area was further hypothesized to have played a major role in the origin of both parental species and probably represented an important glacial refugium. However, evidence for glacial refugia was also found in arctic and boreal regions of Alaska and near the Great Lakes. In comparison to nuclear ribosomal internal transcribed spacer data, chloroplast DNA divergence was very high and evidently predated the origin of A. drummondii and possibly A. holboellii . Divergence of major chloroplast lineages dates back to the middle of the Pleistocene at least. Extensive hybridization is the most likely evolutionary factor working on A. holboellii to explain the revealed discrepancy in nuclear DNA and chloroplast DNA diversification.

Leukotrienes mediate 5-hydroxytryptamine-induced plasm extravasation in the rat knee joint via CysLT-type receptors - Y. Wang; J. Mitchell; M. Sharma; A. Gabriel; K. Moriyama; P. Pierce Palmer (Inflammation Research, 2004)

CHARACTERIZATION OF A SPONTANEOUSLY POLARIZING HT-29 CELL LINE, HT-29/cl.f8 - DEANNE M. MITCHELL; JUDITH M. BALL (In Vitro Cellular & Developmental Biology - Animal, 2004)

The herpes simplex virus type 1 early gene (thymidine kinase) promoter is activated in neurons of brain, but not trigeminal ganglia, of transgenic mice in the absence of viral proteins - Christie M Loiacono; Robert Myers; William J Mitchell (Journal of NeuroVirology, 2004)

Genome mosaicism is conserved but not unique in Pseudomonas aeruginosa isolates from the airways of young children with cystic fibrosis - Robert K. Ernst; David A. D′Argenio; Jeffrey K. Ichikawa; M. Gita Bangera; Sara Selgrade; Jane L. Burns; Peter Hiatt; Karen McCoy; Mitchell Brittnacher; Arnold Kas; David H. Spencer; Maynard V. Olson; et al. (Environmental Microbiology, 2003)
Summary Pseudomonas aeruginosa strains from the chronic lung infections of cystic fibrosis (CF) patients are phenotypically and genotypically diverse. Using strain PAO1 whole genome DNA microarrays, we assessed the genomic variation in P. aeruginosa strains isolated from young children with CF (6 months to 8 years of age) as well as from the environment. Eighty‐nine to 97% of the PAO1 open reading frames were detected in 20 strains by microarray analysis, while subsets of 38 gene islands were absent or divergent. No specific pattern of genome mosaicism defined strains associated with CF. Many mosaic regions were distinguished by their low G + C content; their inclusion of phage related or pyocin genes; or by their linkage to a vgr gene or a tRNA gene. Microarray and phenotypic analysis of sequential isolates from individual patients revealed two deletions of greater than 100 kbp formed during evolution in the lung. The gene loss in these sequential isolates raises the possibility that acquisition of pyomelanin production and loss of pyoverdin uptake each may be of adaptive significance. Further characterization of P. aeruginosa diversity within the airways of individual CF patients may reveal common adaptations, perhaps mediated by gene loss, that suggest new opportunities for therapy.

Development and Adoption of a Simple Nonpoint Source Pollution Model for Port Phillip Bay, Australia - Robert M. Argent; V. Grace Mitchell (Environmental Management, 2003)

New records of Australian Myxomycota - R. McHugh; S. L. Stephenson; D. W. Mitchell; M. H. Brims (New Zealand Journal of Botany, 2003)
Twenty‐eight species of myxomycetes and other related organisms not previously known to occur in Australia are reported along with 78 new state records. Records were obtained from collections made in the field and from moist chamber cultures prepared with samples of various types of organic material known to support the growth of myxomycetes. The majority of these samples consisted of bark from living trees and shrubs but some samples of litter, both ground and aerial, and dung also were collected. Physarum crateriforme var. columellatum comb. et stat. nov. is proposed as a new name. The number of species recorded from the continent now stands at 177, which represents approximately 20% of the total number of world species.

Usp9y (ubiquitin-specific protease 9 gene on the Y) is associated with a functional promoter and encodes an intact open reading frame homologous to Usp9x that is under selective constraint - Nicola M. Hall; Graeme M. Brown; Robert A. Furlong; Carole A. Sargent; Michael Mitchell; Dominique Rocha; Nabeel A. Affara (Mammalian Genome, 2003)

Common actions of adenosine receptor agonists in modulating human trabecular meshwork cell transport - J. C. Fleischhauer; C. H. Mitchell; W. D. Stamer; M. O. Karl; K. Peterson-Yantorno; M. M. Civan (The Journal of Membrane Biology, 2003)

Reduced hybrid cluster proteins (HCP) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at high resolution using synchrotron radiation - David Aragão; Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Ming Y. Liu; Carlos Frazão; Lígia M. Saraiva; António V. Xavier; Jean LeGall; Walter M. A. M. van Dongen; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

Population genetics of tandem trypsin inhibitor genes in Arabidopsis species with contrasting ecology and life history - M. J. Clauss; T. Mitchell‐Olds (Molecular Ecology, 2003)
Duplicated genes are important in the evolution and ecology of plant‐defences because herbivore and pathogen attack can be countered via functional diversification at two levels: among duplicated loci and within loci. We explore molecular sequence variation for two members of a defence‐related gene family, Arabidopsis thaliana trypsin inhibitors ( ATTI ), in A. thaliana and a closely related species, A. lyrata subspp. petraea . A worldwide sample of the inbreeding annual A. thaliana had less genetic variation at two ATTI loci (π TOTAL ≤ 0.0006) than observed previously at other functional loci. A significant excess of high frequency derived alleles in the signal sequence and 5′ UTR of ATTI2 was consistent with a model of positive selection. However, demographic processes such as population subdivision and expansion, both likely to have occurred in A. thaliana during the last 10 000 years, can also give rise to similar deviations from neutrality. A single population of A. lyrata subspp. petraea in Germany had up to an order of magnitude more standing genetic variation at ATTI loci than the species‐wide sample of A. thaliana. Although the level of variability for ATTI1 and ATTI2 within this single population was similar to, or even greater than, observed species‐wide diversity for other loci in A. lyrata, there was little evidence to reject an equilibrium neutral model. A spatially explicit sample of 87 A. lyrata subspp. petraea individuals detected outbreeding ( F IS = −0.16; F IT = −0.15) but little population subdivision ( F ST = 0.006) in this self‐incompatible perennial herb. Genetic differences between Arabidopsis species were consistent with, but not fully explained by, divergence in ecology and life history. Diversification appears to have occurred in different functional domains for the tandemly duplicated ATTI1 and ATTI2 genes; the majority of fixed replacements in ATTI1 surround the enzyme binding site of the mature protein, whereas in ATTI2 most functional evolutionary change is located in the signal peptide. This pattern is consistent with a hypothesis of subfunctionalization in trypsin inhibitory function.

Linkage analysis for mapping genes of sex-influenced traits - Nicole R. London; John R. Garbe; Sheila M. Schmutz; Mitchell S. Abrahamsen; Yang Da (Mammalian Genome, 2003)

Anthropogenic climate change for 1860 to 2100 simulated with the HadCM3 model under updated emissions scenarios - T. C. Johns; J. M. Gregory; W. J. Ingram; C. E. Johnson; A. Jones; J. A. Lowe; J. F. B. Mitchell; D. L. Roberts; D. M. H. Sexton; D. S. Stevenson; S. F. B. Tett; M. J. Woodage (Climate Dynamics, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

An Examination of Serotonin and Feeding in the Flesh Fly Neobellieria bullata (Sarcophagidae: Diptera) - A. M. Dacks; T. Nickel; B. K. Mitchell (Journal of Insect Behavior, 2003)

5-Hydroxytryptamine-induced plasma extravasation in the rat knee joint is mediated by multiple prostaglandins - G. Xie; Y. Wang; M. Sharma; A. Gabriel; J. Mitchell; Y. Xing; T. Meuser; P. Pierce Palmer (Inflammation Research, 2003)

Herpes Simplex Virus-1 and Varicella-Zoster Virus Latency in Ganglia - Bradley M Mitchell; David C Bloom; Randall J Cohrs; Donald H Gilden; Peter GE Kennedy (Journal of NeuroVirology, 2003)

Molecular systematics of the New Zealand Pachycladon (Brassicaceae) complex: Generic circumscription and relationships to Arabidopsis sens. lat. and Arabis sens. lat. - P. B. Heenan; A. D. Mitchell; M. Koch (New Zealand Journal of Botany, 2002)
Nuclear ribosomal DNA ITS sequence data were used to assess the relationships of Cheesemania, Ischnocarpus, and Pachycladon to each other and to other genera in the Brassicaceae. Phylogenetic analyses are congruent with other studies that infer the Pachycladon complex (including Pachycladon, Cheesemania, and Ischnocarpus) is monophyletic. The complex occurs within an Arabidopsoid clade that includes Arabidopsis and the recently recognised segregate genera Beringia, Crucihimalaya, Olimarabidopsis, and Pseudoarabidopsis, and the Arabis segregates Boechera and Turritis. The Pachycladon complex is sister to Beringia and Crucihimalaya, and forms a distinct New Zealand lineage. Molecular clock estimates suggest the Pachycladon complex diverged from its nearest relatives between 1.0 and 3.5 million years ago. The close relationship of Cheesemania, Ischnocarpus, and Pachycladon is reflected in low ( Pachycladon to include species placed in Cheesemania and Ischnocarpus. New combinations are made in Pachycladon for species previously placed in Cheesemania and Ischnocarpus. A new name, P. cheesemanii, is presented for Ischnocarpus novae‐zelandiae as that species epithet is preoccupied in Pachycladon.

Linoleic acid metabolites act to increase contractility in isolated rat heart - Lex A. Mitchell; David F. Grant; Russell B. Melchert; Nathan M. Petty; Richard H. Kennedy (Cardiovascular Toxicology, 2002)

The Consequences of CO2 Stabilisation for the Impacts of Climate Change - N. W. Arnell; M. G. R. Cannell; M. Hulme; R. S. Kovats; J. F. B. Mitchell; R. J. Nicholls; M. L. Parry; M. T. J. Livermore; A. White (Climatic Change, 2002)

Developments in ecotoxicity testing - Ed. J.A.K. Mitchell; Joanna E. Burgess; Richard M. Stuetz (Reviews in Environmental Science and Bio/Technology, 2002)

The fate of nitrogen in gypsy moth frass deposited to an oak forest floor - Lynn M. Christenson; Gary M. Lovett; Myron J. Mitchell; Peter M. Groffman (Oecologia, 2002)

Nitroxides as antioxidants: Tempol protects against EO9 cytotoxicity - Ayelet M. Samuni; William DeGraff; Murali C. Krishna; James B. Mitchell (Molecular and Cellular Biochemistry, 2002)

Genetic and molecular control of folate-homocysteine metabolism in mutant mice - Sheila Ernest; Benedicte Christensen; Brian M. Gilfix; Orval A. Mamer; Angela Hosack; Mitchell Rodier; Clemencia Colmenares; James McGrath; Allen Bale; Rudi Balling; David Sankoff; David S. Rosenblatt; et al. (Mammalian Genome, 2002)

Use of stereo aerial photography for quantifying changes in the extent and height of mangroves in tropical Australia - R.M. Lucas; J.C. Ellison; A. Mitchell; B. Donnelly; M. Finlayson; A.K. Milne (Wetlands Ecology and Management, 2002)

Cross‐species microsatellite markers for elucidating population genetic structure in Arabidopsis and Arabis (Brassicaeae) - M. J. Clauss; H. Cobban; T. Mitchell‐Olds (Molecular Ecology, 2002)
Species closely related to model organisms present the opportunity to efficiently apply molecular and functional tools developed by a large research community to taxa with different ecological and evolutionary histories. We complied 42 microsatellite loci that amplify under common conditions in four closely related Arabidopsis : A. thaliana ; A. halleri ; A. lyrata ssp. lyrata ; and A. lyrata ssp. petraea , as well as in one more distantly related crucifer; Arabis drummondii . Variation at these loci is amenable to a diversity of applications including population genetics, phylogeographical analyses, mapping of inter and intraspecific crosses, and recombination mapping. Our analysis of microsatellite variation illustrates significant differences in population genetic parameters among three Arabidopsis species. A population of A. thaliana , an inbreeding annual plant associated with disturbed habitats, was highly monomorphic ( P = 8% percent polymorphic loci) and only 0.2% heterozygous for 648 locus‐by‐individual combinations. A population of the self‐incompatible perennial herb, A. halleri , was more genetically variable ( P = 71%) and had an excess of heterozygosity that may reflect a recent population bottleneck associated with human‐mediated founder events. A population of the self‐incompatible perennial herb, A. lyrata ssp. petraea , was even more genetically variable ( P = 86%) and appeared to be at mutation‐drift equilibrium. Population structure estimated from neutrally evolving loci provides an empirical expectation against which hypotheses of adaptive evolution at functional loci can be tested.

Microsatellites in Zea – variability, patterns of mutations, and use for evolutionary studies - Y. Matsuoka; S. E. Mitchell; S. Kresovich; M. Goodman; J. Doebley (Theoretical and Applied Genetics, 2002)

Evaluation of Hbr (MITE) markers for assessment of genetic relationships among maize (Zea mays L.) inbred lines - A. M. Casa; S. E. Mitchell; O. S. Smith; J. C. Register III; S. R. Wessler; S. Kresovich (Theoretical and Applied Genetics, 2002)

Introgression and stabilization oferwinia tuber soft rot resistance into potato after somatic hybridization ofsolanum tuberosum ands. brevidens - J. Mitchell McGrath; Christie E. Williams; Geraldine T. Haberlach; Susan M. Wielgus; Thomas F. Uchytil; John P. Helgeson (American Journal of Potato Research, 2002)

Molecular characterization of a novel recombinant strain of human astrovirus associated with gastroenteritis in children - J. E. Walter; J. Briggs; M. L. Guerrero; D. O. Matson; L. K. Pickering; G. Ruiz-Palacios; T. Berke; D. K. Mitchell (Archives of Virology, 2001)

How are climate and marine biological outbreaks functionally linked? - Marshall L. Hayes; Joseph Bonaventura; Todd P. Mitchell; Joseph M. Prospero; Eugene A. Shinn; Frances Van Dolah; Richard T. Barber (Hydrobiologia, 2001)

Use of Stable Isotope Ratios for Evaluating Sulfur Sources and Losses at the Hubbard Brook Experimental Forest - M. J. Mitchell; B. Mayer; S. W. Bailey; J. W. Hornbeck; C. Alewell; C.T. Driscoll; G.E. Likens (Water, Air, & Soil Pollution, 2001)

Expression and conservation of processed copies of the RBMX gene - Patricia A. Lingenfelter; Margaret L. Delbridge; Sushma Thomas; Hopi E. Hoekstra; Michael J. Mitchell; Jennifer A. Marshall Graves; Christine M. Disteche (Mammalian Genome, 2001)

Climate Change and Cryptosporidiosis: A Qualitative Analysis - Elizabeth Casman; Baruch Fischhoff; Mitchell Small; Hadi Dowlatabadi; Joan Rose; M. Granger Morgan (Climatic Change, 2001)

N Storage and Cycling in Vegetation of a Forested Wetland: Implications for Watershed N Processing - Joseph M. Bischoff; Paul Bukaveckas; Myron J. Mitchell; T. Hurd (Water, Air, & Soil Pollution, 2001)

A paradox: urgent BRCA genetic testing - G. Mitchell; A. Ardern-Jones; M. Kissin Mchir; R. Taylor; R. A. Eeles (Familial Cancer, 2001)

Proteomic analysis reveals a novel set of cell wall proteins in a transformed tobacco cell culture that synthesises secondary walls as determined by biochemical and morphological parameters - Kristopher A. Blee; Edward R. Wheatley; Victoria A. Bonham; Geoffrey P. Mitchell; Duncan Robertson; Antoni R. Slabas; Michael M. Burrell; Przemyslaw Wojtaszek; G. Paul Bolwell (Planta, 2001)

A meta-analysis of the response of soil respiration, net nitrogen mineralization, and aboveground plant growth to experimental ecosystem warming - L. Rustad; J. Campbell; G. Marion; R. Norby; M. Mitchell; A. Hartley; J. Cornelissen; J. Gurevitch (Oecologia, 2001)

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

The relationship between Y chromosome DNA haplotypes and Y chromosome deletions leading to male infertility - L. Quintana-Murci; C. Krausz; E. Heyer; J. Gromoll; I. Seifer; D.E. Barton; T. Barrett; N.E. Skakkebaek; E. Rajpert-De Meyts; M. Mitchell; A.C. Lee; M.A. Jobling; et al. (Human Genetics, 2001)

Chemical scoring and ranking assessment model - Erin M. Snyder; Shane A. Snyder; John Paul Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2001)

Phylogenomic Analysis of the α Proteasome Gene Family from Early-Diverging Eukaryotes - Juan L. Bouzatrid="*"rid="†"; Leslie K. McNeilrid="*"; Hugh M. Robertson; Leellen F. Solter; Julie E. Nixon; Jonathan E. Beever; H. Rex Gaskins; Gary Olsen; Shankar Subramaniam; Mitchell L. Sogin; Harris A. Lewin (Journal of Molecular Evolution, 2000)

Structural Evidence for the Evolution of Pyrogenic Toxin Superantigens - David T. Mitchell; David G. Levitt; Patrick M. Schlievert; Douglas H. Ohlendorf (Journal of Molecular Evolution, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Optimal detection and attribution of climate change: sensitivity of results to climate model differences - G. C. Hegerl; P. A. Stott; M. R. Allen; J. F. B. Mitchell; S. F. B. Tett; U. Cubasch (Climate Dynamics, 2000)

Crystal chemistry of perovskite-type compounds in the tausonite-loparite series, (Sr 1−2 x Na x La x )TiO 3 - R. H. Mitchell; A. R. Chakhmouradian; P. M. Woodward (Physics and Chemistry of Minerals, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

The effects of in situ drying on sediment–phosphate interactions in sediments from an old wetland - D. S. Baldwin; A. M. Mitchell; G. N. Rees (Hydrobiologia, 2000)

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

IDENTIFYING DIURNAL FORAGING HABITAT OF ENDANGERED HAWAIIAN MONK SEALS USING A SEAL‐MOUNTED VIDEO CAMERA - Frank A. Parrish; Mitchell P. Craig; Timothy J. Ragen; Gregory J. Marshall; Birget M. Buhleier (Marine Mammal Science, 2000)
A bstract The Hawaiian monk seal ( Monachus schauinslandi ) is thought to be a foraging generalist, preying on numerous species in diverse habitats of the subtropical Northwestern Hawaiian Islands. At the atoll of French Frigate Shoals, recent evidence of emaciation and low survival in monk seals prompted a search for their specific prey communities and foraging habitat. A video camera (National Geographic Television's CRITTERCAM) fitted to 24 adult male seals documented benthic and demersal foraging on the deep slopes (50‐80 m) of the atoll and neighboring banks. The number of bottom searches for prey was compared by year, time of day, type of bottom, individual seal, and length of bottom time. Analysis of variance identified a significant interaction of seal and bottom type, explaining 65% of the total variance. Seals fed on communities of cryptic fauna (fish and large invertebrates) in transitional “ecotone” regions of low relief where consolidated substrate, rubble, and talus bordered areas of sand. Independent areal surveys of bottom types throughout the atoll and neighboring banks suggest that the type of bottom selected as foraging habitat represents a relatively small percentage of the total benthic area available.

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the north american great lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

The simulation of SST, sea ice extents and ocean heat transports in a version of the Hadley Centre coupled model without flux adjustments - C. Gordon; C. Cooper; C. A. Senior; H. Banks; J. M. Gregory; T. C. Johns; J. F. B. Mitchell; R. A. Wood (Climate Dynamics, 2000)

ESTABLISHMENT AND CHARACTERIZATION OF A CAPRINE MAMMARY MYOEPITHELIAL CELL LINE (CMMyoEC) - A. G. PANTSCHENKO; M. R. BARBER; J. WOODCOCK-MITCHELL; S. L. BUSHMICH; T. J. YANG (In Vitro Cellular & Developmental Biology - Animal, 2000)

Species of Agaricus occurring in New Zealand - A. D. Mitchell; M. Walter (New Zealand Journal of Botany, 1999)
A key is provided for 21 species occurring in New Zealand: Agaricus arvensis,A. augustus, A. bambusae var. australis, A. bernardii, A. bisporus var. bisporus, A. bitorquis, A. campestris var. campestris, A. campestris cf. var. floccipes, A. cupreobrunneus, A. horakii, A. impudicus (= A. variegans ) ,A. lanatoniger, A. lanipes,A. meleagris, A. oligocystis, A. porphyrocephalus, A. purpureoniger, A. semotus, A. subperonatus, A. viridopurpurascens , and A. xanthoderma . Full descriptions are given for those taxa encountered by the authors in the field, including 10 species which are considered cosmoplitan in distribution. Six of these species are new records for New Zealand.

Molecular characterization of radiation- and chemically induced mutations associated with neuromuscular tremors, runting, juvenile lethality, and sperm defects in jdf2 mice - Mitchell Walkowicz; Yonggang Ji; Xiaojia Ren; Bernhard Horsthemke; Liane B. Russell; Dabney Johnson; Eugene M. Rinchik; Robert D. Nicholls; Lisa Stubbs (Mammalian Genome, 1999)

Diel variation in horizontal distribution of Daphnia and Ceriodaphnia in oligotrophic and mesotrophic lakes with contrasting fish densities - Torben L. Lauridsen; Erik Jeppesen; Stuart F. Mitchell; David M. Lodge; Romi L. Burks (Hydrobiologia, 1999)

Mineral Soil and Solution Responses to Experimental N and S Enrichment at the Bear Brook Watershed in Maine (BBWM) - I. Fernandez; L. Rustad; M. David; K. Nadelhoffer; M. Mitchell (Environmental Monitoring and Assessment, 1999)

Towards the Construction of Climate Change Scenarios - John F. B. Mitchell; T. C. Johns; M. Eagles; W. J. Ingram; R. A. Davis (Climatic Change, 1999)

Subtleties in Perception and Discrimination by Cabbage Looper Moths, Trichoplusia ni, of the two 14-carbon Acetate Sex Pheromone Components - M. S. Mayer; E. R. Mitchell (Journal of Chemical Ecology, 1999)

The effects of sediment desiccation on the potential for nitrification, denitrification, and methanogenesis in an Australian reservoir - A. M. Mitchell; D. S. Baldwin (Hydrobiologia, 1999)

Metals in Surficial Sediments of the North-West Irish Sea - M. Charlesworth; M. Service; S. H. Mitchell; W. T. Oliver (Bulletin of Environmental Contamination and Toxicology, 1999)

Variant in sulfonylurea receptor-1 gene is associated with high insulin concentrations in non-diabetic Mexican Americans: SUR-1 gene variant and hyperinsulinemia - Denise L. Goksel; Kathryn Fischbach; Ravindranath Duggirala; Braxton D. Mitchell; Lydia Aguilar-Bryan; John Blangero; M. P. Stern; Peter O’Connell (Human Genetics, 1998)

Glycoalkaloid accumulation during tuber development of early potato cultivars - F. Papathanasiou; S. H. Mitchell; Barbara M. R. Harvey (Potato Research, 1998)

Rapid measure of sex pheromone emission from plastic rope dispensers: Example of utility in sexual communication disruption of the diamondback moth,Plutella xylostella1 - M. S. Mayer; E. R. Mitchell (Phytoparasitica, 1998)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)

Frequency choice for radio telemetry: the HF vs. VHF conundrum - Mitchell M. Sisak; James S. Lotimer (Hydrobiologia, 1998)

DNA damage induced by ultraviolet radiation in coral-reef microbial communities - M. M. Lyons; P. Aas; J. D. Pakulski; L. Van Waasbergen; R. V. Miller; D. L. Mitchell; W. H. Jeffrey (Marine Biology, 1998)

Changes in daily precipitation under enhanced greenhouse conditions - K. J. Hennessy; J. M. Gregory; J. F. B. Mitchell (Climate Dynamics, 1997)

Reinstatement of Raukaua , a genus of the Araliaceae centred in New Zealand - A. D. Mitchell; D. G. Frodin; M. J. Heads (New Zealand Journal of Botany, 1997)
The genus Pseudopanax is recognised as polyphyletic. Morphological and anatomical characters are described that support the monophyly of Pseudopanax anomalus , P. edgerleyi , and P. simplex . Reinstatement of the genus Raukaua is recommended to accommodate these species. The new combinations R. anomalus and R. simplex are made.

An evaluation of the utility of SSR loci as molecular markers in maize (Zea mays L.): comparisons with data from RFLPS and pedigree - J. S. C. Smith; E. C. L. Chin; H. Shu; O. S. Smith; S. J. Wall; M. L. Senior; S. E. Mitchell; S. Kresovich; J. Ziegle (Theoretical and Applied Genetics, 1997)

Influence of a proton pump inhibitor-based therapy onHelicobacter pylori strain selection - S. L. Hazell; H. M. Mitchell; G. Hanna; G. Daskalopoulos (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Floral flavonoids and pH in Dendrobium orchid species and hybrids - Adelheid R. Kuehnle; David H. Lewis; Kenneth R. Markham; Kevin A. Mitchell; Kevin M. Davies; Brian R. Jordan (Euphytica, 1997)

Depression, Cognitive Impairment, and Understanding of Medication Directions in Hospitalized Elderly Patients - Shelly L. Gray; Mark A. Sager; Mitchell R. Lestico; M. Jalaluddin (Pharmaceutical Research, 1997)

Style and timing of glaciation in the Lahul Himalaya, northern India: a framework for reconstructing late Quaternary palaeoclimatic change in the western Himalayas - LEWIS A. OWEN; RICHARD M. BAILEY; EDWARD J. RHODES; WISHART A. MITCHELL; PETE COXON (Journal of Quaternary Science, 1997)

The second Hadley Centre coupled ocean-atmosphere GCM: model description, spinup and validation - T. C. Johns; R. E. Carnell; J. F. Crossley; J. M. Gregory; J. F. B. Mitchell; C. A. Senior; S. F. B. Tett; R. A. Wood (Climate Dynamics, 1997)

The establishment and regeneration of a range ofCuphea germplasm t in vitro - Steve Millam; Susan M. Mitchell; Elisabetta Moscheni; Janie E. Lyon (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Hormone-sensitive lipase (Lipe): Sequence analysis of the 129Sv mouse Lipe gene - R. Sztrolovics; S. P. Wang; P. Lapierre; H. S. Chen; M -F. Robert; G. A. Mitchell (Mammalian Genome, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Anaerobic O-demethylation of chlorinated guaiacols byAcetobacterium woodii andEubacterium limosum - Max M. Hggblom; Mitchell H. Berman; Anne Cornish Frazer; L. Y. Young (Biodegradation, 1993)

Correlation between humoral immune responses and presence of virus in the CNS in dogs experimentally infected with canine distemper virus - B. K. Rima; N. Duffy; W. J. Mitchell; B. A. Summers; M. J. G. Appel (Archives of Virology, 1991)

Zonal and meridional circulations in the equatorialzone as deduced from the divergence field of the surface wind - Wang Shaowu; Todd P. Mitchell; John M. Wallace (Advances in Atmospheric Sciences, 1987)

Factors influencing peroxisome proliferation in cultured rat hepatocytes - Angela M. Mitchell; James W. Bridges; Clifford R. Elcombe (Archives of Toxicology, 1984)

Organochlorine pesticide, polychlorobiphenyl, and mercury residues in bald eagle eggs?1969?79?and their relationships to shell thinning and reproduction - Stanley N. Wiemeyer; Thair G. Lamont; Christine M. Bunck; Charles R. Sindelar; Francis J. Gramlich; James D. Fraser; Mitchell A. Byrd (Archives of Environmental Contamination and Toxicology, 1984)

Mutagenicity of potential effluents from an experimental low btu coal gasifier - J. M. Benson; C. E. Mitchell; R. E. Royer; C. R. Clark; R. L. Carpenter; G. J. Newton (Archives of Environmental Contamination and Toxicology, 1982)

Toxicological characterization of the process stream from an experimental low Btu coal gasifier - J. M. Benson; J. O. Hill; C. E. Mitchell; G. J. Newton; R. L. Carpenter (Archives of Environmental Contamination and Toxicology, 1982)

Electron probe X-ray microanalysis of arsenic inclusions in fish - Elsie M. B. Sorensen; Nancy K. R. Smith; Ruben Ramirez-Mitchell (Archives of Environmental Contamination and Toxicology, 1982)

Rhinoviruses: Kinetics of ultraviolet inactivation and effects of UV and heat on immunogenicity - J. H. Hughes; M. Mitchell; V. V. Hamparian (Archives of Virology, 1979)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Relative concentrations of14C-DDT and of two polychlorinated biphenyls in the lipids of cod tissues after a single oral dose - A. I. Mitchell; P. A. Plack; I. M. Thomson (Archives of Environmental Contamination and Toxicology, 1977)

Transcriptional changes in pupal hypoderm in Drosophila melanogaster - Herschel K. Mitchell; Loveriza S. Lipps; Ursula M. Tracy (Biochemical Genetics, 1977)

Physiological and DNA characterization of Candida maltosa, a hydrocarbon-utilizing yeast - S. A. Meyer; K. Anderson; R. E. Brown; M. Th. Smith; D. Yarrow; G. Mitchell; D. G. Ahearn (Archives of Microbiology, 1975)

Sectional notes - L. M. Ware; M. A. Lindsay; W. B. Ward; H. A. Reiley; A. G. Tolaas; Marx Koehnke; John C. Campbell; Robert Schmidt; Earl B. Tussing; K. W. Lauer; Mitchell Jenkins; John Noonan; et al. (American Journal of Potato Research, 1941)

Sectional notes - L. M. Ware; Geo D. Ruehle; J. G. Richard; J. C. Campbell; E. V. Hardenbueg; C. A. Henderson; Robert Schmidt; J. Mitchell Jenkins; John Noonan (American Journal of Potato Research, 1941)

Sectional notes - M. A. Lindsay; E. Marx; E. R. Bennett; C. L. Fitch; A. A. Henderson; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1941)

Sectional notes - L. M. Ware; E. Marx; A. H. Eddins; J. G. Richard; Robert Schmidt; Mitchell Jenkins (American Journal of Potato Research, 1939)

Sectional notes - L. M. Ware; W. M. Fifield; J. G. Richards; J. V. Pace; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1939)